Method for producing composite having elastomer and filler
By filling solid elastomer and wet filler in a mixer, and mixing and liquid removal at 65°C or higher, the problem of poor dispersion of filler in solid elastomer is solved, and the machinery of elastomer composites is improved Strength and performance.
Patent Information
- Application Number
- CN202411121963.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-05
- Filing Date
- 2020-06-04
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to efficiently disperse fillers in solid elastomers, especially in natural rubbers, resulting in poor mechanical strength and elastomer composite performance, and the wet mixing technology has operational challenges in the manufacturing process.
The solid elastomer and wet filler are loaded into a kneader with a rotor, and the liquid is removed by controlling the temperature and evaporation, and the filler is efficiently dispersed in the elastomer. The specific steps include mixing at a temperature of 65°C or higher and passing Evaporation removes some of the liquid, ensuring dispersibility of the 20 phr or higher loading of the filler in the composite.
The dispersion quality and functionality of the filler in the elastomer are improved, the yield loss of filler is reduced, the properties of the corresponding rubber compound are improved, and the problem of easy degradation of natural rubber is solved.
Smart Images

Figure BDA0004995355440000551 
Figure BDA0004995355440001031 
Figure BDA0004995355440001061
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 202080055982.8, application date June 4, 2020, and invention name “Method for preparing a composite having an elastomer and a filler”. Background Art
[0002] There is a continuing desire in the rubber industry to develop methods for dispersing fillers in elastomers and a particular desire to develop methods for doing so efficiently in terms of filler dispersion quality, time, effort, and / or cost.
[0003] Numerous products of commercial significance are formed by elastomeric compositions in which reinforcing filler materials are dispersed in any of a variety of synthetic elastomers, natural rubber or elastomer blends. For example, carbon black (carbon black) and silica are widely used to reinforce natural rubber and other elastomers. It is common to produce a masterbatch, i.e. a premix of reinforcing materials, elastomers, and various optional additives such as extender oils. Such a masterbatch is then compounded with processing and curing additives and, when cured, produces numerous products of commercial significance. Such products include, for example, pneumatic and non-pneumatic or solid tires for vehicles, including a tread portion, which includes a cap and a base, an undertread, an innerliner, a sidewall, a wire skim, a carcass, etc. Other products include, for example, engine mounts, bushings, conveyor belts, windshield wipers, rubber parts for aerospace and marine equipment, vehicle track elements, seals, linings, gaskets, wheels (steering wheels), bumpers, shock absorption systems, etc.
[0004] Good dispersion of reinforcement fillers in rubber compounds has been recognized as a factor to achieve mechanical strength and consistent elastomeric composite and rubber compound performance. Considerable effort has been paid to develop a method for improving dispersion quality, and multiple solutions have been provided to cope with this challenge. For example, more intense mixing can improve the dispersion of reinforcement fillers, but the elastomer degradation (deterioration) to which the filler is dispersed can be made. This is particularly problematic in the case of natural rubber, which is highly prone to mechanical / thermal degradation, especially under dry mixing conditions.
[0005] As an alternative to dry mixing technology, it is known to feed elastomer latex or polymer solution and carbon black or silica slurry (slurry) to a liquid mixing system, such as a stirred tank. For natural rubber latex and emulsified synthetic elastomers such as styrene butadiene rubber (SBR), or other elastomeric polymers in liquid form, such "liquid masterbatch" technology can be used. However, although wet mixing technology has shown promise, intermittent wet mixing can be challenging in terms of manufacturing operations. Continuous or semi-continuous technologies for producing liquid masterbatches, such as those disclosed in U.S. Patent Nos. 6,048,923 and 8,586,651 (the contents of which are incorporated herein by reference), have always been effective for producing elastomer-filler composites characterized by high quality. However, these processes are limited to rubbers in liquid form such as elastomer latex or solution form.
[0006] Therefore, there is a need to develop methods for incorporating fillers into solid elastomers to achieve acceptable or improved elastomeric compound dispersion quality and functionality from elastomeric compound masterbatches that can translate into acceptable or improved properties in corresponding vulcanized rubber compounds and rubber articles. Summary of the invention
[0007] Disclosed herein are methods of preparing composites from solid elastomer(s) and wet filler(s), and products therefrom, including composites, vulcanizates, and articles.
[0008] One aspect is a method for preparing a composite, comprising: (a) charging a mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount ranging from 15% to 65% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and performing the mixing in at least one of the mixing steps, wherein the mixer has at least one temperature control means set to a temperature Tz of 65°C or higher, and removing at least a portion of the liquid from the mixture by evaporation; and (c) discharging a composite from the mixer, the composite comprising a filler dispersed in the elastomer at a loading of at least 20 phr, wherein the filler yield loss is no more than 10% (e.g., no more than 5%), wherein the composite has a liquid content of no more than 10% by weight based on the total weight of the composite.
[0009] On the other hand is a method for preparing a composite, which comprises: (a) charging a mixer with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler, wherein the filling factor of the at least solid elastomer and the wet filler on a dry weight basis is not greater than 68%, (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means, and at least a portion of the liquid is removed from the mixture by evaporation; and (c) discharging a composite from the mixer, the composite comprising a filler dispersed in the elastomer at a loading of at least 20 phr, wherein the filler yield loss is not greater than 10%, wherein the composite has a liquid content of not greater than 10% by weight based on the total weight of the composite.
[0010] On the other hand is a method for preparing a composite, which comprises (a) charging a mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in the mixer in one or more mixing steps to form a mixture, and in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation; (c) discharging a composite from the mixer, the composite comprising a filler dispersed in the elastomer at a loading of at least 20 phr, wherein the filler yield loss is no more than 10%, and wherein the composite has a liquid content of no more than 10% by weight based on the total weight of the composite.
[0011] In another aspect is a method for preparing a composite, comprising: (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation; (c) discharging the mixture from the first mixer, the mixture comprising the filler dispersed in the elastomer at a loading of at least 20 phr, wherein the mixture (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its maximum level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ramless; and (vi) the filling factor of the mixture is in the range of 25%-70%; and (e) discharging the composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
[0012] On the other hand, a method for preparing a composite comprises: (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means and an average specific power of at least 2.5 kW / kg is applied during the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation; (c) discharging the mixture from the first mixer, the mixture comprising the filler dispersed in the elastomer in an amount of at least 20 phr, wherein the mixture having a liquid content reduced to an amount less than the liquid content at the beginning of step (b), and wherein the mixture has a material temperature in the range of 100°C-180°C; (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its maximum level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ram-free; and (vi) the filling factor of the mixture is in the range of 25%-70%; and (e) discharging the composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
[0013] On the other hand, the method is a method for preparing a composite, which comprises: (a) charging a continuous flow of at least a solid elastomer and a granulated wet filler into the input end of a continuous mixer, wherein the wet filler comprises a filler and a liquid present in an amount of at least 15 weight percent based on the total weight of the wet filler; (b) conveying the solid elastomer and the wet filler along the length of the continuous mixer, wherein during the conveying, mixing occurs and at least a portion of the liquid is removed by evaporation; and (c) discharging a composite from the discharge end of the continuous mixer, the composite comprising the filler dispersed in the elastomer at a loading of at least 20 phr, wherein the filler yield loss is no more than 10%, and wherein the composite has a liquid content of no more than 10 weight percent based on the total weight of the composite. One or more embodiments may be applied including: a continuous mixer having an elongated chamber; mixing in (b) may occur by contacting the solid elastomer and the wet filler with one or more rotors positioned axially in the elongated chamber; the temperature of the one or more rotors may be controlled; the mixer may be a continuous mixer, such as a continuous compounder; conveying (b) may be carried out by at least one rotatable screw, through which mixing also occurs; the mixer may be a twin-screw extruder; the loading in (a) may include loading a substantially continuous flow of a pre-blend of at least the solid elastomer and the granulated wet filler; the loading in (a) may include separately loading a first substantially continuous flow of the solid elastomer and a second substantially continuous flow of the granulated wet filler.
[0014] Another aspect is a method for preparing a composite, comprising: (a) charging a mixer with a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, performing the mixing and removing at least a portion of the liquid from the mixture by evaporation at a mixer temperature controlled by at least one temperature control means, wherein during the mixing, the mixer reaches an indicated temperature of 120° C. or higher; (c) optionally adding at least one additive selected from an antidegradant and a coupling agent during the charging (a) or the mixing (b), and optionally adding one or more rubber chemicals (rubber chemicals, rubber compounding chemicals, rubber (d) discharging a composite from a mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is not greater than 10%, wherein the composite has a liquid content of not greater than 10 weight percent based on the total weight of the composite, and said loading (a) and said mixing (b) before the mixer reaches the indicated temperature are conducted in the substantial absence of the one or more rubber chemicals.
[0015] With respect to any aspect or method or embodiment disclosed herein, the method may further comprise any one or more of the following embodiments, as appropriate: the at least one temperature control means heats at least the wall of the mixer; the at least one temperature control means comprises a jacket having a fluid flow means; in one or more mixing steps (step (b)) and optionally during the filling (step (a)), the at least one temperature control means is set to a temperature T of 50°C or more, or 60°C or more, or 65°C or more, or 70°C or more, or in the range of 30°C-150°C, or in the range of 50°C-100°C, or in the range of 60°C-100°C, or in the range of 65°C-100°C, or in the range of 70°C-100°C. z at least 50% of the filler is carbon black and / or silicon-treated carbon black and in one or more mixing steps (step (b)) and optionally during the filling (step (a)), the at least one temperature control means is set to a temperature T of 65°C or higher, or 70°C or higher, or in the range of 65°C-100°C, or in the range of 70°C-100°C z at least 50% of the filler is silica and in one or more mixing steps (step (b)) and optionally during filling (step (a)), the at least one temperature control means is set to a temperature T of 50°C or more, or 60°C or more, or 65°C or more, or 70°C or more, or in the range of 30°C-150°C, or in the range of 50°C-100°C, or in the range of 60°C-100°C, or in the range of 65°C-100°C, or in the range of 70°C-100°C z .
[0016] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: in at least one of the mixing steps, the mixing is carried out at a mixer temperature controlled by at least one temperature control means and the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; the tip speed is at least 0.7 m / s, or at least 1 m / s, or in the range of 0.6 m / s-10 m / s.
[0017] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the total specific energy obtained for mixing is at least 1,100 kJ / kg of the compound; the total specific energy obtained for mixing is at least 1,100 kJ / kg of the compound and the filler includes silica; the total specific energy obtained for mixing is at least 1,400 kJ / kg of the compound; the total specific energy obtained for mixing is at least 1,500 kJ / kg of the compound; after substantially all of the wet filler has been loaded into the mixer, the total specific energy obtained for mixing is at least 1,100 kJ / kg of the compound and the filler includes silica; 100%填料 is at least 1,100 kJ / kg of compound; after at least 75% by weight of the total wet filler has been loaded into the mixer, the resulting specific energy E for mixing 75%填料 is at least 1,300 kJ / kg of the compound; the mixing of step (b) (in one or more mixing steps) comprises applying energy E to at least one rotor of the mixer at an energy efficiency in the range of 20%-80% in accordance with the following equation R :Energy efficiency = heat load / E R x100%, wherein the heat load is the energy required to remove liquid from 1 kg of the composite with 100% efficiency; the energy efficiency range is 40%-55%; the time-averaged release rate of liquid per kg of the composite on a dry weight basis ranges from 0.01-0.14 kg / (min·kg) or 0.01-0.07 kg / (min·kg); and the one or more mixing steps include applying an average specific power of at least 2.5 kW / kg during the mixing time, and the mixing time may be the time for the top bolt to be lowered (hammer down, ram down, impact, ram down) time.
[0018] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filling factor of the mixture is no greater than 72%, no greater than 70%, no greater than 68%, or in the range of 50%-70%, or 50%-68%; the mixer is an intermittent mixer including a top pin capable of moving vertically downward to a lowest position, wherein during mixing, the mixer is operated with a maximum top pin offset from the lowest position being no greater than 30% of the diameter of the one or more rotors.
[0019] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the wet filler has liquid present in an amount of at least 15% by weight, at least 20% by weight, at least 30% by weight; the wet filler has liquid present in an amount ranging from 30% to 65% by weight, or 40% to 65% by weight; the wet filler has liquid present in an amount determined as a function of the OAN of the filler, satisfying the following equation: k*OAN / (100+OAN)*100, wherein for carbon black k ranges from 0.6 to 1.1, or 0.8 to 1.05, or 0.9 to 1; the mixture further includes a non-wet filler; the wet filler is in the form of a powder, paste, pellets or cake, such as a powder or pellets; at least 30% by weight of the total filler loaded in the mixer is wet filler; at least 90% by weight of the total filler loaded in the mixer is wet filler.
[0020] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: mixing includes removing at least 50% by weight of the liquid by evaporation; mixing also includes removing liquid from the mixture by expression, compaction, wringing, or any combination thereof; the liquid includes water; the liquid further includes at least one component selected from a base, an acid, a salt, a surfactant, and a processing aid.
[0021] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the loading includes loading at least a portion of the solid elastomer into the mixer, and then loading at least a portion of the wet filler into the mixer; the loading includes multiple additions of the filler; when loading at least a portion of the solid elastomer into the mixer, the elastomer is heated to a temperature of 90° C. or higher, and then loading at least a portion of the wet filler into the mixer; during the loading or mixing, the method further includes adding at least one antidegradant; the at least one antidegradant is N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine.
[0022] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the discharged composite has a liquid content of no more than 5% by weight; the discharged composite has a liquid content of no more than 3% by weight; the discharged composite has a liquid content of no more than 2% by weight; the discharged composite has a liquid content in the range of 0.1%-10% by weight; and the composite has a filler yield loss of no more than 5%, or no more than 3% by weight.
[0023] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: (in step (c)) the discharged composite is free of one or more rubber chemicals; the one or more rubber chemicals are selected from processing aids and activators; the one or more rubber chemicals are selected from zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and processing oils; the mixture consists essentially of solid elastomer and wet filler; the mixture consists essentially of solid elastomer, wet filler, and antidegradant; the composite consists essentially of filler dispersed in elastomer, and antidegradant; the composite consists of filler dispersed in elastomer; the composite consists of filler dispersed in elastomer, and antidegradant.
[0024] With respect to any aspect or method or embodiment disclosed herein, mixing is performed in one mixing step, as appropriate.
[0025] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the mixing is performed in two or more mixing steps; the mixer is a first mixer and the method further includes, after the mixing and before the discharge, further mixing the mixture in the first mixer or the second mixer or both to obtain a composite; before the further mixing, after the mixing, the method further includes stopping the mixing to obtain the mixture; the further mixing reduces the liquid content of the mixture compared to the liquid content of the mixture after the mixing; the mixture formed in step (b) obtains a material temperature of less than 180° C. before the start of the further mixing by a rest time or by cooling or both; a second mixer different from the first mixer in step (a) is used for the further mixing; after the further mixing and before the discharge, further mixing is performed in a third mixer to obtain a composite The first mixer is a tangential mixer or an intermeshing mixer, and the second mixer is a tangential mixer, an intermeshing mixer, a kneader, or a roll mill; the first mixer is a tangential mixer or an intermeshing mixer, and the second mixer is a kneader, a single screw extruder, a twin screw extruder, a multi-screw extruder, a continuous mixer, or a roll mill; the first mixer is a first tangential mixer and the second mixer is a second tangential mixer; the second mixer is operated under at least one of the following conditions: (i) 5 psi or less; (ii) the push pin is raised to at least 75% of its maximum level; (iii) the push pin is operated in a floating mode; (iv) the push pin is positioned so that it does not substantially contact the mixture; (v) the mixer is push pin-free; and (vi) the filling factor of the mixture ranges from 25% to 70%; the method further includes discharging the composite from the first mixer into the second mixer; mixing and further mixing are carried out as an intermittent process, a continuous process, a semi-continuous process, or a combination thereof.
[0026] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the period between the start of mixing and discharge is less than 30 minutes, less than 15 minutes, in the range of 3 minutes to 30 minutes, in the range of 5 minutes to 15 minutes; the time for the top bolt to be lowered is less than 30 minutes, less than 15 minutes, less than 10 minutes, in the range of 3 minutes to 30 minutes or 5 minutes to 15 minutes, or 5 minutes to 10 minutes.
[0027] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: at discharge, the mixer temperature range is 120°C-180°C or 130°C-170°C.
[0028] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the method may be a continuous process; the mixing may be carried out in a continuous mixer; the method may be a batch process; the mixer is a closed mixer; the mixer is a tangential mixer or an intermeshing mixer; the mixer has a chamber capacity of at least 10 L; the mixing is carried out with at least one rotor selected from a two-ribbed rotor, a four-ribbed rotor, a six-ribbed rotor, an octagonal rotor, and one or more screw rotors.
[0029] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the composite has an oil content of less than 5% by weight based on the total weight of the composite or less than 1% by weight based on the total weight of the composite, and optionally the filler comprises silica.
[0030] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: further including at least one additional or post-processing step selected from extrusion, calendering, grinding, granulation, packaging, compounding, and tableting; the at least one additional processing step is carried out with one or more of a kneader, a roller mill, a screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous mixer, and a twin-screw tablet press.
[0031] With respect to any aspect or method or embodiment disclosed herein, where appropriate, the method may further include any one or more of the following embodiments: the filler includes at least one material selected from the following: carbonaceous material, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxide, metal carbonate, pyrolytic carbon, graphene, graphene oxide (graphene oxide), reduced graphene oxide (reduced graphene oxide), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof; the filler includes at least one material selected from carbon black, and coated and treated materials thereof (e.g., carbon black and / or silicon-treated carbon black); at least 50% by weight of the filler is selected from carbon black, and coated and treated materials thereof; at least 90% by weight of the filler is carbon black.
[0032] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler comprises carbon black dispersed in the elastomer at a loading in the range of 30 phr-150 phr, such as in the range of 20 phr-100 phr, 30 phr-70 phr, or 40 phr-65 phr; the filler comprises carbon black having a loading in the range of 30 phr-150 phr, such as in the range of 20 phr-100 phr, 30 phr-70 phr, or 40 phr-65 phr; 2 / g-200m 2 / g of STSA carbon black; fillers include having a range of 60m 2 / g-200m 2 / g of STSA carbon black; filler includes carbon black having a COAN in the range of 60 mL / 100 g-120 mL / 100 g; filler includes carbon black having a COAN in the range of 60 m 2 / g-170m 2 / g of STSA and a carbon black with a COAN ranging from 70mL / 100g to 115mL / 100g.
[0033] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the wet filler comprises carbon black that has never been dried; the wet filler comprises dry carbon black that has been rewetted; the wet filler comprises dry carbon black that has been rewetted in a pelletizer, fluidized bed, sprayer, mixer, or drum; the dry carbon black pellets are subjected to at least one process selected from grinding, pelletizing, milling, and classification before being rewetted; the wet filler comprises carbon black pellets; the wet filler comprises one or more of pelletized, agglomerated, or fluffed carbon black;
[0034] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: at least one filler is selected from carbon black, silica, and silicon-treated carbon black, and the elastomer comprises natural rubber; at least one filler is selected from carbon black, silica, and silicon-treated carbon black, and the elastomer comprises natural rubber and at least one additional elastomer; and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber.
[0035] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler includes silica; at least 50% of the filler is silica; at least 90% of the filler is silica; the silica is selected from precipitated silica, fumed silica, silica gel, and colloidal silica; the filler further includes carbon black; the filler further includes carbon black in an amount ranging from 1% to 10% by weight relative to the total weight of the filler; the method further includes charging a coupling agent to the mixer; the coupling agent is charged together with at least a portion of the wet filler.
[0036] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler comprises silica; wherein during one or more mixing steps (step (b)) and optionally during the filling step (step (a)), the at least one temperature control means is set to a temperature T in the range of 40°C-110°C, 40°C-100°C, 40°C-90°C, 40°C-75°C, or in the range of 50°C-110°C, 50°C-100°C, 50°C-90°C, or 50°C-75°C. z The wet filler has liquid present in an amount of at least 20% by weight, at least 30% by weight, in a range of 20%-75% by weight, 20%-65% by weight, 20%-60% by weight, in a range of 20%-50% by weight, or 40%-65% by weight.
[0037] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler comprises silica; the silica is dispersed in the elastomer at a loading in the range of 30 phr-180 phr, or in the range of 30 phr-150 phr, or in the range of 30 phr-100 phr, or in the range of 40 phr-75 phr; the silica has a range of 80 m 2 / g-250m 2 / g STSA; silica has a range of 80m 2 / g-200m 2 / g of STSA; the wet filler includes silica that has never been dried.
[0038] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomer, polychloroprene rubber, nitrile rubber (nitrile rubber), hydrogenated nitrile rubber (hydrogenated nitrile rubber, hydrogen ... rubber), polysulfide rubber, polyacrylate elastomer, fluorine-containing elastomer, perfluoroelastomer, silicone elastomer, and blends thereof; the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, nitrile rubber, hydrogenated nitrile rubber, and blends thereof; the elastomer comprises natural rubber, for example, at least 50 wt % or at least 70 wt % or at least 90 wt % of the solid elastomer is natural rubber; the elastomer is selected from one or more of natural rubber, styrene-butadiene rubber, and oil-extended styrene-butadiene rubber.
[0039] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: further including mixing the discharged composite with at least one additional elastomer; the at least one additional elastomer is the same as the solid elastomer; the at least one additional elastomer is different from the solid elastomer to form a composite comprising an elastomer blend; the solid elastomer is natural rubber and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber; the solid elastomer is a first solid elastomer and the loading further includes loading the mixer with at least one additional solid elastomer; the at least one additional elastomer is the same as the first solid elastomer; the at least one additional elastomer is different from the first solid elastomer; the solid elastomer is a blend comprising the first solid elastomer and at least one additional elastomer; the first solid elastomer is natural rubber and the at least one additional elastomer is selected from polybutadiene rubber and styrene-butadiene rubber.
[0040] With respect to any aspect or method or embodiment disclosed herein (including methods involving first and second mixers), the method may further include any one or more of the following embodiments, as appropriate: the mixture (discharged from the first mixer) has a liquid content reduced to an amount less than 50% by weight of the liquid content of the mixture at the start of the one or more mixing steps (step (b)), for example, a liquid content in the range of 1%-20% by weight, or in the range of 2%-15% by weight, or in the range of 5%-15% by weight, or in the range of 7%-15% by weight, or in the range of 2%-5% by weight; the mixture has a material temperature in the range of 100°C-170°C; the filling factor of the mixture in the first mixer is in the range of 50%-70%; the tip speed is at least 0.6 m / s, or at least 0.7 m / s, or at least 1 m / s.
[0041] With respect to any aspect or method or embodiment disclosed herein (including methods involving first and second mixers), the method may further include any one or more of the following embodiments, as appropriate: at least 50% by weight of the filler is carbon black; the wet filler has a liquid present in an amount of at least 20% by weight, or at least 30% by weight, or in the range of 40%-65% by weight; in one or more mixing steps (step (b)) of the first mixer and optionally during charging (step (a)), the at least one temperature control means is set to a temperature T in the range of 40°C-110°C, or in the range of 50°C-110°C, or in the range of 60°C-110°C, or 60°C or more, or 65°C or more, or in the range of 65°C-100°C, or in the range of 75°C-90°C. z ; The mixture (discharged from the first mixer) has a material temperature in the range of 120°C-150°C, or in the range of 130°C-140°C, for example, when the solid elastomer includes natural rubber; the elastomer is selected from natural rubber, styrene-butadiene rubber, butadiene rubber, and blends thereof, and the mixture has a material temperature in the range of 120°C-170°C.
[0042] With respect to any aspect or method or embodiment disclosed herein (including methods involving first and second mixers), the method may, where appropriate, further include any one or more of the following embodiments: (in (b)) the resulting total specific energy of the mixing in the first mixer is in the range of 1000-2500 kJ / kg.
[0043] With respect to any aspect or method or embodiment disclosed herein (including methods involving first and second mixers), the method may further include any one or more of the following embodiments, as appropriate: at least 50% by weight of the filler is silica; further comprising charging the first mixer with a coupling agent; the coupling agent is charged together with at least a portion of the wet filler; the at least one temperature control means is set to a temperature T in the range of 40°C-100°C, or 40°C-75°C, or in the range of 50°C-90°C, or in the range of 50°C-75°C during one or more mixing steps (step (b)) of the first mixer and optionally during charging (step (a)); z ; the wet filler has liquid present in an amount of at least 20% by weight, or in an amount in the range of 20%-65% by weight; (in (c)) the discharged mixture has a liquid content in the range of 1%-10% by weight, or in the range of 2%-15% by weight; the composite has an oil content of less than 5% or less than 1% by weight based on the total weight of the composite; the mixture has a material temperature in the range of 100°C-140°C, or 110°C-140°C, or 130°C-150°C, or 130°C-140°C.
[0044] With respect to any aspect or method or embodiment disclosed herein regarding the first and second mixers, the method may further include any one or more of the following embodiments, as appropriate: the second mixer is a tangential mixer; the filling factor of the mixture in the second mixer is in the range of 25%-60%; the filling factor of the mixture in the second mixer is in the range of 25%-50%.
[0045] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the composite has a Payne difference index of at least 105, or at least 110, and optionally at least 50% of the filler is silica.
[0046] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler comprises silicon-treated carbon black; at least 90% of the filler is silicon-treated carbon black; the silicon-treated carbon black is dispersed in the elastomer at a loading in the range of 30 phr-150 phr; the silicon-treated carbon black is dispersed in the elastomer at a loading in the range of 40 phr-100 phr; the silicon-treated carbon black is dispersed in the elastomer at a loading in the range of 40 phr-65 phr; the silicon-treated carbon black has a range of 60 phr; 2 / g-200m 2 / g STSA; silicon-treated carbon black has a range of 60m2 / g-150m 2 / g of STSA; the silicon-treated carbon black has a COAN in the range of 60 mL / 100 g-120 mL / 100 g; the silicon-treated carbon black has a COAN in the range of 70 mL / 100 g-115 mL / 100 g.
[0047] With respect to any aspect or method or embodiment disclosed herein, the method may further include any one or more of the following embodiments, as appropriate: the filler includes a blend of at least two fillers selected from carbon black, treated carbon black, silica, and silicon-treated carbon black.
[0048] With respect to any aspect or method or embodiment disclosed herein involving continuous mixing, the method may further include any one or more of the following embodiments, as appropriate: the mixing in (b) occurs by contacting the solid elastomer and the wet filler with one or more rotors positioned axially in an elongated chamber; the temperature of the one or more rotors is controlled; the mixer is a continuous mixer; conveying (b) is performed with at least one rotatable screw through which mixing also occurs; the mixer is a twin-screw extruder; the charging in (a) includes charging a substantially continuous flow of the pre-blend of at least the solid elastomer and the granulated wet filler; (a) The loading in (a) comprises separately loading a first substantially continuous flow of a solid elastomer and a second substantially continuous flow of a granulated wet filler; the loading in (a) further comprises loading a substantially continuous flow of an antidegradant; the granulated wet filler is a filler that has never been dried; the granulated wet filler comprises a dry filler that has been remoistened; the granulated wet filler comprises carbon black; the granulated wet filler comprises silica; the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomer, and blends thereof.
[0049] Another aspect is a composite comprising a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight relative to the total weight of the filler and the elastomer comprises at least 50% by weight of natural rubber relative to the total weight of the elastomer, and the composite has the following properties:
[0050] (a) The filler has a dispersion state in the elastomer that conforms to equation (1):
[0051] A≤1.25*B+x (1)
[0052] in:
[0053] A is the area equivalent diameter (μm) of the filler particles in the composite. 90 ,and
[0054] B is [Total area of particles with area equivalent diameter ≥ 2 μm] x100%
[0055] [Total imaging area]
[0056] Where B ≥ 1%,
[0057] A and B were determined by optical microscopy in transmission mode of sections, and
[0058] x is a number in the range of 15-20; and
[0059] (b) The complex has properties that conform to equation (2):
[0060] G'(0.1%) / G'(200%)≤0.1*G'(50%)-y (2)
[0061] Wherein G'(0.1%) is the dynamic storage modulus measured at a strain amplitude of 0.1%, G'(200%) is the dynamic storage modulus measured at a strain amplitude of 200%, G'(50%) is the dynamic storage modulus measured at a strain amplitude of 50%, the dynamic storage modulus is measured at a frequency of 1 Hz at 100°C, and y is a number ranging from 7 to 10.
[0062] With respect to the composite, any one or more of the following embodiments may be applicable: the filler comprises carbon black in an amount of at least 90% by weight relative to the total weight of the filler; the elastomer further comprises at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber; x=15; y=10; the carbon black has at least 60 m 2 / g STSA; carbon black has a range of 60m 2 / g-210m 2 / g STSA; the carbon black has a COAN of at least 75mL / 100g; the carbon black has a BET / STSA ratio in the range of 1-1.2; the composite has a carbon black loading of 60phr or less, for example, a loading in the range of 30phr-60phr or 40phr-60phr; the filler further includes silica; the composite consists of a filler dispersed in an elastomer at a loading of at least 20phr, or essentially consists of a filler dispersed in an elastomer at a loading of at least 20phr; the composite consists of a filler dispersed in an elastomer at a loading of at least 20phr, and an antidegradant, or essentially consists of a filler dispersed in an elastomer at a loading of at least 20phr, and an antidegradant.
[0063] Another aspect is a method of making a vulcanizate comprising mixing any of the compounds disclosed herein with at least one curing agent and / or curing any of the compounds disclosed herein in the presence of at least one curing agent.
[0064] Another aspect is a vulcanizate prepared from any of the compounds disclosed herein.
[0065] Another aspect is a vulcanizate comprising a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight relative to the total weight of the filler and the elastomer comprises at least 50% by weight of natural rubber relative to the total weight of the elastomer, and wherein:
[0066] Carbon black has at least 60m 2 / g STSA and a BET / STSA ratio in the range of 1-1.2; and
[0067] The sulfide product has resistivity and dispersion properties that satisfy equation (3)
[0068] [1n(R)-3.8] / [0.28*δ]≥0.0004*v+0.9 (3)
[0069] in:
[0070] R is the resistivity, measured in ohm·cm;
[0071] δ=(6000·[0.806·φ -1 / 3 β -1 / 3 -1] / ρS)xβ 1.43
[0072] in:
[0073] φ = volume fraction of carbon black in the composite,
[0074] S = BET surface area of carbon black, in m 2 / g,
[0075] p = carbon black density, assumed to be 1.8 g / cm 3 ,
[0076] β=φ eff / φ,
[0077] φ eff The effective volume fraction of carbon black taking into account the entrapped rubber is calculated as follows: eff =φ[1+(0.0181*COAN)] / 1.59, where COAN is the compression oil absorption value of carbon black as determined by ASTM D3493; and
[0078] v ≥ 65, where v is the number of particles / mm having an area equivalent diameter of at least 4 μm as determined by optical microscopy in transmission mode of a section 2 .
[0079] With respect to the vulcanized product, any one or more of the following embodiments may be applicable: the filler comprises carbon black in an amount of at least 90% by weight relative to the total weight of the filler; the elastomer further comprises at least one rubber selected from polybutadiene rubber and styrene-butadiene rubber; the carbon black has a range of 60 m 2 / g-210m 2 / g STSA; carbon black has a range of 60m 2 / g-190m 2 / g STSA; the carbon black has a COAN of at least 75 mL / 100 g; the vulcanizate has a carbon black loading of 60 phr or less; the filler further includes silica; the vulcanizate has a tensile stress ratio M300 / M100 of at least 5.9, at least 6.0, at least 6.1, or at least 6.2, wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively; the vulcanizate has a maximum tan δ (60 ° C) of not more than 0.22 (e.g., not more than 0.21, not more than 0.2, not more than 0.19, or not more than 0.18); the vulcanizate has a resistivity index of at least 105; the tan The tan δ value is less than the tan δ value of a vulcanizate prepared from a dry-mix compound having the same composition ("dry-mix counterpart"); the tensile stress ratio M300 / M100 of the vulcanizate is greater than the tensile stress ratio of the vulcanizate prepared from a dry-mix compound having the same composition, wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0080] Regarding a vulcanized product prepared from a composite, wherein the method for preparing a composite includes a first and a second mixer, the vulcanized product may have a tan δ value smaller than the tan δ value of the vulcanized product prepared from the mixture discharged in step (c); and the tensile stress ratio M300 / M100 of the vulcanized product is greater than the tensile stress ratio of the vulcanized product prepared from the mixture discharged in step (b), wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0081] Another aspect is an article comprising any vulcanized product disclosed herein; the article can be selected from tire treads, undertreads, inner liners, sidewalls, sidewall inserts, wire skins, and cushion gums for retreaded tires; the article can be selected from hoses, linings, liners, seals, gaskets, anti-vibration articles, tracks, track pads for track-propelled vehicle equipment, engine mounts, seismic stabilizers, mining equipment screens, mining equipment linings, conveyor belts, chute linings, slurry pump linings, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, impellers for mixing slurries and slurry pump impellers, grinder linings, cyclone separators and hydrocyclones, expansion joints, outboard motor pumps for water equipment and sludge suction pump linings, water shaft seals, and drive shafts.
[0082] On the other hand is a method for preparing a composite in an integrated manufacturing operation, comprising: (a) manufacturing a filler in a filler manufacturing facility by a process in which the final product as a wet filler includes a filler and a liquid present in an amount of at least at least 20 weight percent based on the total weight of the wet filler; (b) conveying the wet filler to at least one mixer; (c) charging at least a solid elastomer and the wet filler to the at least one mixer, wherein the at least one mixer has at least one temperature control means; (d) in one or more mixing steps, mixing the at least solid elastomer and the wet filler to form a mixture, and in at least one of the mixing steps, conducting the mixing at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation; and (e) discharging a composite from the at least one mixer, the composite comprising filler dispersed in the elastomer at a loading of at least 20 phr, wherein the filler yield loss is no more than 10%, and wherein the composite has a liquid content of no more than 10 weight percent based on the total weight of the composite.
[0083] With respect to the integrated manufacturing operation, the method may further include any one or more of the following embodiments, as appropriate: the wet filler is a filler that has never been dried; the filler manufacturing facility is a carbon black manufacturing facility, and the wet filler is a carbon black that has never been dried; the filler manufacturing facility is a precipitated silica manufacturing facility, and the wet filler is a precipitated silica that has never been dried; the filler manufacturing facility is a silicon-treated carbon black manufacturing facility; further comprising preparing a vulcanizate including an elastomeric compound, and optionally forming an article including the vulcanizate or the elastomeric compound;
[0084] With regard to the integrated manufacturing operation, where appropriate, the method may further include any one or more of the following parameters during the method: during the mixing, the at least one temperature control means is set to a temperature Tz of 65°C or higher; and / or during the mixing, the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or the mixer is charged with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, wherein the filling factor of the at least solid elastomer and the wet filler on a dry weight basis is not greater than 68%; and / or the mixing is carried out at a mixer temperature controlled by at least one temperature control means and an average specific power of at least 2.5 kW / kg is applied during the mixing time; and / or the mixing is a continuous mixing step and the loading comprises loading a continuous flow of at least a solid elastomer and a wet filler into a continuous mixer; and / or The second mixer obtains the composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its highest level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ram-free; and (vi) the filling factor of the mixture ranges from 25% to 70%; and / or the one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time, resulting in a total specific energy of at least 1500 kJ / kg of composite, and wherein the wet filler is a wet granular filler; and / or optionally at least one additive selected from an antidegradant and a coupling agent is added during said filling (a) or said mixing (b), and optionally one or more rubber chemicals are added after the mixer reaches a temperature of 120° C. or higher.
[0085] Those skilled in the art can easily appreciate that any aspects or embodiments disclosed herein can be combined where appropriate, for example, any two, three, four, etc. can be combined.
[0086] The present invention includes the following embodiments:
[0087] 1. A method for preparing a composite, comprising:
[0088] (a) charging a mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount ranging from 15% to 65% by weight based on the total weight of the wet filler;
[0089] (b) mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and said mixing is carried out in at least one of said mixing steps, wherein the mixer has at least one temperature control means set to a temperature Tz of 65°C or higher, and at least a portion of the liquid is removed from the mixture by evaporation; and
[0090] (c) discharging a composite from the mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 5%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0091] 2. The method of item 1, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
[0092] 3. The method of item 1, wherein the filler comprises at least one material selected from the group consisting of carbon black and silicon-treated carbon black.
[0093] 4. The method of any one of items 1 to 3, wherein the filler further comprises silicon dioxide.
[0094] 5. The method of any one of items 1 to 4, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T of 70° C. or higher. z .
[0095] 6. The process of any one of items 1 to 5, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 65°C to 100°C. z .
[0096] 7. The process of any one of items 1 to 6, wherein the resulting total specific energy for compounding is at least 1,400 kJ / kg of compound.
[0097] 8. The method of any one of items 1 to 7, wherein the time-averaged release rate of the liquid per kg of the composite calculated on a dry weight basis is in the range of 0.01 to 0.14 kg / (min·kg).
[0098] 9. The method of any one of items 1 to 8, wherein the mixing of step (b) comprises applying energy ER to at least one rotor of the mixer at an energy efficiency in the range of 20% to 80% in accordance with the following equation:
[0099] Energy efficiency = heat load / E R x 100%,
[0100] The heat load is the energy required to remove liquid from 1 kg of the composite at 100% efficiency.
[0101] 10. The process of any one of items 1 to 9, wherein one or more rubber chemicals are not present in the composite discharged in step (c).
[0102] 11. The process of any one of clauses 1 to 10, wherein the wet filler has the liquid present in an amount ranging from 30% to 65% by weight.
[0103] 12. The process of any one of items 1 to 11, wherein the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomer, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomer, fluoroelastomer, perfluoroelastomer, silicone elastomer, and blends thereof.
[0104] 13. A method for preparing a composite, comprising:
[0105] (a) charging a mixer with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler, wherein the packing factor of the at least solid elastomer and the wet filler on a dry weight basis is not greater than 68%;
[0106] (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means, and removing at least a portion of the liquid from the mixture by evaporation; and
[0107] (c) discharging a composite from a mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0108] 14. The process of item 13, wherein the filling factor is not more than 66% by dry weight.
[0109] 15. The method of item 13 or 14, wherein the mixer is a batch mixer comprising a plunger capable of vertically moving downward to a lowermost position, wherein during mixing, the mixer is operated with a maximum plunger displacement from the lowermost position of no more than 30% of the diameter of the one or more rotors.
[0110] 16. The method according to any one of items 13 to 15, wherein the time-averaged release rate of the liquid per kg of the composite calculated on a dry weight basis is in the range of 0.01 to 0.14 kg / (min·kg).
[0111] 17. The method of any one of items 13 to 16, wherein the mixing of step (b) comprises applying energy ER to at least one rotor of the mixer at an energy efficiency in the range of 20% to 80% in accordance with the following equation:
[0112] Energy efficiency = heat load / E R x 100%,
[0113] The heat load is the energy required to remove liquid from 1 kg of the composite at 100% efficiency.
[0114] 18. The process of any of items 13-17, wherein the one or more mixing steps are performed with one or more rotors operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time.
[0115] 19. The process of any of items 13 to 18, wherein at least 70% by weight of the solid elastomer is natural rubber.
[0116] 20. The process of any one of items 13 to 18, wherein at least 90% by weight of the solid elastomer is natural rubber.
[0117] 21. The method of any one of items 13 to 20, wherein the solid elastomer further comprises at least one additional elastomer other than natural rubber to form a composite comprising an elastomer blend.
[0118] 22. The process of item 21, wherein the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber.
[0119] 23. The method of item 21 or 22, wherein the charging comprises charging the at least one additional solid elastomer to a mixer separately from the natural rubber.
[0120] 24. The process of any one of items 13 to 23, wherein the charging comprises charging the solid elastomer to a mixer as a blend of natural rubber and the at least one additional solid elastomer.
[0121] 25. The method of any one of items 13 to 24, wherein the mixing of step (b) comprises applying an average specific power of at least 2.5 kW / kg during the ram down time.
[0122] 26. The process according to any one of items 13 to 25, wherein one or more rubber chemicals are not present in the composite discharged in step (c).
[0123] 27. The method of any one of items 13 to 26, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
[0124] 28. The method of any one of items 13 to 26, wherein the filler comprises at least one material selected from the group consisting of carbon black, silicon-treated carbon black, and silica.
[0125] 29. The process of any one of items 13 to 28, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C to 110°C z .
[0126] 30. A method for preparing a composite, comprising:
[0127] (a) charging a mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0128] (b) mixing the at least solid elastomer and the wet filler in a mixer in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation;
[0129] (c) discharging a composite from a mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0130] 31. The method of item 30, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
[0131] 32. The process of item 30, wherein at least 50% by weight of the filler is selected from carbon black and silicon-treated carbon black.
[0132] 33. The process of item 30, wherein at least 50% by weight of the filler is carbon black.
[0133] 34. The process of any one of items 30 to 33, wherein the resulting total specific energy for compounding is at least 1,400 kJ / kg of compound.
[0134] 35. The process of any one of items 30 to 34, wherein after substantially all of the wet filler has been loaded into the mixer, the resulting specific energy E for mixing 100%填料 is at least 1,100 kJ / kg of the complex.
[0135] 36. The process of any one of items 30 to 35, wherein after at least 75% by weight of the total wet filler has been loaded into the mixer, the resulting specific energy E for mixing 75%填料 is at least 1,300 kJ / kg of the complex.
[0136] 37. The method of any one of items 30 to 36, wherein the mixing of step (b) comprises applying energy E to at least one rotor of the mixer at an energy efficiency in the range of 20% to 80% in accordance with the following equation: R :
[0137] Energy efficiency = heat load / E R x 100%,
[0138] The heat load is the energy required to remove liquid from 1 kg of the composite at 100% efficiency.
[0139] 38. The method according to any one of items 30 to 37, wherein the time-averaged release rate of the liquid per kg of the composite calculated on a dry weight basis is in the range of 0.01 to 0.14 kg / (min·kg).
[0140] 39. The method of any one of items 30 to 38, wherein the mixing of step (b) comprises applying an average specific power of at least 2.5 kW / kg during the ram down time.
[0141] 40. The process of any one of items 30 to 39, wherein the wet filler has the liquid present in an amount of at least 30% by weight.
[0142] 41. The process of any one of items 30 to 39, wherein the wet filler has the liquid present in an amount ranging from 40% to 65% by weight.
[0143] 42. The method of any one of items 30 to 39, wherein the wet filler has liquid present in an amount determined as a function of the OAN of the filler that conforms to the following equation:
[0144] k*OAN / (100+OAN)*100
[0145] The k range is 0.6-1.1.
[0146] 43. The method of any one of items 30 to 42, wherein the tip velocity is in the range of 0.6 m / s to 10 m / s.
[0147] 44. The process according to any one of items 30 to 43, wherein the discharged composite has a liquid content of not more than 5% by weight.
[0148] 45. The method of any one of items 30 to 44, wherein the mixing further comprises removing liquid from the mixture by pressing, compacting, wringing, or any combination thereof.
[0149] 46. The method of any one of items 30 to 45, wherein the liquid comprises water.
[0150] 47. The process of any one of items 30 to 46, wherein the wet filler is in the form of a powder, paste, pellets, or cake.
[0151] 48. The process of any one of items 30 to 47, wherein the mixture further comprises a non-wet filler.
[0152] 49. The process according to any one of items 30 to 48, wherein the temperature of the mixer during discharge in step (c) is in the range of 120°C to 180°C.
[0153] 50. The process of any one of items 30 to 49, wherein the composite has a filler yield loss of no more than 5%.
[0154] 51. The method of any one of items 30-51, wherein the filling factor of the mixture is in the range of 50% to 70%.
[0155] 52. The process of any one of items 30 to 51, wherein the solid elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
[0156] 53. The method of any one of items 30 to 52, further comprising compounding the discharged composite with at least one additional elastomer.
[0157] 54. The method of any one of items 30 to 52, wherein the solid elastomer is a first solid elastomer and the loading further comprises loading the mixer with at least one additional solid elastomer.
[0158] 55. The method of item 53 or 54, wherein the at least one additional elastomer is different from the solid elastomer to form a composite comprising an elastomer blend.
[0159] 56. The process of any of items 53 to 55, wherein the solid elastomer is natural rubber and the at least one additional elastomer is selected from polybutadiene and styrene-butadiene rubber.
[0160] 57. The process according to any one of items 30 to 56, wherein one or more rubber chemicals are absent from the composite discharged in step (c).
[0161] 58. The process of any one of items 30 to 57, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C to 110°C z .
[0162] 59. The process of any one of items 30 to 57, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T of 65° C. or higher. z .
[0163] 60. The process of any one of items 30 to 59, wherein said mixing is performed in one mixing step.
[0164] 61. The process of any one of items 30 to 59, wherein the mixing is performed in two or more mixing steps.
[0165] 62. The method of item 61, wherein said mixer is a first mixer and said method further comprises, after said mixing and before said discharging, further mixing said mixture in said first mixer or in a second mixer or in both, to obtain a composite.
[0166] 63. The method of item 62, wherein said further mixing reduces the liquid content of said mixture compared to the liquid content of said mixture after said mixing.
[0167] 64. The method of any one of items 30 to 63, wherein the one or more mixing steps are a continuous process.
[0168] 65. The process of any one of items 30 to 63, wherein the one or more mixing steps are a batch process.
[0169] 66. The method of item 65, wherein the one or more mixing steps are performed in one step and the plunger lowering time ranges from 3 minutes to 30 minutes.
[0170] 67. The process of any one of items 30 to 66, wherein the mixer has a chamber capacity of at least 10 L.
[0171] 68. The method of any one of items 30 to 67, wherein the mixing is performed with at least one rotor selected from a two-rib rotor, a four-rib rotor, a six-rib rotor, an eight-rib rotor, and one or more screw rotors.
[0172] 69. The method of any one of items 30 to 68, wherein the composite has an oil content of less than 5% by weight, based on the total weight of the composite.
[0173] 70. The process of any one of items 30 to 69, wherein the wet filler comprises carbon black which has never been dried.
[0174] 71. The process of any one of items 30 to 69, wherein the wet filler comprises dry carbon black which has been remoistened.
[0175] 72. The process of any one of items 30 to 71, wherein the wet filler comprises dry carbon black that is rewetted in a granulator, fluidized bed, ejector, mixer, or drum.
[0176] 73. The method of item 72, wherein the dry carbon black pellets are subjected to at least one process selected from grinding, pelletizing, milling, and classification before being re-moistened.
[0177] 74. The process of any one of items 30 and 34-69, wherein the filler comprises silica.
[0178] 75. The method of item 74, wherein the filler further comprises carbon black.
[0179] 76. The method of any one of items 74 or 75, further comprising charging the mixer with a coupling agent.
[0180] 77. The process of item 76, wherein the charging in (a) further comprises charging the mixer with a coupling agent and at least a portion of the wet filler.
[0181] 78. The process of any one of items 74 to 77, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C to 110°C z .
[0182] 79. The process of any one of items 74 to 78, wherein the wet filler has the liquid present in an amount ranging from 20% to 60% by weight.
[0183] 80. The process according to any one of items 74 to 79, wherein the resulting total specific energy for compounding is at least 1,100 kJ / kg of composite.
[0184] 81. The process of any one of items 74 to 80, wherein the wet filler comprises silica which has never been dried.
[0185] 82. The method of any one of items 74 to 81, wherein the composite has a Payne Difference Index of at least 105.
[0186] 83. The method of any one of items 30 and 59-69, wherein the filler comprises silicon-treated carbon black.
[0187] 84. The method of any one of items 30 to 83, wherein the filler comprises a blend of at least two fillers selected from carbon black, treated carbon black, silica, and silicon-treated carbon black.
[0188] 85. A method for preparing a composite, comprising:
[0189] (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0190] (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation;
[0191] (c) discharging a mixture from the first mixer, the mixture comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the mixture has a liquid content reduced to an amount less than the liquid content at the beginning of step (b), and wherein the mixture has a material temperature in the range of 100° C. to 180° C.;
[0192] (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions:
[0193] (i) A bolt pressure of 5 psi or less;
[0194] (ii) the jack is raised to at least 75% of its maximum level;
[0195] (iii) the jack is operated in floating mode;
[0196] (iv) the top pin is positioned so that it does not substantially contact the mixture;
[0197] (v) the mixer is jackless; and
[0198] (vi) the fill factor of the mixture is in the range of 25% to 70%; and
[0199] (e) discharging a composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
[0200] 86. The method of item 85, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
[0201] 87. The method of item 85, wherein the filler comprises at least one material selected from the group consisting of carbon black and silicon-treated carbon black.
[0202] 88. The method of item 85, wherein the filler comprises carbon black.
[0203] 89. The process of any of items 85 to 88, wherein the wet filler has the liquid present in an amount of at least 20% by weight.
[0204] 90. The process of any one of items 85 to 88, wherein the wet filler has the liquid present in an amount ranging from 40% to 65% by weight.
[0205] 91. The process of any one of items 85 to 90, wherein the mixture has a liquid content which is reduced to an amount less than 50% by weight of the liquid content of the mixture at the start of step (b).
[0206] 92. The process of any one of items 85 to 90, wherein the mixture in (c) has a liquid content in the range of 1% to 20% by weight.
[0207] 93. The process of any one of items 85 to 90, wherein the mixture in (c) has a liquid content in the range of 2% to 15% by weight.
[0208] 94. The process of any one of items 85 to 93, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 60°C to 110°C z .
[0209] 95. The process of any one of items 85 to 94, wherein the time between the start of mixing and the discharging in (c) ranges from 3 minutes to 15 minutes.
[0210] 96. The process of any one of items 85 to 94, wherein the plunger down time for mixing in the first mixer is in the range of 3 minutes to 15 minutes.
[0211] 97. The process of any one of items 85 to 96, wherein the filling factor of the mixture in the first mixer is in the range of 50% to 70%.
[0212] 98. The process of any one of items 85 to 97, wherein the filling factor of the mixture in the second mixer is in the range of 25% to 60%.
[0213] 99. The process of any one of items 85 to 98, wherein the solid elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
[0214] 100. The method of any of items 85 to 99, wherein the solid elastomer comprises natural rubber.
[0215] 101. The process of any one of items 85 to 100, wherein the mixture has a material temperature in the range of 120°C to 150°C.
[0216] 102. The process of any one of items 85 to 100, wherein the mixture has a material temperature in the range of 130°C to 140°C.
[0217] 103. The process of any one of items 85 to 102, wherein the elastomer is selected from the group consisting of natural rubber, styrene-butadiene rubber, butadiene rubber, and blends thereof.
[0218] 104. The process of any of item 103, wherein the mixture has a material temperature in the range of 120°C to 170°C.
[0219] 105. The process of any one of items 85 to 138, wherein the resulting total specific energy of the mixing in (b) is in the range of 1000 to 2500 kJ / kg.
[0220] 106. The method of any one of items 85 and 89-105, wherein the filler comprises silica.
[0221] 107. The process of item 106, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C to 110°C z .
[0222] 108. The process of item 106 or 107, wherein the wet filler has the liquid present in an amount ranging from 20% to 65% by weight.
[0223] 109. The method of any one of items 106 to 108, wherein the filler comprises silica and the elastomer comprises natural rubber.
[0224] 110. The process of item 109, wherein the mixture has a material temperature in the range of 100°C to 150°C.
[0225] 111. A method for preparing a composite, comprising:
[0226] (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0227] (b) mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means and an average specific power of at least 2.5 kW / kg is applied during the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation;
[0228] (c) discharging a mixture from the first mixer, the mixture comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the mixture has a liquid content reduced to an amount less than the liquid content at the beginning of step (b), and wherein the mixture has a material temperature in the range of 100° C. to 180° C.;
[0229] (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions:
[0230] (i) A bolt pressure of 5 psi or less;
[0231] (ii) the jack is raised to at least 75% of its maximum level;
[0232] (iii) the jack is operated in floating mode;
[0233] (iv) the top pin is positioned so that it does not substantially contact the mixture;
[0234] (v) the mixer is jackless; and
[0235] (vi) the fill factor of the mixture is in the range of 25% to 70%; and
[0236] (e) discharging a composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
[0237] 112. The process of item 111, wherein the average specific power over the mixing time is at least 3 kW / kg.
[0238] 113. The process of item 111, wherein the average specific power over the mixing time is at least 4.5 kW / kg.
[0239] 114. The method of item 111, wherein the average specific power over the mixing time is in the range of 2.5-10 kW / kg.
[0240] 115. The process of any one of items 111 to 114, wherein the mixing time is no more than 15 minutes.
[0241] 116. The method of any one of items 111 to 115, wherein the mixing time is the time the ejector pin is lowered.
[0242] 117. The process according to any one of items 111 to 115, wherein the mixing time is the total mixing time from the filling in (a) to the discharging in (c).
[0243] 118. The process of any of items 111 to 117, wherein the wet filler has the liquid present in an amount of at least 30% by weight.
[0244] 119. The process of any of items 111 to 117, wherein the wet filler has the liquid present in an amount ranging from 40% to 65% by weight.
[0245] 120. The process of any one of items 111 to 119, wherein the solid elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
[0246] 121. The method of any one of items 111 to 120, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
[0247] 122. A method for preparing a composite, comprising:
[0248] (a) charging a continuous stream of at least a solid elastomer and a granulated wet filler into an input end of a continuous mixer, wherein the wet filler comprises a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0249] (b) conveying the solid elastomer and the wet filler along the length of a continuous mixer, wherein during the conveying, mixing occurs and at least a portion of the liquid is removed by evaporation; and
[0250] (c) discharging a composite from a discharge end of the continuous mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0251] 123. The process of item 122, wherein the continuous mixer has an elongated chamber.
[0252] 124. The process of item 123, wherein the mixing in (b) occurs by contacting the solid elastomer and the wet filler with one or more rotors positioned axially in an elongated chamber.
[0253] 125. The method of item 124, wherein the temperature of the one or more rotors is controlled.
[0254] 126. The process of item 122, wherein the conveying of (b) is performed with at least one rotatable screw, by which the mixing also occurs.
[0255] 127. The method of item 126, wherein the mixer is a twin-screw extruder.
[0256] 128. The process of any one of items 122 to 127, wherein the loading in (a) comprises loading a substantially continuous flow of a pre-blend of at least the solid elastomer and the granulated wet filler.
[0257] 129. The process according to any one of items 122 to 127, wherein the loading in (a) comprises separately loading a first substantially continuous flow of solid elastomer and a second substantially continuous flow of granulated wet filler.
[0258] 130. The process of any one of items 122 to 129, wherein the pelletized wet filler is selected from carbon black, silicon-treated carbon black, and silica.
[0259] 131. The process of any one of items 122 to 129, wherein the solid elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, and blends thereof.
[0260] 132. A method for preparing a composite, comprising:
[0261] (a) charging a mixer with a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0262] (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, carrying out said mixing and removing at least a portion of the liquid from the mixture by evaporation at a mixer temperature controlled by at least one temperature control means, wherein during said mixing, the mixer reaches an indicated temperature of 120° C. or higher;
[0263] (c) optionally adding at least one additive selected from antidegradants and coupling agents during said filling (a) or said mixing (b), and optionally adding one or more rubber chemicals after the mixer reaches the indicated temperature; and
[0264] (d) discharging a composite from a mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is not greater than 10%, wherein the composite has a liquid content of not greater than 10 weight percent based on the total weight of the composite, and said charging (a) and said mixing (b) before the mixer reaches the indicated temperature are conducted in the substantial absence of the one or more rubber chemicals.
[0265] 133. A method for preparing a sulfurized product, comprising:
[0266] The composite prepared by the method of any one of items 1 to 132 is cured in the presence of at least one curing agent to form a vulcanized product.
[0267] 134. The process of item 133, wherein the tan δ value of the vulcanizate is less than the tan δ value of a vulcanizate prepared from a dry blend compound having the same composition.
[0268] 135. The process of item 133 or 134, wherein the tensile stress ratio M300 / M100 of the vulcanizate is greater than the tensile stress ratio of the vulcanizate prepared from a dry blend compound having the same composition, wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0269] 136. The vulcanizate according to any one of items 133 to 135, wherein the vulcanizate has a tensile stress ratio M300 / M100 of at least 5.9, wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0270] 137. The vulcanizate according to any one of items 133 to 136, wherein the vulcanizate has a maximum tan δ (60° C.) of not more than 0.22.
[0271] 138. The vulcanizate of any one of items 133 to 137, wherein at least 50% by weight of the filler in the vulcanizate is carbon black and the vulcanizate has a resistivity index of at least 105.
[0272] 139. A method for preparing a sulfurized product, comprising:
[0273] The composite prepared by the method of any one of items 85 to 121 is cured in the presence of at least one curing agent to form a vulcanizate.
[0274] 140. The process of item 139, wherein the tan δ value of the sulphurized product is less than the tan δ value of the sulphurized product prepared from the mixture discharged in step (b).
[0275] 141. The process of item 139 or 140, wherein the tensile stress ratio M300 / M100 of the vulcanizate is greater than the tensile stress ratio of the vulcanizate prepared from the mixture discharged in step (b), wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0276] 142. A composite comprising a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight relative to the total weight of the filler, and the elastomer comprises at least 50% by weight of natural rubber relative to the total weight of the elastomer, and the composite has the following properties:
[0277] (a) The filler has a dispersion state in the elastomer that conforms to equation (1):
[0278] A≤1.25*B+x (1)
[0279] in:
[0280] A is the area equivalent diameter (μm) of the filler particles in the composite. 90 ,and
[0281] B is [Total area of particles with area equivalent diameter ≥ 2 μm] x100%
[0282] [Total imaging area]
[0283] Where B ≥ 1%,
[0284] A and B were determined by optical microscopy in transmission mode of sections, and
[0285] x is a number in the range of 15-20; and
[0286] (b) The complex has properties that conform to equation (2):
[0287] G'(0.1%) / G'(200%)≤0.1*G'(50%)-y (2)
[0288] Wherein G'(0.1%) is the dynamic storage modulus measured at a strain amplitude of 0.1%, G'(200%) is the dynamic storage modulus measured at a strain amplitude of 200%, G'(50%) is the dynamic storage modulus measured at a strain amplitude of 50%, the dynamic storage modulus is measured at a frequency of 1 Hz at 100°C, and y is a number ranging from 7 to 10.
[0289] 143. The composite of item 142, wherein the elastomer further comprises at least one rubber selected from the group consisting of polybutadiene rubber and styrene-butadiene rubber.
[0290] 144. The compound of item 142 or 143, wherein x=15.
[0291] 145. The complex according to any one of items 142 to 144, wherein y=10.
[0292] 146. The composite of any one of items 142 to 145, wherein the carbon black has a 2 / g of STSA.
[0293] 147. The composite of any one of items 142-146, wherein the carbon black has a COAN of at least 75 mL / 100 g.
[0294] 148. The composite of any one of items 142-147, wherein the carbon black has a BET / STSA ratio in the range of 1-1.2.
[0295] 149. The composite of any one of items 142-148, wherein the composite has a carbon black loading of 60 phr or less.
[0296] 150. The composite according to any one of items 142 to 149, wherein the filler further comprises silica.
[0297] 151. A method for producing a vulcanizate, comprising curing the compound according to any one of items 142 to 150 in the presence of at least one curing agent.
[0298] 152. Vulcanizate prepared from the compound according to any one of items 142 to 150.
[0299] 153. A vulcanizate comprising a filler dispersed in an elastomer, wherein the filler comprises carbon black in an amount of at least 50% by weight relative to the total weight of the filler and the elastomer comprises at least 50% by weight of natural rubber relative to the total weight of the elastomer, and wherein:
[0300] Carbon black has at least 60m2 / g STSA and a BET / STSA ratio in the range of 1-1.2; and
[0301] The sulfide product has resistivity and dispersion properties that satisfy equation (3)
[0302] [ln(R)-3.8] / [0.28*δ]≥0.0004*v+0.9 (3)
[0303] in:
[0304] R is the resistivity, measured in ohm·cm;
[0305] δ=(6000·[0.806·φ -1 / 3 β -1 / 3 -1] / pS)xβ 1.43
[0306] in:
[0307] φ = volume fraction of carbon black in the composite,
[0308] S = BET surface area of carbon black, in m 2 / g,
[0309] ρ = carbon black density, assumed to be 1.8 g / cm 3 ,
[0310] β=φ eff / φ,
[0311] φ eff The effective volume fraction of carbon black taking into account the entrapped rubber is calculated as follows: eff =φ[1+(0.0181*COAN)] / 1.59, where COAN is the compression oil absorption value of carbon black as determined by ASTM D3493; and
[0312] v ≥ 65, where v is the number of particles / mm having an area equivalent diameter of at least 4 μm as determined by optical microscopy in the transmission mode of a section 2 .
[0313] 154. The vulcanizate of item 153, wherein the elastomer further comprises at least one rubber selected from the group consisting of polybutadiene rubber and styrene-butadiene rubber.
[0314] 155. The vulcanized product of item 153 or 154, wherein the carbon black has a COAN of at least 75 mL / 100 g.
[0315] 156. The vulcanizate of any one of items 153 to 155, wherein the filler further comprises silica.
[0316] 157. The vulcanizate according to any one of items 153 to 156, wherein the vulcanizate has a tensile stress ratio M300 / M100 of at least 5.9, wherein M100 and M300 refer to the tensile stress at 100% and 300% elongation, respectively.
[0317] 158. The vulcanizate according to any one of items 153 to 157, wherein the vulcanizate has a maximum tan δ (60° C.) of not more than 0.22.
[0318] 159. Tyre tread comprising the vulcanizate of any of items 153 to 158.
[0319] 160. An article comprising the vulcanized product of any of items 153 to 158.
[0320] 161. The article of item 160, wherein the article is incorporated into a pneumatic, non-pneumatic or solid tire.
[0321] 162. The article of item 160, wherein the article is selected from the group consisting of tire treads, undertreads, inner liners, sidewalls, sidewall inserts, wire skins, and cushioning rubbers for retreaded tires.
[0322] 163. The article of item 160, wherein the article is selected from hoses, linings, liners, seals, gaskets, shock absorbing articles, tracks, track pads for track-propelled vehicle equipment, engine mounts, seismic stabilizers, mining equipment screens, mining equipment linings, conveyor belts, chute linings, slurry pump linings, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, impellers for mixing slurries and slurry pump impellers, grinding machine linings, cyclone separators and hydrocyclones, expansion joints, linings for outboard motor pumps and suction dredgers for marine equipment, marine shaft seals, and drive shafts.
[0323] 164. A method of preparing a composite in an integrated manufacturing operation, comprising:
[0324] (a) manufacturing a filler in a filler manufacturing facility by a process wherein the final product as a wet filler comprises filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0325] (b) conveying the wet filler to at least one mixer;
[0326] (c) charging at least the solid elastomer and the wet filler into the at least one mixer, wherein the at least one mixer has at least one temperature control means;
[0327] (d) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps carrying out said mixing at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation; and
[0328] (e) discharging from the at least one mixer a composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein a filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0329] 165. The method of item 164, wherein one or more of the following parameters are utilized during said method:
[0330] - During said mixing the at least one temperature control means is set to a temperature T of 65°C or higher z ; and / or
[0331] - during said mixing, the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or
[0332] - charging a mixer with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, wherein the packing factor of the at least solid elastomer and the wet filler is not greater than 68% by dry weight; and / or
[0333] - said mixing is carried out at a mixer temperature controlled by at least one temperature control means and applying an average specific power of at least 2.5 kW / kg during the mixing time; and / or
[0334] - the mixing is a continuous mixing step and the charging comprises charging a continuous flow of at least a solid elastomer and a wet filler into a continuous mixer; and / or
[0335] - a second mixer to obtain the composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its maximum level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ramless; and (vi) the fill factor of the mixture ranges from 25% to 70%; and / or
[0336] - one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time, resulting in a total specific energy of at least 1500 kJ / kg of compound, and wherein the wet filler is a wet particulate filler; and / or
[0337] - optionally adding at least one additive selected from antidegradants and coupling agents during said filling (a) or said mixing (b), and optionally adding one or more rubber chemicals after the mixer reaches a temperature of 120° C. or higher.
[0338] 166. The process of any one of items 1 and 5 to 12, wherein at least 50% of the filler is silica.
[0339] 167. The method of item 166, further comprising charging the mixer with a coupling agent.
[0340] 168. The method of any one of items 1, 5 to 12, 166 and 167, wherein the filling comprises introducing a dry filler into a mixer, wherein the dry filler is moistened in the mixer by adding a liquid to form a wet filler.
[0341] 169. The method of any one of items 30-69, 74-80 and 82-84, the filling comprising introducing a dry filler into a mixer, wherein the dry filler is moistened in the mixer by adding a liquid to form a wet filler. DETAILED DESCRIPTION
[0342] Disclosed herein, in part, are methods of preparing or forming a composite by mixing a solid elastomer with a wet filler. Also disclosed herein, in part, are the composite, vulcanizates formed therefrom, and articles.
[0343] When mixing fillers and elastomers, the challenge is to ensure that the mixing time is long enough to ensure adequate filler incorporation and dispersion before the elastomer in the mixture experiences high temperatures and undergoes degradation. In typical dry mixing processes, the ability to control mixing time and temperature to avoid such degradation and optimize filler incorporation and dispersion is often not possible.
[0344] For the presently claimed method, by utilizing wet fillers (e.g., which include fillers and liquids), sufficient liquid is present in the mixture to enable control of batch time and temperature beyond that achievable with known dry mixing processes. Other benefits may be achieved, such as enhanced filler dispersion and / or promotion of rubber-filler interactions and / or improved rubber compound properties.
[0345] Wet fillers are not typically used for commercial production because of the longer mixing times inherently required to evaporate the liquid and disperse the filler in the elastomer (compared to "dry" mixing or dry blending or dry mixing, i.e., dry filler mixed with a solid elastomer).
[0346] Typically, and as described herein, the mixing process can be managed by controlling one or more mixer or process parameters, such as controlled mixer surface temperature, rotor speed, fill factor, ram pressure, incorporation of rubber chemicals (if any) at a later time in the mixing cycle, compound discharge temperature, specific power, and / or the number of mixing steps or stages, such as applying two or more mixing stages.
[0347] The compound formed by the method disclosed herein can be considered as an uncured mixture of filler (one or more) and elastomer (one or more), optionally and one or more additives, wherein the additive is discussed in further detail herein. The formed compound can be considered as a mixture or masterbatch. As an option, the formed compound can be an intermediate product that can be used in subsequent rubber compounding and one or more vulcanization processes. The compound can also undergo other processes (processes) before compounding and vulcanization, such as one or more preservation (holding) steps or further mixing steps (one or more), one or more other drying steps, one or more extrusion steps, one or more calendering steps, one or more grinding steps, one or more granulation steps, one or more packaging steps, one or more twin-screw discharge extrusion steps or one or more rubber processing (working) steps to obtain rubber compound or rubber products.
[0348] The method for preparing the composite comprises the steps of: charging or introducing at least a solid elastomer and a wet filler in a mixer, for example, a) one or more solid elastomers and b) one or more fillers, wherein at least one filler or a portion of at least one filler has been wetted with a liquid (wet filler) before mixing with the solid elastomer. The combination of the solid elastomer and the wet filler forms a mixture during the mixing step(s).
[0349] Wet filler
[0350] The method further comprises, in one or more mixing steps, performing the mixing wherein at least a portion of the liquid is removed by evaporation or an evaporation process occurring during mixing. The liquid of the wet filler can be removed by evaporation (and at least a portion can be removed under the described mixing conditions) and can be a volatile liquid, for example, volatile at the bulk mixture temperature. The volatile liquid can be or include water, for example, at least 50% by weight water, at least 75% by weight water, at least 90% by weight water, at least 95% by weight water, at least 99% by weight water. For example, the liquid may have a boiling point of 180°C or less, such as 170°C or less, 160°C or less, 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 105°C or less at 1 atmosphere, such as 60°C-180°C, 60°C-170°C, 60°C-160°C, 60°C-150°C, 60°C-14 ... ℃-130 ℃, 60 ℃-120 ℃, 60 ℃-110 ℃, 60 ℃-100 ℃, 60 ℃-90 ℃, 90 ℃-180 ℃, 90 ℃-170 ℃, 90 ℃-160 ℃, 90 ℃-150 ℃, 90 ℃-140 ℃, 90 ℃-130 ℃, 90 ℃-120 ℃, 90 ℃-110 ℃, 90 ℃-100 ℃, 95 ℃-120 ℃, or 95 ℃-110 ℃. For example, volatile liquids can be distinguished from oils (e.g., extender oils, process oils) that may be present during at least a portion of the mixing because such oils are intended to be present in the discharged composite and therefore do not evaporate during a significant (substantial) portion of the mixing time.
[0351] About wet filler, in one embodiment, wet filler has the consistency of solid. As an option, dry filler is only wetted to the extent that the obtained wet filler keeps the form of powder, granules, pellets, cake or paste, or similar consistency and / or has the appearance of powder, granules, pellets, cake or paste. Wet filler does not flow like liquid (e.g., under zero applied stress). As an option, wet filler can maintain such shape at 25°C when molded into a certain shape, regardless of whether it is a separate particle, agglomerate, pellets, cake or paste. Wet filler is not a compound made by a liquid masterbatch process and is not any other pre-blended compound (wherein the elastomer is a continuous phase) of a filler dispersed in a solid elastomer (elastomer from a liquid state). In another embodiment, wet filler may be a slurry. In yet another embodiment, wet filler is not a slurry of filler and does not have the consistency of a liquid or slurry.
[0352] In its dry state, the filler may contain no or a small amount of liquid (e.g., water or moisture) adsorbed on its surface. For example, carbon black may have 0 wt%, or 0.1 wt%-1 wt%, or up to 3 wt%, or up to 4 wt% liquid and precipitated silica may have a liquid (e.g., water or moisture) content of 4 wt%-7 wt% liquid, such as 4 wt%-6 wt% liquid. Such fillers are referred to herein as dry or non-wetting fillers. For the present wet filler, liquid or additional liquid may be added to the filler and present on a significant portion or substantially all of the surface of the filler (which may include an inner surface or pores that the liquid can enter and exit). Therefore, prior to mixing with the solid elastomer, sufficient liquid is provided to wet a significant portion or substantially all of the surface of the filler. During mixing, as the wet filler is dispersed in the solid elastomer and the surface of the filler can then become available for interaction with the solid elastomer, at least a portion of the liquid is also removed by evaporation. The wet filler may have a liquid content of at least 15% by weight relative to the total weight of the wet filler, for example, at least 20%, at least 25%, at least 30%, at least 40%, at least 50% by weight, or 15%-99%, 15%-95%, 15%-90%, 15%-80%, 15%-70%, 15%-60%, 15%-65%, 20%-99%, 20%-95%, 20%-90%, 20%-80%, 20%-70%, 20%-60%, 30%-99%, 30%-95%, 30%-90%, 30%-80%, 30%-90%, 30%-80%, 30%-90%, 30%-90%, 30%-80%, 30%-80%, 30%-80%, 30%-80%, 30%-90%, 30%-80%, 30%-80%, 30%-80%, 30%-90%, 30%-90%, 30%-80%, 30%-80%, 30%-80%, 30%-80%, 30%-9 ... The liquid content of the filler can be expressed as a weight percentage: 100*[mass of liquid] / [mass of liquid+mass of dry filler]. As another option, the amount of liquid can be determined based on the oil absorption number (OAN) of the filler, wherein the OAN is determined based on ASTM D1765-10. The OAN is a measure of the filler structure and can be used to determine the amount of liquid used to wet the filler. For example, a wet filler such as wet carbon black, wet silica (e.g., precipitated silica), or wet silicon-treated carbon black can have a liquid content determined according to the following equation: k*OAN / (100+OAN)*100.In one embodiment, k ranges from 0.3-1.1, or 0.5-1.05, or 0.6-1.1, or 0.7-1.1, or 0.8-1.1, or 0.9-1.1, or 0.6-1.0, or 0.7-1.0, or 0.8-1.0, or 0.8-1.05, or 0.9-1.0, or 0.95-1, or 0.95-1.1, or 1.0-1.1.
[0353] The liquid used to wet the filler may be, or include, an aqueous (aqueous) liquid, such as, but not limited to, water. The liquid may include at least one other component, such as, but not limited to, base (one or more), acid (one or more), salt (one or more), solvent (one or more), surfactant (one or more), coupling agent (one or more), and / or processing aid (one or more) and / or any combination thereof. More specific examples of the components are NaOH, KOH, acetic acid, formic acid, citric acid, phosphoric acid, sulfuric acid, or any combination thereof. For example, the base may be selected from NaOH, KOH, and mixtures thereof, or the acid may be selected from acetic acid, formic acid, citric acid, phosphoric acid, or sulfuric acid, and combinations thereof. The liquid may be or include a solvent (one or more) that is immiscible with the elastomer used (e.g., an alcohol such as ethanol). Alternatively, the liquid is composed of about 80% by weight to 100% by weight water or 90% by weight to 99% by weight water based on the total weight of the liquid.
[0354] Solid elastomer
[0355] With respect to the solid elastomer used and mixed with the wet filler, the solid elastomer can be considered to be a dry elastomer or a substantially dry elastomer. The solid elastomer can have a liquid content (e.g., solvent or water content) of 5% by weight or less, for example, 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, or 0.1% by weight to 5% by weight, 0.5% by weight to 5% by weight, 1% by weight to 5% by weight, 0.5% by weight to 4% by weight, etc., based on the total weight of the solid elastomer. The solid elastomer (e.g., the starting solid elastomer) can be entirely an elastomer (having a starting liquid, such as water, content of 5% by weight or less) or can be an elastomer that also includes one or more fillers and / or other components. For example, the solid elastomer can be 50% by weight to 99.9% by weight of an elastomer with 0.1% by weight to 50% by weight of a filler pre-dispersed in the elastomer, wherein the pre-dispersed filler is present in addition to the wet filler. Such an elastomer can be prepared by a dry blending process between a non-wetting filler and a solid elastomer. Alternatively, a compound made by mixing a wet filler and a solid elastomer (e.g., according to the process disclosed herein) can be used as a solid elastomer and further mixed with a wet filler according to the process disclosed herein. However, a solid elastomer is not a compound, mixture or compound made by a liquid masterbatch process and is not any other pre-blended compound of a filler dispersed in the elastomer, although the elastomer is in a liquid state such as a latex, suspension or solution.
[0356] The wet filler can be separately loaded into the mixer and finally mixed with the elastomer in the mixer. The solid elastomer can be one or more pieces or bulk particulate material. Multiple pieces (e.g., strips, sheets, lumps) of elastomer or bulk particulate material can be obtained by cutting or grinding the solid elastomer using methods known in the art. The size of these pieces can have a scale of at least 1 μm, such as at least 10 μm or at least 100 μm up to 10 cm, up to 5 cm, or up to 1 cm.
[0357] Examples of solid elastomers include, but are not limited to, any natural or synthetic elastomer in solid form.
[0358] After the composite is formed and discharged, the method may include the further optional step of mixing the composite with an additional elastomer to form a composite comprising an elastomer blend. The "additional elastomer" may be the same or different from the solid elastomer used in the mixing step and may be any elastomer described herein, a dry combination thereof, such as a natural rubber or a synthetic elastomer (e.g., styrene butadiene rubber (SBR), polybutadiene (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (e.g., EPDM), an isobutylene-based elastomer (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (nitrile rubber) (NBR), hydrogenated nitrile rubber (hydrogenated nitrile rubber) (HNBR), polysulfide rubber, polyacrylate elastomer, fluoroelastomer, perfluoroelastomer, and silicone elastomer). Blends of two or more types of elastomers (blends of the first and second solid elastomers) may also be used, including blends of synthetic elastomers and natural rubber or blends having two or more types of synthetic or natural rubber. For example, two or more different elastomer loading materials may be loaded into a mixer to form a composite blend. Alternatively, an elastomer blend may be loaded into a mixer. As another option, the process may include mixing the discharged composite with another elastomer to form a blend. Alternatively, the process may include mixing the discharged composite with another elastomer (wherein the other elastomer is the same as the solid elastomer initially loaded into the mixer) to form a composite in which the filler loading is diluted. Alternatively, the process may include blending a first discharged composite with a second discharged composite, wherein the first and second discharged composites are each made of a wet filler and a solid elastomer), wherein the first and second discharged composites may have the same or different fillers (e.g., to form a blend of fillers) or may have the same or different elastomers (e.g., to form a blend of elastomers).
[0359] Filling the mixer
[0360] In the method disclosed herein, at least a solid elastomer and a wet filler are loaded (e.g., fed, introduced) into a mixer. For example, the loading of the solid elastomer and the wet filler may be a step in which the solid elastomer and the wet filler are introduced into the mixer. The loading of the solid elastomer and / or the filler may occur in one or more steps or additions. The loading may occur in any manner, including, but not limited to, the solid elastomer and the wet filler are conveyed, metered, dumped and / or fed into the mixer in an intermittent, semi-continuous, or continuous flow. The solid elastomer and the wet filler are not introduced into the mixer as a premix, wherein the premix is prepared by means other than the combination of the solid elastomer and the wet filler. The solid elastomer and the wet filler may be added together, but not as a mixture prepared by means other than the combination of the solid elastomer and the wet filler (e.g., not the case where the wet filler is pre-dispersed in the elastomer by means other than the combination of the solid elastomer and the wet filler, wherein the elastomer is the continuous phase). The mixture or premix or pre-blend from the solid elastomer and the wet filler can be charged to the mixer and can be prepared by many known methods, such as in a mixer or a container. The charging of the solid elastomer and the charging of the wet filler can all occur at once, or sequentially, and can occur in any order. For example, (a) all of the solid elastomer is added first, (b) all of the wet filler is added first, (c) all of the solid elastomer and a portion of the wet filler are added first, followed by one or more remaining portions of the wet filler, (d) a portion of the solid elastomer is added, followed by a portion of the wet filler, (e) at least a portion of the wet filler is added first, followed by at least a portion of the solid elastomer, or (f) a portion of the solid elastomer and a portion of the wet filler are added to the mixer as separate charges at the same time or approximately at the same time.
[0361] As an option for the loading step, the solid elastomer may be plasticated before the wet filler is loaded into the mixer until the solid elastomer reaches a predetermined temperature, for example, a temperature of about 90° C. or 100° C. or higher. The temperature may be 90° C.-180° C., 100° C.-180° C., 110° C.-170° C., 120° C.-160° C., or 130° C.-160° C. The elastomer may be plasticated using an internal mixer such as a Banbury or Brabender mixer, an extruder, a roll mill, a continuous mixer, or other rubber mixing equipment.
[0362] As an option, the loading may be such that the dry filler is introduced into the mixer and wetted by adding a liquid (e.g., water, sequentially or simultaneously or nearly simultaneously) to form a wet filler in the mixer, and then the solid elastomer may be added to the mixer. The introduction of the dry filler to be wetted may be done for all the filler intended to be used or for a portion thereof (e.g., wherein one or more additional portions of the wet filler are further added to the mixer to obtain the intended total amount of starting wet filler).
[0363] As an option, the solid elastomer (all or part) or the wet filler (all or part) can be added to the mixer separately, but added to the mixer within 20 minutes of each other, or within 15 minutes of each other, or within 10 minutes of each other, or within 5 minutes of each other, or within 1 minute of each other, or within 30 seconds of each other, or within 15 seconds of each other.
[0364] Mixing
[0365] With regard to mixing, mixing can be performed in one or more mixing steps. Mixing begins when at least the solid elastomer and the wet filler are loaded into the mixer and energy is applied to the mixing system of the one or more rotors driving the mixer. The one or more mixing steps may occur after the completion of the loading step or may overlap with the loading step for any length of time. For example, a portion of one or more solid elastomers and / or wet fillers may be loaded into the mixer before or after mixing begins. The mixer may then be loaded with one or more additional portions of solid elastomers and / or fillers. For intermittent mixing, the loading step is completed before the completion of the mixing step.
[0366] By "one or more mixing steps", it is understood that the steps disclosed herein (e.g., having the following parameters as described: tip speed, T z , filling factor, specific energy, specific power, etc.) can be the first mixing step, followed by a further mixing step, followed by discharge. Alternatively, the steps disclosed herein (e.g., with the following parameters described: tip speed, T z , fill factor, specific energy, specific power, etc.) need not be performed as the first mixing step. For example, the one or more mixing steps may include a first mixing step in which the solid elastomer and the wet filler are mixed under conditions in which a very small amount of liquid is removed by evaporation. For example, the first mixing step may form a pre-blend. The mixture from the first mixing step may then be subjected to a second or further mixing step, which uses the disclosed process (e.g., having the following parameters described: tip speed, T z, filling factor, specific energy, specific power, etc.). As understood in the art, the mixing step is equivalent to the mixing stage.
[0367] As shown, during the one or more mixing steps, in any method disclosed herein, at least some liquid present in the mixture and / or the wet filler introduced is at least partially removed by evaporation. As an option, most of any liquid removed from the mixture (in % by weight) occurs by evaporation. For example, at least 50 % by weight of the liquid is removed by evaporation, based on the total weight of the liquid removed during mixing. The total weight of the liquid removed can be determined by the difference between the liquid content of the wet filler and any liquid left in the composite when discharged from the mixer plus any liquid present in the mixer or discharged from the mixer when the composite is discharged from the mixer. For example, when the composite is discharged, additional liquid (e.g., unevaporated liquid) may also be discharged with the composite or in the composite or through an outlet provided in the mixer. The liquid removed by evaporation may constitute at least 30 wt %, at least 40 wt %, at least 50 wt %, at least 60 wt %, at least 70 wt %, at least 80 wt %, or 51 wt %-100 wt %, 51 wt %-95 wt %, 51 wt %-90 wt %, 51 wt %-80 wt %, 51 wt %-70 wt %, 60 wt %-100 wt %, 60 wt %-95 wt %, 60 wt %-90 wt %, or 60 wt %-80 wt % of the total liquid contained in the wet charge charged to the mixer.
[0368] As an option, the one or more mixing steps or stages can further remove a portion of the liquid from the mixture by squeezing, compacting, and / or wringing, or any combination thereof. Alternatively, after or while discharging the composite, a portion of the liquid can be drained from the mixer.
[0369] With regard to the mixer that can be used in any method disclosed herein, any suitable mixer that can combine fillers with solid elastomers (e.g., mix together or compound together) can be utilized. The mixer (one or more) can be an intermittent mixer or a continuous mixer. A combination of multiple mixers and multiple processes can be utilized in any method disclosed herein, and the mixer can be used sequentially, in series and / or integrated with other processing equipment. The mixer can be a closed or closed mixer open mixer, or an extruder or a continuous mixer or a kneading mixer or a combination thereof. The mixer can be capable of incorporating fillers into solid elastomers and / or can disperse fillers in elastomers and / or distribute fillers in elastomers. Any one or combination of commercial mixers that produce rubber compounds can be used in the present method.
[0370] The mixer may be capable of batch processing, continuous processing, or semi-continuous processing. The mixer may have any chamber capacity. A closed mixer generally includes an enclosed mixing chamber. For a batch mixer, the chamber capacity may be at least 1 L, at least 2 L, at least 5 L, at least 10 L, at least 20 L, at least 50 L, at least 100 L, at least 250 L, at least 300 L, at least 600 L, or at least 1000 L, such as 1 L-1500 L, 10 L-1200 L, 10 L-1000 L, 10 L-750 L, 10 L-500 L, 10 L-300 L, 10 L-400 L, 10 L-500 L, 10 L-600 L, 10 L-700 L, 10 L-800 L, 10 L-900 L, 10 L-1100 L, 10 L-1200 L, 10 L-1000 L, 10 L-750 L, 10 L-500 L, 10 L-3 ...200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 L, 10 L-1200 10L-100L, 20L-1500L, 20L-1200L, 20L-1000L, 20L-750L, 20L-500L, 20L-300L, 20L-100L, 50L-1500L, 50L-1200L, 50L-1000L, 50L-750L, 50L-500L, 50L-300L, or 50L-100L.
[0371] The top of a typical batch mixing chamber can be raised and lowered by an inflatable or hydraulic piston (often called a "floating weight" or "jack"). The jack operates within a housing called a "feed hopper" that has a loading door through which the material to be mixed is introduced. The jack is raised to feed the material (e.g., at least a solid elastomer and a wet filler) and lowered to apply pressure to the mixture and confine the mixture within the mixing chamber. Typically, the filling factor and jack pressure of the batch are selected so that the jack can reach its lowest position to minimize the spacing between the jack and the rotor, which can achieve good filler dispersion. The vertical distance that the jack is above its lowest position is called the "jack offset." The bottom of a typical batch mixer can be lowered onto a pivot and is called a "lift gate." It is used to discharge or "dump" the contents of the mixer.
[0372] The mixer may have one or more rotors (at least one rotor). For example, each rotor may rotate in its own cylindrical chamber, which may be connected to the chamber of other rotors (one or more). Typically, for an intermittent mixer, two rotors are utilized. The body of the one or more rotors is connected to an axle and may form an integral component. The axle is controlled by a mixing system to which energy (electrical energy) is applied. The rotor may be considered as a device for imparting energy to a mixture and / or to the components forming the mixture. The rotor may be designed to have an internal circuit or passage with steam or water or other fluids for cooling and / or heating. If there are two rotors, they may rotate in the same or opposite directions generally, and may rotate at the same or different speeds (e.g., differing by no more than 20rpm or differing by no more than 10rpm). The sharp convergence of the rotor with the chamber wall and / or the sharp convergence between the rotors imparts shearing to the mixture and the resulting intensive work produces a generally uniform mixture. The at least one rotor or the one or more rotors may be a screw-type rotor, a meshing rotor, a tangential rotor, a kneading rotor (one or more), a rotor for an extruder, a roller mill imparting a significant total specific energy, or a creper mill. Typically, one or more rotors are utilized in a mixer, for example, a mixer may incorporate one rotor (e.g., a screw-type rotor), two, four, six, eight or more rotors. The rotor groups may be arranged in parallel and / or in a sequential orientation within a given mixer configuration.
[0373] In one instance, liquid evaporated from the mixture can exit the mixer from a gap between the ejector pin and the body and / or a port or outlet or vent designed to release evaporated liquid (e.g., vapor). For example, in a continuous mixer (e.g., a devolatilizing extruder), evaporated liquid can be released through a vent stuffer or through a piston that periodically clears material (e.g., evaporated liquid) through a vent or outlet or port.
[0374] The one or more mixing steps may be a single mixing step, for example, a stage or a single-stage mixing step or process, wherein mixing is performed under one or more of the following conditions: at least one of the mixer temperatures is controlled by a temperature control means and one or more rotors are operated at a tip speed of at least 0.6 m / sat for at least 50% of the mixing time, and / or the at least one temperature control means is set to a temperature Tz of 65°C or higher, a filling factor of 68% or lower, an average specific power of at least 2.5 kW / kg is applied during the mixing time, and / or continuous mixing, and / or mixing is performed in the substantial absence of the one or more rubber chemicals before the mixer reaches the indicated temperature; each is further described in detail herein. In some cases, the compound may be discharged in a single stage or single mixing step with a liquid content of no more than 10% by weight. In other embodiments, two or more mixing steps or mixing stages may be performed, as long as one of the mixing steps is performed under one or more of the conditions.
[0375] In the case of multi-stage mixing, as an option, a second or any number of subsequent stages of mixing can provide a compound that improves the properties of the corresponding compound compared to a compound prepared by mixing using only a single stage of mixing. In other words, the compound formed by a single stage of mixing can be compared to a compound formed by another stage of mixing process, such as a compound that undergoes a second stage. When such multi-stage mixing is utilized, one or more of the properties of the corresponding compound (e.g., tan δ and / or tensile stress ratio) can be improved. In terms of one or more properties, the improvement can be 5%, 10%, or 15% or more improvement compared to a compound prepared by a compound that undergoes a single stage of mixing. The improvement can be obtained independently of the type of filler used and independently of the type of elastomer used. For example, the second stage can be carried out with a second mixer operating under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its maximum level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ramless; and (vi) the fill factor of the mixture ranges from 25% to 70%.
[0376] The process may utilize one or more mixing steps and / or one or more mixers. For example, mixing the at least solid elastomer and the wet filler to form a mixture, removing at least a portion of the liquid from the mixture by evaporation, and discharging a compound having a liquid content of no more than 10% by weight from the mixer may occur as one mixing step in one mixer. In the case of more than one mixing step, the discharged product, while the compound, may also be referred to as a mixture because it will undergo further processing or mixing to form the final compound. In another example, the first mixing step includes mixing the at least solid elastomer and the wet filler to form a mixture, and the second mixing step includes discharging a compound (or mixture) having a liquid content of no more than 10% by weight from the mixer. In this option, the first and second mixing steps may be performed in the same or different mixers. In yet another example, mixing the at least solid elastomer and the wet filler to form a mixture, removing at least a portion of the liquid from the mixture by evaporation, and discharging the compound (or mixture) having a liquid content of no more than 10% by weight from the mixer may occur as one mixing step, and a second mixing step (in the same or second mixer) may be performed to further dry the compound (or mixture). In other words, the process may include using more than one mixer, such that the mixture is mixed in a first mixer in a first mixing step, then removed and loaded into a second mixer in a second mixing step, and so on as desired. Each mixer, if more than one is used, may be the same or different from the other mixers used in the method. For example, the compound (or mixture) may be discharged from the first mixer and otherwise transferred to the second mixer. In another example, the compound (or mixture) may be discharged from the mixer and then loaded back into the same mixer (e.g., after being allowed to cool). These processes, which may be referred to as multi-stage mixing, may be repeated as many times as desired. Each stage can be mixed using the same or one or more different operating parameters.
[0377] During a typical dry mixing process using fillers (non-wetted) and solid elastomers, the temperature of the mixture increases, at least in part due to viscous flow of the elastomer, for example, during mastication of the elastomer and / or mixing as fillers are incorporated into the elastomer. This increase can be quite rapid, and the mixture is typically discharged before significant thermal degradation of the rubber occurs, regardless of whether adequate filler dispersion has been achieved.
[0378] It has been found that by incorporating wet fillers during the mixing process, the presence and subsequent evaporation of a liquid can enable improved dispersion of the filler in the elastomer. In order to obtain a suitable final compound, the amount of liquid is reduced (e.g., to an amount of 10% or less based on the total weight of the compound). Without wishing to be bound by any theory, the presence of a liquid can cool and / or lubricate the mixture, which can reduce the overall rate of temperature rise, which can increase the mixing or residence time and improve filler dispersion without significant degradation of the elastomer. Further, these can lead to improved compound and vulcanizate properties.
[0379] Temperature control
[0380] In certain embodiments, in at least one of the mixing steps, the method includes mixing at a mixer temperature controlled by at least one temperature control means. In other words, the method may include mixing at a controlled mixer temperature (e.g., by using a temperature controller). Controlling the mixer temperature refers to controlling the temperature of at least one surface of the mixer. As an option, the mixer temperature can be controlled during at least one of the mixing steps and during both filling. The temperature control means may be a temperature control device on and / or in the mixer or otherwise associated with the mixer (e.g., connected to the mixer) that heats or cools at least one surface of the mixer, and / or one or more components. Without wishing to be bound by any theory, by controlling the mixer temperature, such as the mixer surface temperature, via a temperature control means, mixing characteristics such as the slippage and grip of the mixture at the mixer surface can be affected, which can affect the shear and viscous flow of the mixture in the mixer, and can further affect the heating of the mixture.
[0381] Slippage can be a problem when liquid is present in the mix. Without wishing to be bound by any theory, the risk of excessive slippage (lubrication) may be more likely to occur when the surface temperature of the mixer surface is too low. Such excessive slippage may result in less viscous flow and subsequent low heat generation, which in turn may reduce the rate of removal of liquid by evaporation and result in inefficient or insufficient mixing, inefficient or insufficient drying, and / or long mixing times. There may be slow filler incorporation and / or poor filler dispersion in the elastomer. In typical mixing with dry fillers, slippage is not a significant problem; however, the viscous flow of the mixture may be more pronounced and may result in faster heating, which may degrade the elastomer. Such rapid heating (which results in a rapid temperature rise of the mixture) requires a short residence or mixing time to avoid rubber degradation. Inadequate mixing and insufficient filler dispersion may result.
[0382] Without wishing to be bound by any theory, when mixing wet filler and solid elastomer without temperature control of at least one surface of the mixer (e.g., mixing in the absence of at least one temperature control means), there may be less opportunity to control slip and resulting temperature properties, such as temperature profiles. At the initial stage of mixing, when operating a sequential mixing process or batch, the mixer surface temperature may have a wide range of surface temperatures, such as from room temperature to a high temperature of, for example, 180° C. or more. Loading solid elastomer and wet filler into a mixer at room temperature may result in inefficient mixing because excessive slip is more likely to occur and heating of the mixture may be delayed or may not even occur. As a result, mixing may be inefficient, or the mixture may be discharged with a high liquid content and / or with unincorporated filler at the surface of the mixture. Loading solid elastomer and wet filler into a mixer at high temperature in the absence of temperature control means may result in too fast evaporation of the liquid and the benefits of using wet filler are not realized. Without temperature control means, mixing characteristics and mixture quality may be difficult to control and may vary between mixing processes. At temperatures above the boiling point of the liquid, flashing and loss of liquid can occur. If the loss of liquid occurs in the form of vapor, the vapor can transport filler, resulting in loss of filler yield. In some cases, high surface temperatures of mixer components can create safety hazards.
[0383] Without wishing to be bound by any theory, if the mixer surface temperature is controlled (e.g., by temperature control means), the slip between the mixture and the mixer surface can be controlled, which in turn can affect the mixture viscous flow and resulting heating. Additionally or alternatively, the controlled mixer surface temperature can achieve a better grip of the mixer surface by the mixture. By controlling the mixer surface temperature, it may be possible to control the viscous flow heating and the mixing time to achieve a target discharge temperature.
[0384] Without wishing to be bound by any theory, alternatively or in addition to any other mechanism, controlling the mixer surface temperature by at least one temperature control means can enable control of the surface or overall temperature of the mixture. At the beginning of mixing, the solid elastomer in the mixture is typically at room temperature, and in the case where the mixer surface temperature is greater than the surface temperature of the mixture, the mixer surface can transfer heat to at least a portion of the mixture so that the mixture surface temperature can be increased. Without wishing to be bound by any theory, alternatively or in addition to any other mechanism, the increase in the mixture surface temperature can enable the mixture to grip the mixer surface, thereby reducing slippage and allowing the mixer to input more energy into the mixture and generate enough heat via viscous flow, ultimately removing the liquid. Once the mixture temperature exceeds the mixer surface temperature, the mixer surface can allow heat to be transferred from the mixture. In other words, the mixer cools at least a portion of the mixture, for example, cooling the surface or the body. This cooling can delay rapid temperature increases and allow longer mixing or residence times at temperatures that do not degrade the rubber.
[0385] This control of mixer surface temperature by whatever mechanism(s) may provide the opportunity for longer mixing or residence times compared to a mixing process without temperature control of at least one mixer surface, which may result in improved filler dispersion and / or improved rubber-filler interaction and / or consistent mixing and / or efficient mixing.
[0386] The temperature control means may be, but is not limited to, a channel in which a heat transfer fluid flows or flows through one or more components of a mixer. For example, the heat transfer fluid may be water or heat transfer oil. For example, the heat transfer fluid may flow through a rotor, a mixing chamber wall, a top bolt, and a lift gate. In other embodiments, the heat transfer fluid may flow in a jacket (e.g., a jacket with fluid flow means) or a coil around one or more components of a mixer. As another option, the temperature control means (e.g., supply heat) may be an electrical component embedded in the mixer. The system for providing the temperature control means may further include a means for measuring the temperature of the heat transfer fluid or the temperature of one or more components of the mixer. The temperature measurement result may be fed to a system for controlling the heating and cooling of the heat transfer fluid. For example, the desired temperature of at least one surface of the mixer may be controlled by setting the temperature of the heat transfer fluid in a channel adjacent to one or more components of the mixer such as a wall, a door, a rotor, etc.
[0387] As an example, the temperature of the at least one temperature control means may be set and maintained by one or more temperature control units ("TCU"). The set temperature, or TCU temperature, is also referred to herein as "T z ". In the case of introducing the temperature control means of the heat transfer fluid, T zis an indication of the temperature of the fluid itself. The heating or cooling provided by the temperature control means depends on T z , is transferred to at least one surface of the mixer or one or more components of the mixer; heat is transferred to or from the at least one surface and then to or from the material in the mixer to affect the overall temperature of the mixture or a portion thereof, such as a local temperature of the mixture. If the flow of the heat transfer fluid is sufficient, the transferred heating or cooling should result in a temperature of the mixer component that is reasonably close to T z As an option, the velocity of the heat transfer fluid in the channel is at least 1 m / s.
[0388] The mixer may have thermocouples located at different parts (components) of the mixer to provide a more accurate measurement of the temperature of the mixer component (s) or the mixture. Typical thermocouples installed in commercial mixers are effective in measuring the temperature of the mixture. The temperature of the at least one surface may deviate from T z , but should still be reasonably close to T z , for example, the average surface temperature of at least one surface is from T z Deviation + / -5%, + / -10%, + / -20%.
[0389] In an alternative or additional embodiment, the temperature control means or device includes a communication link between the temperature monitoring / setting device and a heating / cooling device such as a heater chiller or a combined heater-chiller (having the ability to heat a fluid or chill a fluid to maintain a set temperature).
[0390] The mixer may have more than one temperature control means or devices, such as two, three, or more, each providing a temperature control zone within the mixer or mixer section. When more than one temperature control means or devices are utilized, each temperature control means or means may utilize the same or different T z As a further example, when two or more temperature control devices or means are used, the temperature difference between each temperature setting may be 0°C or about 0°C, or may be 1°C-100°C or 1°C-50°C, such as 5°C-50°C (e.g., T Z1 , T Z2 , T Z3The one or more temperature control means or devices may be located at any part or component of the mixer (one or more). For example, the wall (one or more) or all walls of the mixer or mixer chamber, and / or the top bolt, and / or the lifting door (one or more), and / or the one or more rotors, and / or the extrusion head may be temperature controlled to form one or more temperature control zones. As an option, the at least one temperature control means heats at least the wall of the mixer.
[0391] As mentioned, the mixer temperature or mixer temperatures may be controlled by at least one temperature control means. As an option, and typically, the temperature control means may be set to a temperature T in the range of 5°C-150°C or in the range of 5°C-155°C. z For example, if the mixer is equipped with a fluid jacket, the heat transfer fluid passing through the fluid jacket is at T before any heat transfer occurs with the material in the mixer. z Or about T z , for example, with T z The difference is not more than 5°C or not more than 2°C or not more than 1°C. As an option, the temperature control means can be set to a temperature T in the range of z : 30°C-150°C, 40°C-150°C, 50°C-150°C, or 60°C-150°C, for example 30°C-155°C, 30°C-125°C, 40°C-125°C, 50°C-125°C, 60°C-125°C, 30°C-110°C, 40°C-110°C, 50°C-110°C, 60°C-110°C, 30°C-100°C, 40°C-100°C, 50°C-100°C, 6 0°C-100°C, 30°C-95°C, 40°C-95°C, 50°C-95°C, 50°C-95°C, 30°C-90°C, 40°C-90°C, 50°C-90°C, 65°C-95°C, 60°C-90°C, 70°C-110°C, 70°C-100°C, 70°C-95°C, 70°C-90°C, 75°C-110°C, 75°C-100°C, 75°C-95°C, or 75°C-90°C. Other ranges are possible with equipment available in the art. During the filling step, the temperature control means may be set to any of these temperatures Tz.
[0392] In other embodiments, the temperature control means may be set to a higher temperature than typically used for dry mixing, for example, a temperature of 65° C. or higher (T z ). zis imparted by temperature control means. For example, if the mixer is equipped with a fluid jacket, the heat transfer fluid passing through the fluid jacket is at or about this temperature, e.g., within 5°C, or within 2°C, or within 1°C, before any heat transfer with the material in the mixer. (T z ) can be set to a temperature within the following range: 65℃-140℃, or 65℃-130℃, or 65℃-120℃, or 65℃-110℃, or 65℃-100℃, or 65℃-95℃, or 70℃-130℃, or 70℃-120℃, or 70℃-110℃, or 70℃-100℃, or 80℃-140℃, or 80℃-130℃, or 80℃-120℃, or 80℃-110℃, or 80℃-100℃, or other temperatures within these ranges or above or below these ranges.
[0393] Best T z The value of T may be selected based on the filler type. For example, for a filler including carbon black and silicon-treated carbon black (e.g., at least 50 wt. %, at least 75 wt. %, at least 90 wt. %, or all or substantially all of the filler is carbon black or silicon-treated carbon black), T z It may have the values described herein, for example, 65° C. or greater or 65° C.-100° C. When the filler is silica, the Tz value may range from 40° C.-110° C., 40° C.-100° C., for example, 40° C.-90° C., 40° C.-80°, 40° C.-75° C., 50° C.-110° C., 50° C.-100° C., 50° C.-90° C., 50° C.-80°, 50° C.-75° C., 60° C.-110° C., or 60° C.-100° C.
[0394] As an option, for example, if the mixer conditions produce sufficient mechanical energy input, T z The upper limit of Tz should not substantially exceed the boiling point of the liquid in the wet filler. If too fast evaporation occurs, this can result in liquid removal before sufficient mixing has occurred and in addition, some of the filler can escape with the vapor (e.g., steam) through the mixer vent, resulting in insufficient filler loading and high filler yield loss in the discharged composite. Moreover, some of the loose filler can coat the surface of the composite. As an option, the upper limit of Tz can be selected to be close to the boiling point of the liquid, such as the boiling point of the liquid + 10 ° C, or + 5 ° C, or + 1 ° C, or -1 ° C, or -5 ° C, or -10 ° C.
[0395] One option to prevent the temperature of the mixture from exceeding the boiling point of the liquid during charging or in the early stages of mixing is to stage the addition of the wet filler to the mixer. For example, a portion or a portion of the filler can be added at the beginning and the remainder added later in the mixing cycle (in one or more addition steps). Another option is to select mixer conditions that allow all of the wet filler to be added at or near the beginning of the cycle. Another option is to add additional liquid (e.g., water) to the mixer (e.g., mixer chamber) to cool the mixture.
[0396] Total specific energy
[0397] Compared with dry mixing, the present process can allow higher energy input when the filler type, elastomer type, and mixer type are similar. The controlled removal of liquid from the wet filler achieves a longer mixing time and thus improves the dispersion of the filler. The energy input can be represented by the resulting total specific energy given to the composite during the mixing process. For example, mixing occurs when at least the wet filler and the solid elastomer are loaded into the mixer and energy is applied to at least one rotor. For example, in an intermittent mixer, the total specific energy considers the energy applied to the rotor (one or more) between the loading and discharge of the solid elastomer and / or wet filler per kg of the composite on a dry weight basis. For a continuous mixer, the total specific energy is the power (power input) input per kg of output on a dry weight basis under steady-state conditions. For a process with multi-stage mixing, the total specific energy is the sum of the specific energies from each mixing process. The determination of the total specific energy preferably does not include the amount of energy used to shape or form the discharged composite (e.g., excluding the energy of rolling the composite). The resulting "total specific energy" as defined herein is the energy E applied to the mixing system driving the one or more rotors relative to the mass of the compound on a dry weight basis. R (e.g., electrical energy). This total specific energy may also be referred to as E 总 As described herein, the present process provides an overall specific energy under selected operating conditions that balances longer mixing times with evaporation or removal of water in a reasonable amount of time.
[0398] As an option, the process includes, in at least one of the mixing steps, mixing so that the resulting total specific energy is at least 1,100 kJ / kg, at least 1,200 kJ / kg, at least 1,300 kJ / kg, or at least 1,400 kJ / kg or at least 1,500 kJ / kg of the composite, for example, at least 1,600 kJ / kg, at least 1,700 kJ / kg, at least 1,800 kJ / kg, at least 1,900 kJ / kg, at least 2,000 kJ / kg, at least 2,500 kJ / kg, or at least 3,000 kJ / kg. As an alternative for some systems, the total specific energy may range from 1,000 kJ / kg to 3,000 kJ / kg, for example, 1,000 kJ / kg to 2,500 kJ / kg, 1,100 kJ / kg to 2,500 kJ / kg, etc. As an option, the total specific energy may range from about 1,400 kJ / kg of the compound or about 1,500 kJ / kg of the compound (or per kg of the mixture present in the mixer) to about 10,000 kJ / kg of the compound (or per kg of the mixture present in the mixer), for example, 2,000 kJ / kg to about 5,000 kJ or 1,500 kJ / kg to 8,000 kJ / kg, 1,500 kJ / kg to 7,000 kJ / kg, 1,500 kJ / kg to 6,000 kJ / kg, 1, 500 kJ / kg-5,000 kJ / kg, 1,500 kJ / kg-3,000 kJ / kg, 1,600 kJ / kg-8,000 kJ / kg, 1,600 kJ / kg-7,000 kJ / kg, 1,600 kJ / kg-6,000 kJ / kg, 1,600 kJ / kg-5,000 kJ / kg, 1,600 kJ / kg-4,000 kJ / kg, 1,600 kJ / kg-3,000 kJ / kg, or other values within any of these ranges.
[0399] Specific energy after filler addition
[0400] In addition to the total specific energy, understanding E 100%填料 and E 75%填料 and how they compare to the overall specific energy may be useful in one or more aspects disclosed herein. 100%填料 is the amount of specific energy (kJ / kg dry compound) utilized once 100% (by weight) of all fillers are added or present during compounding (in the mixer) and until the compound is discharged and has a liquid content of not more than 10% by weight, e.g., not more than 5% by weight, not more than 4% by weight, not more than 3% by weight, or not more than 2% by weight. In addition, E 75%填料E is the amount of energy utilized (kJ / kg dry compound) once 75% by weight of all fillers are added or present during compounding until the compound is discharged and has a liquid content of no more than 10% by weight, such as no more than 5% by weight, no more than 4% by weight, no more than 3% by weight, or no more than 2% by weight. In addition to the time point when the amount of energy input to compounding is calculated, E is measured. 100%填料 and E 75%填料 The way is no different than the total specific energy.
[0401] E 100%填料 and E 75%填料 It can be measured from the point in time when the ram is lowered to start or restart mixing (the latter being the case where two or more filler addition steps are performed) after the filler has been loaded into the mixer. 100%填料 will be different from E 75%填料 And, unless all the fillers have been added before any mixing, the total specific energy will be higher than E 100%填料 and E 75%填料 As an option, it is understood from various experiments that the minimum E 100%填料 and minimum E 75%填料 , which is not necessarily the same as the minimum total specific energy. Sometimes, a better understanding of filler-elastomer interactions can be obtained by combining one or more studies and understandings of the methods disclosed herein. 100%填料 and / or E 75%填料 And realize.
[0402] The properties of rubber compounds can be driven in part by the formulation (elastomer, filler type, etc.) and how these ingredients are brought together (e.g., by mixing). For a given material selection and filler loading, the properties can be affected by (a) the degree of filler dispersion and its distribution in the elastomer matrix, (b) the adhesion (interaction) between the filler and the polymer, (c) the polymer properties, and other factors. The challenge is to improve dispersion by mixing without negatively affecting the interaction and / or degrading the polymer. Degradation from high energy input can be viewed as the breaking of polymer chains and oxidation for elastomers such as natural rubber or gel formation for synthetic rubbers. Without wishing to be bound by any theory, with wet fillers, more specific energy can be applied to the mixture and can be used for dispersion compared to mixing with dry fillers. This energy can then be partially released by evaporation of the liquid. This is in contrast to dry mixing, in which most of the energy input leads to temperature rise and subsequent potential degradation of the elastomer.
[0403] For fillers, for example, when the filler includes or is carbon black or a carbon-based filler (e.g., a dual-phase carbon black-silica or a carbon black-silicon aggregate, e.g., a silicon-treated carbon black), or when the filler is primarily (based on the weight of the total filler) carbon black or a carbon-based filler, there may be a preferred minimum amount of specific energy (E) for dispersing the wet filler after a significant amount of filler (at least 75% by weight of the total wet filler in the composite) has been charged into the mixer to obtain the desired improvement in the properties of the resulting rubber compound.
[0404] For example, as at least one option, 1100 kJ / kg (E 100%填料 ) or 1300kJ / kg(E 75%填料 ) can be used to achieve the desired one or more reinforcing properties, or other elastomeric properties (e.g., M300 / M100 and / or hysteresis (tan δ)) of the resulting vulcanizate. Thus, below these energy values, for systems using predominantly wet carbon-based fillers such as carbon black or silicon-treated carbon black, the composite can result in a vulcanizate having less than optimal properties.
[0405] As an option, the process includes, in at least one of the mixing steps, mixing such that the resulting E 100%填料 At least 1,100 kJ / kg of the composite, e.g., at least 1,150 kJ / kg, at least 1,200 kJ / kg, at least 1,300 kJ / kg, at least 1,400 kJ / kg, at least 1,500 kJ / kg, at least 2,000 kJ / kg, or at least 3,000 kJ / kg. 100%填料 The range may be from about 1,100 kJ / kg of the compound (or per kg of the mixture present in the mixer) to about 10,000 kJ / kg of the compound (or per kg of the mixture present in the mixer), for example 1,100 kJ / kg to about 5,000 kJ or 1,200 kJ / kg to about 8,000 kJ / kg, 1,300 kJ / kg to about 7,000 kJ / kg, 1,400 kJ / kg to about 6,000 kJ / kg, 1,500 kJ / kg to about 8,000 kJ / kg, 1,600 kJ / kg to about 9,000 kJ / kg, 1,700 kJ / kg to about 10,000 kJ / kg, 1,800 kJ / kg to about 2,000 kJ / kg, 1,900 kJ / kg to about 3,000 kJ / kg, 2,100 kJ / kg to about 5,000 kJ kJ / kg, 1,600 kJ / kg-5,000 kJ / kg, 1,500 kJ / kg-3,000 kJ / kg, 1,600 kJ / kg-8,000 kJ / kg, 1,600 kJ / kg-7,000 kJ / kg, 1,600 kJ / kg-6,000 kJ / kg, 1,600 kJ / kg-5,000 kJ / kg, 1,600 kJ / kg-3,000 kJ / kg, or other values within any of these ranges.
[0406] As an option, the process includes, in at least one of the mixing steps, mixing such that the resulting E75%填料 At least 1,300 kJ / kg of the composite, for example, at least 1,350 kJ / kg, at least 1,400 kJ / kg, at least 1,500 kJ / kg, at least 1,600 kJ / kg, at least 1,700 kJ / kg, at least 1,800 kJ / kg, or at least 2,000 kJ / kg or at least 3,000 kJ / kg. 75%填料 The range may be from about 1,300 kJ / kg of the compound (or per kg of the mixture present in the mixer) to about 10,000 kJ / kg of the compound (or per kg of the mixture present in the mixer), for example 1,350 kJ / kg to about 5,000 kJ or 1,400 kJ / kg to 8,000 kJ / kg, 1,500 kJ / kg to 7,000 kJ / kg, 1,600 kJ / kg to 6,000 kJ / kg, 1,700 kJ / kg to 8,000 kJ / kg, 1,800 kJ / kg to 9,000 kJ / kg, 1,900 kJ / kg to 2,000 kJ / kg, 2,100 kJ / kg to 3,000 kJ / kg, 3,150 kJ / kg to 4,000 kJ / kg, 4,160 kJ / kg to 5,000 kJ / kg, 5,170 kJ / kg to 6,000 kJ / kg, 6,180 kJ / kg to 7,000 kJ / kg, 7,190 kJ / kg to 8,000 kJ / kg, 8,190 kJ / kg to 9,000 kJ / kg, 9,100 kJ / kg to 10,000 kJ / kg, 11,150 kJ / kg to 12,000 kJ / kg, 12 kJ / kg, 1,600 kJ / kg-7,000 kJ / kg, 1,600 kJ / kg-6,000 kJ / kg, 1,600 kJ / kg-5,000 kJ / kg, 1,600 kJ / kg-3,000 kJ / kg, or other values within any of these ranges.
[0407] Specific power
[0408] As an option, the method includes applying an average specific power (specific energy / mixing time, kW / kg) during the one or more mixing steps. The average specific power can be reported for a single mixing step, such as the first stage mixing, where the average specific power of the mixing stage = specific energy / mixing time. The mixing time can be the time when the top bolt is lowered. For continuous mixing, the average specific power can be calculated by dividing the average specific energy by the mixer residence time. Alternatively, for continuous mixing, the average specific power can be calculated by dividing the mass of the material in the mixer at a certain point in time (kg) over a defined period of time (kW).
[0409] As an option, the average specific power applied is at least 2.5 kW / kg during the mixing time, for example, at least 3 kW / kg, at least 3.5 kW / kg, at least 4 kW / kg, at least 4.5 kW / kg, 2.5 kW / kg-10 kW / kg, 2.5 kW / kg-9 kW / kg, 2.5 kW / kg-8 kW / kg, or 2.5 kW / kg-10 kW / kg during the time when the top bolt is lowered. As an option, one or more parameters can be selected to obtain the desired specific power, including but not limited to, liquid content in the filler, Tz, filling factor, and / or tip speed.
[0410] If a sufficiently high average specific power is used during mixing with wet fillers, the mixing time, such as the plunger down time, can be reduced to an amount suitable for both efficiency and product properties. Thus, as an option, the method includes, in at least one or more mixing steps, applying an average specific power of at least 2.5 kW / kg (or other ranges disclosed herein) during a plunger down time of 10 minutes or less, such as 8 minutes or less, or 6 minutes or less.
[0411] The energy applied, for example imparted, by one or more rotors in the mixer may be constant or relatively constant. As an option, during the mixing process, the instantaneous specific energy per unit time (kJ / (min-kg) (specific power) may differ from the average specific energy per unit time (average specific power) by no more than 10%.
[0412] peripheral speed
[0413] As an option, the process includes, in at least one of the mixing steps, mixing is performed such that one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time or at a tip speed of at least 0.6 m / s for at least 50% of the mixing time. The energy input to the mixing system varies at least in part with the speed of the at least one rotor and the type of rotor. The tip speed (which takes into account the rotor diameter and the rotor speed) can be calculated according to the following formula:
[0414] Tip speed, m / s = πx(rotor diameter, m)x(rotation speed, rpm) / 60.
[0415] Since the tip speed can vary during the mixing process, as an option, a tip speed of at least 0.5 m / s or at least 0.6 m / s is achieved for at least 50% of the mixing time, for example, at least 60%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or substantially all of the mixing time. The tip speed can be at least 0.6 m / s, at least 0.7 m / s, at least 0.8 m / s, at least 0.9 m / s, at least 1.0 m / s, at least 1.1 m / s, at least 1.2 m / s, at least 1.5 m / s or at least 2 m / s for at least 50% of the mixing time, or other portions of the mixing listed above. The tip speed can be selected to minimize the mixing time, or can be 0.6m / s-10m / s, 0.6m / s-8m / s, 0.6-6m / s, 0.6m / s-4m / s, 0.6m / s-3m / s, 0.6m / s-2m / s, 0.7m / s-4m / s, 0.7m / s-3m / s, 0.7m / s-2m / s, 0.7m / s-10m / s, 0.7m / s-8m / s, 0.7-6m / s, 1m / s-10m / s, 1m / s-8m / s, 1m / s-6m / s, 1m / s-4m / s, 1m / s-3m / s, or 1m / s-2m / s, (e.g., for at least 50% of the mixing time or other mixing times described herein). Alternatively or additionally, the tip speed may be selected to maximize throughput. Time / throughput considerations may take into account that as mixing time decreases, the liquid level in the discharged compound may increase. In some cases, mixing at a high tip speed may be beneficial for higher throughput balanced with the desired liquid content of the discharged compound (e.g., too high a tip speed may result in shorter residence or mixing times, which may not allow adequate filler dispersion or adequate removal of liquid from the compound).
[0416] Discharge, mixing time, and dump or mixer temperature
[0417] In any of the methods disclosed herein, a step of discharging from a mixer occurs and results in a composite comprising a filler dispersed in an elastomer at a loading of at least 1 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10% by weight. During the mixing cycle, after much of the liquid has been released from the composite and the filler has been incorporated, the mixture undergoes a temperature increase. It is desirable to avoid excessive temperature increases that would degrade the elastomer. Discharging, (e.g., "dumping" in intermittent mixing) can occur based on a time or temperature or specific energy or power parameter selected to minimize such degradation.
[0418] In one embodiment, the mixing time can be determined by the period from completion of loading to discharge. For intermittent closed mixers, the mixing time can be determined by the time the top bolt is lowered, for example, the time the top bolt is operated at the lowest position, such as the time when the top bolt is fully closed or in place. In other embodiments, the lowest position of the top bolt can allow a certain amount of top bolt excursion (as disclosed herein), for example, the maximum top bolt excursion from the lowest position is a distance of no more than 30% of the rotor diameter. The mixing time does not include the period when additional components are loaded, such as one or more additional portions of elastomers and / or fillers. As an option, for a continuous mixer, the nominal mixing time (or residence time) can be calculated from the mixer chamber volume and the volume production rate.
[0419] As an option, the discharge occurs based on a defined mixing time. The mixing time between the start of mixing and the discharge may be about 1 minute or longer, such as about 1 minute to 40 minutes, about 1 minute to 30 minutes, about 1 minute to 20 minutes, or 1 minute to 15 minutes, or 5 minutes to 30 minutes, or 5 minutes to 20 minutes, or 5 minutes to 15 minutes, or 1 minute to 12 minutes, 1 minute to 10 minutes, or 3 minutes to 30 minutes, or other times. Alternatively, for an intermittent sealed mixer, the top bolt lowering time can be used as a parameter for monitoring the intermittent (batch) mixing time (e.g., the time the mixer is operated when the top bolt is in its lowest position, such as a fully seated position, or with a top bolt offset as described herein). For example, the top bolt lowering time may range from 3 minutes to 30 minutes, 3 minutes to 20 minutes, 3 minutes to 10 minutes, 5 minutes to 30 minutes, 5 minutes to 20 minutes, 5 minutes to 10 minutes.
[0420] As an option, discharge occurs based on the dump or discharge temperature (mixer temperature). For example, the mixer can have a dump temperature in the range of 120°C-180°C, 120°C-190°C, 130°C-180°C, such as 140°C-180°C, 150°C-180°C, 130°C-170°C, 140°C-170°C, 150°C-170°C, or other temperatures within or outside these ranges.
[0421] Liquid content of the compound
[0422] The method further includes discharging the formed compound from the mixer. The discharged compound may have a liquid content of no more than 10% by weight based on the total weight of the compound, as summarized in the following equation:
[0423] Liquid content of the compound % = 100*[mass of liquid] / [mass of liquid + mass of dry compound]
[0424] In any method disclosed herein, the discharged composite may have a liquid content of no more than 10% by weight, based on the total weight of the composite, such as no more than 9% by weight, no more than 8% by weight, no more than 7% by weight, no more than 6% by weight, no more than 5% by weight, no more than 2% by weight, or no more than 1% by weight, based on the total weight of the composite. Based on the total weight of the composite discharged from the mixer at the end of the process, the amount may range from about 0.1% by weight to 10% by weight, or from about 0.5% by weight to 9% by weight, or from about 0.5% by weight to about 7% by weight. In any method disclosed herein, the liquid content (e.g., "water content") may be the measured weight % of the liquid present in the composite, based on the total weight of the composite.
[0425] In any of the methods disclosed herein, when the discharged composite may have a liquid content of 10% by weight or less, there may optionally be liquid (e.g., water) in the mixer that is not retained in the discharged composite. This excess liquid is not part of the composite and is not part of any liquid content calculated for the composite.
[0426] In any of the methods disclosed herein, the total liquid content (or total water content or total moisture content) of the material charged to the mixer is higher than the liquid content of the discharged composite at the end of the process. For example, the liquid content of the discharged composite may be 10%-99.9% (wt% vs wt%), 10%-95%, or 10%-50% lower than the liquid content of the material charged to the mixer.
[0427] Filler loading
[0428] In any of the methods disclosed herein, as part of the method, at the discharge step, the elastomer, when discharged from the mixer, has a filler loading (measured in parts per hundred parts of rubber, or phr) of at least 1 phr, at least 10 phr, at least 15 phr, at least 20 phr, at least 30 phr, at least 40 phr, and has a filler yield loss of no more than 10% on a dry weight basis. For example, the filler loading can range from 20 phr to 250 phr, 20 phr to 200 phr, 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 100 phr, 20 phr to 90 phr, 20 phr to 80 phr, 30 phr to 200 phr, 30 phr to 180 phr, 30 phr to 150 phr, 30 phr to 100 phr, 30 phr to 80 phr, 30 phr to 70 phr, 40 phr to 200 phr, 40 phr to 180 phr, 40 phr to 150 phr, 40 phr to 100 phr, 40 phr to 80 phr, 35 phr to 65 phr, or 30 phr to 55 phr. Using these loadings, the filler yield loss on a dry weight basis is no greater than 10%. As an option, other filler loadings and filler yield loss values are applicable and disclosed herein.Fillers include carbon black, silica, silicon-treated carbon black, and other fillers disclosed herein, and blends thereof.
[0429] In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is selected from carbon black, and coated and treated materials thereof. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silica. In certain embodiments, at least 50% of the filler (e.g., at least 75% or at least 90% of the filler) is silicon-treated carbon black.
[0430] As an example, the carbon black can be dispersed in the elastomer at a loading in the range of 30 phr-200 phr, 30 phr-70 phr, or 40 phr-65 phr, or 40 phr-60 phr. As a more specific example, where the elastomer is natural rubber alone or natural rubber with one or more other elastomers, and the filler is carbon black alone or carbon black with one or more other fillers (e.g., silica or silicon-treated carbon black), the carbon black can be dispersed in the natural rubber at a loading in the range of 30 phr-70 phr, or 40 phr-65 phr, or 40 phr-60 phr.
[0431] The amount of silica present in the formed elastomeric composite can be 20 phr-250 phr, 20 phr-200 phr, 20 phr-150 phr, 20 phr-100 phr, 30 phr-150 phr, 30 phr-100 phr, 25 phr-100 phr, 25 phr-80 phr, 35 phr-115 phr, 35 phr-100 phr, 40 phr-110 phr, 40 phr-100 phr, 40 phr-90 phr, 40 phr-80 phr, etc. The filler blend including silica can include 10 weight percent carbon black and / or silicon-treated carbon black.
[0432] The amount of silicon-treated carbon black present in the formed elastomeric composite may be from 20 phr to 250 phr, from 20 phr to 200 phr, from 30 phr to 150 phr, from 40 phr to 100 phr, or from 50 phr to 65 phr.
[0433] Other loadings, filler types, and blends are disclosed herein.
[0434] Packing yield loss
[0435] The filler yield loss is determined based on the theoretical maximum phr of the filler in the elastomer (assuming that all filler charged to the mixer is incorporated into the compound) minus the measured phr of the filler in the discharged compound. This measured amount can be obtained from thermogravimetric analysis (TGA). Therefore, the filler yield loss (%) is calculated as follows:
[0436]
[0437] Loose fillers present on the surface of the composite due to poor incorporation of fillers in the elastomer are included in the filler yield loss. As an option, the process of any method disclosed herein does not result in a significant loss of filler originally charged to the mixer. In any method disclosed herein, the filler yield loss may be no more than 10%, such as no more than 9% or no more than 8% or no more than 7% or no more than 6% or no more than 5% or no more than 4% or no more than 3% or no more than 2% or no more than 1%, such as a filler yield loss range of 0.1%-10%, 0.1%-5%, 0.1%-2%, 0.5%-10%, 0.5%-5%, 0.5%-2%, 1%-10%, 1%-5%, or 1%-2%.
[0438] Fill Factor
[0439] When mixing dry fillers with solid elastomers, typical practice is to maximize the packing factor to maximize the amount of compound produced. Packing factor (%) = (volume of material loaded into the mixer) / net mixer chamber volume. The net mixer chamber volume includes considerations of the mixer design, e.g., the volume of the rotor. The packing factor is often selected to ensure that the ejector pin is still in place by the end of mixing, and for dry mixing, a typical packing factor value is about 72%.
[0440] In any of the methods disclosed herein, at least the solid elastomer and the wet filler are loaded such that the mixing chamber of the mixer has a filling factor of about 25% to about 90% of the volume capacity (based on dry weight). In any of the methods disclosed herein, at least the solid elastomer and the wet filler are loaded such that the mixing chamber of the mixer has a filling factor of about 50% to about 80% of the volume capacity, for example, about 50% to about 72%, about 50% to about 70%, about 50% to about 68%, about 60% to about 75%, about 60% to about 72%, about 60% to about 70%, or about 60% to about 68% of the volume capacity.
[0441] As an option of any of the methods disclosed herein, the method can be carried out wherein a mixer (e.g., an internal mixer such as a batch mixer or other mixer) is charged with at least a solid elastomer and a wet filler so that the packing factor of the at least solid elastomer and the wet filler on a dry weight basis is not more than 72%, not more than 70%, or not more than 68%, or not more than 66%, for example, about 30%-72%, 40%-70%, 45%-70%, 30%-60%, 50-72%, 50-70%, 50-68%, 60-72%, 60-70%, 60-68%, 65-72%, 65-70%, 65-68%, or 40-60% or 50-60%, etc. A more specific example is to charge at least solid elastomer and wet filler into a mixer such that the filling factor is not greater than 68% and the solid elastomer includes at least 50% by weight of natural rubber.
[0442] During mixing with wet fillers, it has been observed that certain elastomers, such as natural rubber, swell. As mixing proceeds, the temperature of the mixture increases, thereby superheating the water introduced into the mixture. This causes swelling of the mixture, thereby increasing the total volume of the mixture. If the initial filling factor is too high, the swelling may be sufficient to suppress the top plug (also known as a floating weight), causing the top plug to be raised above its fully seated position. In this case, the portion of the mixture immediately below the top plug becomes partially separated from the main body of the mixture, thereby reducing its mixing effectiveness. In addition, this separated mixture may form a "plug" under the offset top plug, thereby inhibiting the release of steam from the mixer. Therefore, such a top plug offset can extend the batch cycle time and impair filler dispersion. If the top plug is raised in batch sequence when the plug is occurring (for example, to add 6PPD), excessive amounts of steam may be suddenly released, and safety issues may also be a consideration.
[0443] Thus, when the elastomer is swellable in the presence of a liquid capable of evaporation, such as natural rubber, the packing factor (by dry weight) of the wet filler and the solid elastomer including the natural rubber may be no greater than 70%, or no greater than 68%, no greater than 66%, for example, in the range of 60%-70%, 60%-68%, 60%-66%, or 65%-68%. The solid elastomer may include at least 50%, at least 75%, at least 90%, or at least 95% natural rubber. For example, the solid elastomer may be a blend of natural rubber and at least one additional elastomer, such as polybutadiene and / or styrene-butadiene rubber, or other elastomers as disclosed herein. The filler may be any filler disclosed herein, for example, carbon black, silicon-treated carbon black, and silica.
[0444] As an option, in such a method having a controlled fill factor of 72% or less, or 70% or less, or 68% or less, or in any method disclosed herein utilizing a batch mixer or similar type of mixer, the mixer may include a ram that is capable of vertically moving downward to a lowermost position in which the ram is disposed adjacent to one or more rotors in the mixer. During mixing, the mixer may be operated with a maximum ram deflection from the lowermost position being a distance of no more than 30% of the diameter of the one or more rotors. Alternatively, the distance may be no more than 25%, or no more than 20%, or no more than 15%, or no more than 10%, or no more than 5% of the diameter of the one or more rotors. As an option of any method disclosed herein, during the mixing step, the fill factor is optimized to minimize ram deflection.
[0445] In certain embodiments, the filling factor may be a function of one or more variables. For example, the filling factor may be determined based on the rotor type. For example, when using an intermittent mixer (e.g., a tangential mixer), the filling factor may be 72% or less for a double-ribbed rotor; 70% or less for a double-ribbed or quad-ribbed rotor; and 68% or less for a double-ribbed, quad-ribbed, or hex-ribbed rotor. In other embodiments, for example, when using a kneading mixer, the filling factor may be 60% or less.
[0446] In certain embodiments, the use of wet fillers may enable the use of higher tip speeds than in typical dry mixing processes. Such high tip speeds may increase the tendency to compress the ejector pin because they increase the average pressure applied to the ejector pin. As an option, the combination of lower fill factors disclosed herein with increased tip speeds may be desirable for commercial production. In the case of using higher fill factors typically used in the dry mixing industry, the associated problems that may ensue when mixing using wet fillers may make commercial production unfeasible. Therefore, in certain embodiments, fill factors disclosed herein, such as 70% or less, 68% or less, or 66% or less, may be used and higher tip speeds, such as a tip speed of 0.6 m / s for at least 50% of the mixing time, and other tip speeds disclosed herein may be used.
[0447] Time average release rate
[0448] As described herein, the present process provides operating conditions that balance longer mixing times (relative to dry mixing processes) with evaporation or removal of liquids in a reasonable amount of time. z Too low, the liquid can stay in the mixture longer than preferred, resulting in inefficient mixing. In another case, the liquid can evaporate or be removed too quickly, making the mixture similar to a dry blend and thus hindering the benefits associated with longer effective mixing time and sufficient energy input. In any method disclosed herein, the rate of liquid release (including, but not necessarily limited to, the rate at which the liquid evaporates from the composite during mixing) can be measured as the time-averaged release rate of the liquid per kg of the composite, and the rate can be 0.01-0.14kg / (minute kg) or 0.01-0.07kg / (min kg) or other rates lower or higher than this range. The release rate can be the total release rate of liquid removed by any means during mixing or can be the release rate caused only by evaporation. In the case of aqueous liquids, the evaporation rate can be considered as steam release or steam escape rate.
[0449] As an option, the time-averaged release rate (kg / kg.min) can be calculated by the following equation:
[0450] Time average release rate = total liquid removed / (release time x weight of complex)
[0451] in:
[0452] Composite weights were determined on a dry weight basis;
[0453] Total liquid removed (kg) = liquid in wet packing - liquid content in discharged composite;
[0454] Release time = time for the top bolt to be lowered (min) - time for rubber plasticization only (min).
[0455] As discussed herein, the ram down time is the time (period or amount of time) that the ram is operated at the lowest position.
[0456] It is believed that an optimized time-averaged release rate of the liquid (e.g., the time-averaged release rate of the evaporated liquid) can provide improved dispersion of the filler in the elastomer balanced with an appropriate mixing time. A release rate of less than 0.01 kg / (min·kg) can generally reflect (e.g., at a T of less than 65°C) z The release rate of the rubber compound may be greater than 0.15 kg / (min·kg) and / or a specific energy level of less than 1,500 kJ / kg and / or a tip speed of less than 0.5 m / s or less than 0.6 m / s) for a longer period of time to remove the liquid. A release rate greater than 0.15 kg / (min·kg) may reflect a shorter mixing time. Unoptimized time-averaged release rates may result in poor rubber properties or mixing conditions similar to dry mixing that may deteriorate the elastomer.
[0457] Energy efficiency
[0458] During mixing of at least the solid elastomer and the wet filler, mixing (via one or more mixing steps) includes applying energy (ER) to at least one rotor of the mixer, or one or more rotors thereof (e.g., at least two rotors, four rotors, etc.) at an energy efficiency ranging from 20% to 80%, wherein the energy efficiency is based on the following equation:
[0459] Energy efficiency = heat load / E R x 100%,
[0460] in:
[0461] - Heat load (kJ / kg) is the energy (kJ) required to remove liquid from 1 kg of composite with 100% efficiency
[0462] -Heat load is (evaporation heat) + (sensible heat)
[0463] - Heat of evaporation = liquid removed (kg) * latent heat of evaporation of liquid (2260 kJ / kg for water)
[0464] - Sensible heat = liquid removed (kg) * specific heat capacity of liquid (4.1855 kJ / kg / K for water) * (100 - ambient temperature °C)
[0465] - Amount of liquid removed (kg) = total liquid added to the mixer (kg) - liquid content of the discharged compound (kg).
[0466] Typically, the amount of liquid content at fill will be determined by the amount of liquid in the wet fill.
[0467] Energy efficiencies ranging from 20% to 80% are significantly greater than the energy efficiency of dry mixing processes (e.g., <5%). In certain embodiments, energy efficiencies may range from 30% to 80%, 40% to 80%, 50% to 80%, 30% to 70%, 40% to 70%, 50% to 70%, 30% to 60%, 40% to 60%, 50% to 60%, or 40% to 55%. It is believed that energy efficiencies greater than 80% are associated with inadequate mixing.
[0468] Other operating parameters to consider include the maximum pressure that can be used. Pressure affects the temperature of the filler and rubber mixture. If the mixer is a batch mixer with a ram, the pressure in the mixer chamber can be affected by controlling the pressure applied to the ram cylinder.
[0469] Multi-stage or multi-step mixing
[0470] Any method disclosed herein relates in part to a method for preparing a composite comprising at least two mixing steps or stages. These two (or more) mixing steps can be considered as multi-step or multi-stage mixing with a first mixing step or stage and at least a second mixing step or stage. One or more of the multi-stage mixing processes can be intermittent, continuous, semi-continuous, and combinations thereof.
[0471] For a multi-stage process, the method of preparing a composite comprises the steps of charging or introducing into a first mixer at least a) one or more solid elastomers and b) one or more fillers, wherein at least one filler or a portion of at least one filler is a wet filler as described herein (e.g., a wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler). The combination of the solid elastomer and the wet filler forms a mixture or composite during the mixing step (s) which can be considered as the first mixing step or stage. The method further comprises mixing the mixture in the first mixing step to the extent that at least a portion of the liquid is removed by evaporation or an evaporation process occurring during mixing. The first mixing step (in one or more mixing steps) or stage is performed using one or more of the processes described above, which form a composite, and it is understood that after the first mixing is completed, it is not necessary for the mixture discharged from the mixer after the first mixing step (e.g., the discharged mixture) to have a liquid content of no more than 10% by weight. In other words, where a multi-stage process is used, the mixture resulting from completing the first mix (or first mixing step) from the first mixer may have a liquid content greater than 10 wt %, but does have a reduced (in wt %) liquid content compared to the liquid content of the combined solid elastomer and wet filler at the beginning of the first mixing step.
[0472] The method then includes mixing or further mixing the mixture in at least a second mixing step or stage using the same mixer (i.e., the first mixer) and / or using a second mixer (one or more) different from the first mixer. The mixing using the second mixer can be such that the second mixer or second mixer is operated as follows: with a ram pressure of 5 psi or less and / or the ram is raised to at least 75% of the ram maximum level (e.g., at least 85%, at least 90%, at least 95%, or at least 99% or 100% of the ram maximum level), and / or the ram is operated in a floating mode, and / or the ram is positioned so that it does not substantially contact the mixture; and / or there is no ram mixer; and / or the filling factor of the mixture ranges from 25% to 70%. The method then includes discharging the composite from the last mixer used, the composite being formed such that the composite has a liquid content of no more than 10% by weight based on the total weight of the composite.
[0473] After the first mixing, the further mixing step(s) for the multi-stage mixing can utilize any one or more of the mixing procedures or parameters or steps utilized in the first mixing step as described herein. Thus, when performing the further mixing step or stage, the same or different mixer design and / or the same or different operating parameters as the first mixer can be used in the further mixing stage. The mixers and their options previously described for the first mixing step and / or the operating parameters previously described for the mixing step may optionally be used in this further or second mixing step (e.g., a mixing step as described herein that includes a tip speed of at least 0.5 m / s for at least 50% of the time or at least 0.6 m / s for at least 50% of the time, and / or a resulting specific energy of at least 1100, at least 1400, at least 1500 kJ / kg of composite, and / or mixing to an indicated temperature of at least 120° C., and / or a filling factor of no more than 7%, and / or a T of 40° C. or more, 50° C. or more, 60° C. or more, or 65° C. or more). Z , and / or evaporation rate and / or number of rotors, and / or rotor type, and / or temperature control means, and / or applying an average specific power of at least 2.5 kW / kg during the mixing time, and / or continuous mixing, etc.). For the further mixing step (one or more) as described above, any one or more or all of these options can be used. The second or more mixing steps can utilize different process parameters from those used in the first mixing step. Any combination of these mixing parameters can be used in multi-stage mixing. Therefore, any method disclosed herein further includes a method for preparing a composite by multi-stage mixing, wherein one or more of the following parameters can be utilized in at least one of the mixing steps, at least two of the mixing steps, or all of the mixing steps,
[0474] i. the at least one temperature control means is set to a temperature Tz of 65°C or higher during the mixing; and / or
[0475] ii. during said mixing, the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or
[0476] iii. applying an average specific power of at least 2.5 kW / kg during the mixing time; and / or
[0477] iv. Filling (a) comprises filling a mixer with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, wherein the packing factor of the at least solid elastomer and the wet filler on a dry weight basis is not greater than 68%; and / or
[0478] v. Mixing is continuous; and / or
[0479] vi. optionally adding at least one additive selected from antidegradants and coupling agents during said filling (a) or said mixing (b), and optionally adding one or more rubber chemicals after the mixer reaches a temperature of 120° C. or higher; and / or
[0480] vii. said filling (a) and said mixing (b) before the mixer reaches the indicated temperature are carried out in the substantial absence of said one or more rubber chemicals; and / or
[0481] viii. The mixer has a packing factor, and the packing factor of the at least solid elastomer and wet filler is no greater than 72%, no greater than 70%, or no greater than 68% on a dry weight basis.
[0482] In such a multi-stage mixing process, at least one of the above parameters may be used in the first mixing step, at least two of the above parameters may be used in the first mixing step, or at least three of the above parameters may be used in the first mixing step, or at least four of the above parameters may be used in the first mixing step, or all of the above parameters may be used in the first mixing step. Also, in such a multi-stage mixing process, at least one of the above parameters may be used in the second or further mixing step(s), at least two of the above parameters may be used in the second or further mixing step(s), or at least three of the above parameters may be used in the second or further mixing step(s), or at least four of the above parameters may be used in the second or further mixing step(s), or all of the above parameters may be used in the second or further mixing step(s). The parameters used in the first mixing step or stage may be the same or different from the parameters used in the second or further mixing step(s). The mixer used in the first mixing step may be the same or different from the second or further mixing step(s).
[0483] Thus, for a multi-stage mixing process, in at least one option, the first mixer used in the first mixing step is used in a further or second mixing step. Before the first mixer or other mixer is used in the second mixing step, as a further option, there may be a rest time, wherein the compound formed by the first mixing is left to stand or cool or both in the first mixer or in another container or location (e.g., mixing, stopping, and then further mixing). For example, the rest time may be such that the mixture obtains a material temperature of less than 180°C before the further mixing step begins (e.g., the discharged mixture may have a material temperature in the range of about 100°C to about 180°C, about 70°C to 179°C, or about 100°C to about 170°C, or about 120°C to about 160°C). Alternatively, the rest time before the further mixing step begins may be about 1 minute to 60 minutes or more. The material temperature may be obtained by many methods known in the art, such as by inserting a thermocouple or other temperature measuring device into the mixture or compound.
[0484] In a multi-stage process, the second mixing step (second stage mixing) may include charging the mixer with other components in addition to the mixture discharged from the first mixing step. For example, the method may include charging an additional filler, such as a dry filler, a wet filler (e.g., having a liquid present in an amount of at least 15% by weight), or a blend thereof, before or during the second mixing step. The additional filler may be the same as or different from the filler already present in the mixture. For example, the mixture discharged from the first mixer may be considered a masterbatch, all or a portion of which is combined with an additional filler.
[0485] For a multi-stage mixing process, in at least one option, at least a second mixer is used in the further mixing step(s). When this option is used, the second mixer may have the same or a different design as the first mixer, and / or may have the same or one or more different operating parameters as the first mixer. With respect to the first mixer and second mixer options, specific examples are provided below that are not intended to be limiting.
[0486] For example, the first mixer may be a tangential mixer or an intermeshing mixer, and the second mixer may be a tangential mixer, an intermeshing mixer, an extruder, a kneader, or a roll mill.
[0487] For example, the first mixer may be an internal mixer and the second mixer may be a kneader, a single screw extruder, a twin screw extruder, a multi-screw extruder, a continuous compounder, or a roll mill.
[0488] For example, the first mixer may be a first tangential mixer and the second mixer may be a second (different) tangential mixer.
[0489] For example, a first mixer may be operated at a ram pressure greater than 0 psi, and a second mixer at a ram pressure of 5 psi or less, such as 3 psi or less, or even at 0 psi. This option may also be utilized when the second mixing step utilizes the same mixer as the first mixing step. For example, the first mixer is operated with a ram, and the second mixer is operated without a ram.
[0490] For example, a second mixer is utilized and operated at a mixture fill factor ranging from 25%-70%, 25%-60%, 25%-50%, 30%-50% by dry weight, or other fill factor amounts described herein.
[0491] When a second mixer is utilized, any of the methods disclosed herein may include the additional step of discharging the mixture from the first mixer into the second mixer for the second mixing step. As an option, the discharge may occur directly into the second mixer, or the discharge may occur such that the mixture is discharged into a holding (retention) container (e.g., storage bin, rack) and then transferred or conveyed to the second mixer (e.g., using a conveyor or other feeding device).
[0492] As a further option, a third mixer or more may be utilized in any of the methods disclosed herein. When this option is used, the third or more mixers may have the same or different designs as the first mixer and / or the second mixer, and / or may have the same or one or more different operating parameters as the first mixer and / or the second mixer.
[0493] In any of the multi-stage processes disclosed herein, the final discharged composite (e.g., the composite discharged after the second or third, or more, mixing steps) may have a liquid content of no more than 5%, more than 4%, no more than 3%, no more than 2%, or no more than 1% by weight based on the total weight of the composite. This amount may range from 0.1% to 5%, 0.1% to 4%, 0.1% to 3%, 0.1% to 2%, 0.1% to 1%, 0.5% to 5%, 0.5% to 4%, 0.5% to 3%, 0.5% to 2%, or 0.5% to 1% by weight based on the total weight of the composite discharged from the mixer at the end of the process.
[0494] In any multi-stage process disclosed herein, the total liquid content (or total water content or total moisture content) of the material loaded into the mixer at the beginning of the process is higher than the liquid content of the compound when the first mixing step is stopped. For example, the liquid content of the mixture when the first mixing step is stopped may be 10%-50% lower (weight % vs weight %) than when the first mixing step was started, or may be 25% lower or more, or 10% lower or more.
[0495] Further, in any of the multi-stage processes disclosed herein, the total liquid content (or total water content or total moisture content) of the mixture at the end of the first mixing step is higher than the liquid content of the final composite discharged at the end of the process (after the last mixing step). For example, the liquid content of the discharged composite may be 10%-50% lower (wt% vs wt%) than after the first mixing step is completed, or may be 25% or more, or 10% or more lower.
[0496] In any of the multi-stage processes disclosed herein, upon discharge from the final mixer, the temperature of the composite (e.g., dump temperature) may range from 130° C. to 180° C., such as 140° C. to 170° C. Alternatively, the multi-stage process may be monitored by: material temperature, or probe temperature, which is the temperature of the mixture or composite recorded or measured immediately upon discharge (within 5 minutes, within 3 minutes, or within 60 seconds) and may be considered the average temperature of the composite material.
[0497] In a multi-stage process, examples of preferred components or parameters include, but are not limited to, wherein the filler comprises carbon black and the elastomer comprises natural rubber, and / or the filler comprises silica and the elastomer comprises natural rubber, and / or the discharged mixture from the first mixing has a material temperature of 100° C.-140° C., 110° C.-140° C., 130° C.-150° C., 120° C.-150° C., or 130° C.-140° C., and / or the resulting total specific energy from mixing in the first mixer (first mixing) ranges from 1,000 kJ / kg to 2,500 kJ / kg. For any multi-stage process disclosed herein, any one or more of these preferred components or parameters may be used in combination.
[0498] Other multi-stage processes include methods of making a composite comprising:
[0499] (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; and
[0500] (b) mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation.
[0501] The tip velocity may have other values as disclosed herein.
[0502] As an option, instead of controlling the tip speed, the process may utilize the following: Applying a suitable average specific power that allows a reasonable ram down time for mixing in the first mixer. Thus, the method may include:
[0503] (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; and
[0504] (b) mixing at least the solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means and an average specific power of at least 2.5 kW / kg is applied during the ram down time, and at least a portion of the liquid is removed from the mixture by evaporation.
[0505] For example, the method may include applying an average specific power of at least 3 kW / kg during the time when the top bolt is down, at least 3.5 kW / kg during the time when the top bolt is down, at least 4 kW / kg during the time when the top bolt is down, at least 4.5 kW / kg during the time when the top bolt is down, or at least 5 kW / kg during the time when the top bolt is down, for example, the time when the top bolt is down ranges from 2.5-10 kW / kg, 3-10 kW / kg, 3.5-10 kW / kg, 3-10 kW / kg, 4.5-10 kW / kg, 5-10 kW / kg, 2.5-8 kW / kg, 3-8 kW / kg, 3.5-8 kW / kg, 3-8 kW / kg, 4.5-8 kW / kg, or 5-8 kW / kg. The time when the top bolt is down may be 15 minutes or less, 12 minutes or less, 10 minutes or less, 8 minutes or less, or 6 minutes or less.
[0506] Where either option, tip speed or specific power, is used, the method may further comprise:
[0507] (c) discharging a mixture from the first mixer, the mixture comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the mixture has a liquid content reduced to an amount less than the liquid content at the beginning of step (b), and wherein the mixture has a material temperature in the range of 100° C. to 180° C.;
[0508] (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions:
[0509] (i) A bolt pressure of 5 psi or less;
[0510] (ii) the jack is raised to at least 75% of its maximum level;
[0511] (iii) the jack is operated in floating mode;
[0512] (iv) the top pin is positioned so that it does not substantially contact the mixture;
[0513] (v) the mixer is jackless; and / or
[0514] (vi) the fill factor of the mixture is in the range of 25% to 70%; and
[0515] (e) discharging a composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
[0516] The multi-stage method provides additional parameters for dispersing fillers in elastomers. Control of the batch (intermittent) mixing time (representing the time when the top bolt is lowered) in the first mixer allows the filler to be dispersed in the elastomer to a certain extent, followed by mixing in the second mixer under conditions that minimize the significant or any degradation of the solid elastomer, such as natural rubber. Therefore, one or more steps of mixing in the first mixer are accompanied by evaporation of at least some of the liquid, so that the mixture discharged from the first mixer has a liquid content that is reduced to a liquid content less than the liquid content at the beginning of step (b), such as the liquid present in the wet filler. The liquid content can be reduced by 50% by weight, 60% by weight, 70% by weight, or more. The amount of liquid content left in the discharged mixer can depend on the filler type, elastomer type, filler loading, etc. In certain embodiments, it is desirable to have a certain amount of moisture left in the mixture to utilize the wet mixing process and its benefits in the mixing that occurs in the second mixer. Alternatively, when other fillers and / or elastomer types are used, it is desirable to remove most of the liquid during one or more mixing steps in the first mixer. Thus, the discharged mixture may have a liquid content (depending in part on the liquid content of the wet filler) ranging from 0.5% to 20% by weight, relative to the weight of the mixture, for example, 0.5% to 17%, 0.5% to 15%, 0.5% to 12%, 0.5% to 10%, 0.5% to 7%, 0.5% to 5%, 0.5% to 3%, 0.5% to 2%, 1% to 20%, 1% to 17%, 1% to 15%, 1% to 12%, 1% to 10%, 1%-7%, 1%-5%, 1%-3%, 1%-2%, 2%-20%, 2%-17%, 2%-15%, 2%-12%, 2%-10%, 2%-7%, 2%-5%, 2%-3%, 3%-20%, 3%-17%, 3%-15%, 3%-12%, 3%-10%, 3%-7%, 3%-5%, 5%-20%, 5%-17%, 5%-15%, 5%-12%, 5%-10%, or 5%-7%.
[0517] The material temperature (also known as the probe temperature) of the mixture at the time of discharge in (c) can be measured, for example, by inserting a thermocouple or other temperature measuring device into the mixture or composite. The material temperature can be a criterion for the moisture content, because generally, the drier the mixture discharged from the first mixer will have a higher material temperature. Discharging the mixture when the material temperature is within a certain range (for example, a range of 100°C-180°C) ensures that a certain amount of moisture remains in the mixture. Since it may not always be possible to obtain the material temperature of the mixture during the mixing process, the temperature of the mixer can be monitored. The relevant mixer temperature can be obtained, for example, by inserting a thermocouple into the chamber. Such a mixer temperature can be calibrated to reasonably approximate the material temperature or be associated with the material temperature. For example, the mixer temperature can differ from the material temperature by as much as 40°C or less, 30°C or less, 20°C or less, 10°C or less, or 5°C or less. The difference between the mixer temperature and the material temperature may not be very important, as long as the difference is reasonably consistent for each mixing.
[0518] For example, the material temperature of the mixture may range from 100° C. to 150° C., for example, 100° C. to 145° C., 100° C. to 140° C., 110° C. to 150° C., 110° C. to 145° C., 110° C. to 140° C., 120° C. to 150° C., 120° C. to 145° C., 120° C. to 120° C., 125° C. to 150° C., 125° C. to 145° C., 125° C. to 140° C., 130° C. to 150° C., 130° C. to 145° C., 130° C. to 140° C., 135° C. to 150° C., 135° C. to 145° C., or 135° C. to 140° C. In certain embodiments, the material temperature may be suitable when the elastomer is natural rubber.
[0519] For synthetic elastomers such as butadiene rubber or styrene-butadiene rubber, the material temperature of the solid elastomer including such synthetic elastomer may range from 100°C to 170°C, 110°C to 170°C, 120°C to 170°C, 130°C to 170°C, 140°C to 170°C, or 150°C to 170°C.
[0520] As an option, the filler comprises at least one material selected from the following: carbon black, and its coated and treated materials (for example, at least 50% by weight, at least 75% by weight, or at least 90% by weight of the filler is selected from carbon black and silicon-treated carbon black). The wet filler may have a liquid present in an amount of at least 20% by weight, at least 30% by weight, in a range of 40%-65% by weight. In step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 60°C-110°C, such as 65°C or higher, in the range of 65°C-100°C, in the range of 75°C-90°C z.
[0521] As an option, at least 50% (at least 75%, or at least 90%) of the filler is silica. The loading may further comprise loading a coupling agent into the mixer, for example, together with at least a portion (or a first portion) of the wet filler. In step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C-100°C, or in the range of 40°C-75°C, or in the range of 50°C-90°C, or in the range of 50°C-75°C. z The wet filler may have the liquid present in an amount of at least 20% by weight or in an amount ranging from 20% to 65% by weight.
[0522] For the first mixer, as an option, the mixing time is the time when the top plug is lowered, for example, the time when the top plug is lowered is no more than 15 minutes, no more than 10 minutes, no more than 8 minutes, for example, in the range of 3 minutes to 15 minutes, or 3 minutes to 10 minutes, or 5 minutes to 10 minutes. Other ranges are disclosed herein. As another option, for the second mixer, the mixing time is the period between the start of mixing and the discharge.
[0523] The total specific energy of the mixing process in the first mixer can be similar to those previously described in this article, or can be different, for example, to ensure a shorter batch time. In addition, the type of filler can affect the total specific energy. As an option, the mixing in the first mixer, i.e., the mixing in (b), has a total specific energy range of 1000 kJ / kg-2500 kJ / kg.
[0524] For mixing in the second mixer, it is desirable to operate the mixing under conditions that will not degrade the elastomer. Under typical mixing conditions, after the material is loaded into the mixer chamber, the top bolt is pushed down to its fully seated position, thereby applying pressure to the material during the mixing process. During mixing in the second mixer, it is desirable that the pressure is relieved, which can occur under one or more of the following conditions. (i) For example, the top bolt can be in place, but substantially no pressure is applied to the top bolt, for example, 5 psi or less pressure is applied to the top bolt. (ii) The top bolt is raised to at least 75% of its highest level. Some mixers allow the top bolt to be positioned at a certain height. The top bolt in the fully seated position is at 0% of its highest level, in contrast to the top bolt raised to its highest level or fully open position, which is the typical position of the top bolt when the material is loaded into the mixer. A ram positioned at a height of at least 75% of its highest level, for example, raised to at least 80%, at least 85%, at least 90%, at least 95%, or fully raised to its highest level (100%), ensures minimum contact between the ram and the elastomer loaded into the mixer. (iii) Certain rams may operate as floating weights, for example in a floating mode, when no pressure is applied to the mixing chamber. When the ram may contact the elastomer, the pressure applied is minimal (very small). (iv) The ram is positioned so that it does not substantially contact the mixture. If the contents have a low fill factor, for example, as low as 25%, it may not be necessary to position the ram height to at least 75% of its highest level. The ram may be positioned at a height such that it does not substantially contact the mixture, for example, no more than 10% of the surface of the ram (by area) contacts the mixture, for example, no more than 5% of the surface of the ram, or 0% of the surface of the ram does not contact the mixture. (v) Certain mixers are ramless, that is, do not contain a ram. Examples of mixers without ejector pins are models IM550ET, IM1000ET from Harburg Freudenberger Maschinenbau GmbH (HF). (vi) The filling factor of the mixture, based on dry weight, ranges from 25% to 70%, for example, 25% to 60%, 25% to 55%, 25% to 50%, 25% to 45%, 25% to 40%, 30% to 70%, 30% to 60%, 30% to 55%, 30% to 50%, 30% to 45%, 30% to 40%, 35% to 70%, 35% to 60%, 35% to 55%, 35% to 50%, 35% to 45%, or 35% to 40%. By controlling the filling factor, it is not necessary to manipulate the ejector pin operation or position.
[0525] Once again, in order to minimize degradation of the elastomer, the material temperature of the final compound discharged from the second mixer (e.g., the compound discharged from step (e)) can also be monitored. Such material temperatures can be similar to those described previously for the mixture discharged from the first mixer.
[0526] The mixture discharged from (c), although an intermediate in a multi-stage or multi-step process, can also be considered a composite. In some cases, for a given composition (e.g., elastomer type, filler type, filler loading, and optionally, compounding and curing agents), the vulcanizate formed from the mixture in step (c) can have certain rubber properties that are improved relative to a vulcanizate prepared from a composite obtained from a dry blending process. Such vulcanizates are discussed in more detail below.
[0527] It is understood that, as discussed herein, additional mixers or mixing steps may be used. For example, after the composite is discharged from the second mixer, the composite may undergo additional plastication (eg, by mixing in the first or second mixer, or the third mixer).
[0528] Continuous mixing
[0529] As an option, the process is a continuous mixing process in which at least a solid elastomer and a wet filler (e.g., wet carbon black pellets) are mixed in a continuous mixer. The continuous mixer can allow control of the feed rate of the solid elastomer, wet filler, and other components, and / or control of water evaporation. Such control can in turn lead to a process that is easily automated.
[0530] For example, a method of preparing the composite includes:
[0531] (a) charging a continuous stream of at least a solid elastomer and a granulated wet filler into an input end of a continuous mixer, wherein the wet filler comprises a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler;
[0532] (b) conveying the solid elastomer and the wet filler along the length of a continuous mixer, wherein during the conveying, mixing occurs and at least a portion of the liquid is removed by evaporation; and
[0533] (c) discharging a composite from a discharge end of the continuous mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 10 weight percent based on the total weight of the composite.
[0534] The at least one solid elastomer and wet filler can be fed to a continuous mixer using mechanisms known in the art such as conveyors, hoppers, screw feeders, and combinations thereof. For example, the filler can be fed into a hopper, which is then fed into a screw feeder and ultimately fed to an entry port at one end of an elongated chamber of the mixer. The solid elastomer can be provided as a mass, strip, pellet, or other solid form and fed to the mixer via a conveyor. Therefore, a "continuous flow" of loaded elastomer does not necessarily require a single continuous length of polymer, as long as the loading can be measured as a rate of elastomer or filler per unit time.
[0535] The continuous mixer may have, for example, an elongated chamber. As an option, the solid elastomer, wet filler, and / or a mixture comprising a solid elastomer and a wet filler are continuously conveyed or continuously transported along the length of the continuous mixer. For example, the material is continuously conveyed from the input end of the elongated chamber and along the length of the chamber until the material contacts one or more rotors positioned axially in the elongated chamber. The mixture may branch from a path along the length of the mixer. However, the net path of the mixture is along the length of the mixer. The material may be conveyed through the one or more rotors (whereby mixing occurs) and subsequently discharged from the discharge end. An example of such a mixer is a continuous mixer, for example, the FCM manufactured by Farrel-Pomini. TM Farrel continuous mixer (mixer, mixer). Other continuous mixers include Unimix continuous mixer and MVX (mixing, venting, extrusion) machine (from Farrel Pomini Corporation of Ansonia, CT, USA), long continuous mixer (from Pomini, Inc.), Pomini continuous mixer, twin rotor co-rotating kneading extruder, twin rotor counter-rotating non-kneading extruder, continuous compounding extruder, twin shaft grinding extruder (produced by Kobe Steel, Ltd.), and Kobe continuous mixer.
[0536] The continuous mixer can be, for example, an extruder having a rotatable screw, such as a twin-screw extruder. The rotatable screw can simultaneously convey and mix the solid elastomer, the wet filler, and / or a mixture comprising the solid elastomer and the wet filler along the chamber toward the discharge end.
[0537] As an additional option, a continuous mixer, such as a twin-screw extruder or other mixer, may have multiple zones. The zones may be defined based on temperature. For example, upon initial entry into the continuous mixer, at least the solid elastomer and filler may be mixed in the first zone at a temperature where little or no evaporation occurs. As an option, the first zone may operate at a temperature in the range of 100°C-140°C. The first zone may have a constant temperature range throughout the first zone or may increase in temperature as the elastomer and filler mixture passes through the zone. The second zone downstream of the first zone may be a water evaporation zone, in which the mixture experiences a higher temperature and / or reduced pressure to reduce the water content. Such a liquid (e.g., water) evaporation zone (one or more), also referred to as a steam stripping zone (one or more), may be commercially available for screw extruders and may include one or more pumping systems and / or one or more heating systems, either or both of which may promote the evaporation of the liquid. The steam stripping zone may include one or more vents to promote the removal of liquid vapor. A rotatable screw may be present in the continuous mixer to transport the mixture through each zone.
[0538] The temperature of each zone can be controlled as described herein, for example, as described for Tz.
[0539] One or more zones may be provided downstream of the water evaporation zone that allow for the addition of desired amounts of antioxidants, rubber chemicals, and / or curing agents (eg, addition zones) and / or allow for cooling (eg, one or more cooling zones).
[0540] Examples of suitable twin-screw extruders have been described in patent publications WO 2018 / 219630, WO 2018 / 219631, and WO 2020 / 001823, the disclosures of which are incorporated herein by reference. For example, WO 2018 / 219630 describes an extruder that can be used as a continuous mixer as part of a continuous process for drying a coagulated wet masterbatch. The extruder includes 11 zones, the first 5 of which are mixing zones and the 6th is a water evaporation (water stripping) zone capable of removing substantially all of the water content from the mixture.
[0541] The continuous compounding process may further include a press, a roll, an extruder, or the like to receive the dried compound and form the resulting compound into a sheet, a strip, or the like.
[0542] As disclosed herein, "continuous" with respect to the process or method or any step relates to the operation of a process or method (or a segment or part thereof) in which the step or action occurs without any interruption or stoppage (which occurs in an intermittent processing method). A 'continuous process' or 'continuous method' may relate to a process or method such that a compound and / or a vulcanized product and / or a precursor to a compound is produced in a continuous operation without forming an intermediate product for later use. A 'continuous process' or 'continuous method' may be a situation in which a continuous flow or input of raw materials occurs such that the processing of the raw materials is continuous and the production of the resulting material occurs on a continuous basis without any interruption other than maintenance and normal stops in production (e.g., end of shift, end of production batch, etc.).
[0543] As another option, the wet filler and the solid elastomer may be combined (e.g., as a pre-blend) prior to continuous mixing to simplify loading of the materials into the continuous mixer. For example, the wet filler and the solid elastomer may be combined in a batch process (e.g., in an enclosed mixer) prior to loading into the continuous mixer. This entire process using a pre-blend or prior mixing step may be considered a semi-continuous process; however, the step of mixing the wet filler and the solid elastomer and removing at least a portion of the liquid by evaporation is performed in a continuous mixer and is a continuous process. The compound discharged from the continuous mixer may be further processed with a post-processing step as disclosed herein, or further plasticized or mixed in a subsequent mixer, whether intermittent or continuous.
[0544] As an option, the wet filler is loaded in pellet form, which can facilitate continuous loading. For example, a pelletized wet filler can minimize filler yield loss. The pelletized wet filler can be any pelletized filler as described herein, for example, carbon black, silicon-treated carbon black, silica, and blends thereof.
[0545] Integrated Manufacturing
[0546] As an option, any one of the methods disclosed herein is suitable for implementing as a unit operation in a multi-unit manufacturing plant, such as for the manufacture of fillers, elastomers and / or elastomer compounds, vulcanized products and rubber products, or a combination thereof. With regard to fillers, it is necessary to optimize the filler manufacturing process with the following: an intermediate step of forming a wet filler, and a subsequent drying step of producing dry granules with low dust and good disposal. These steps often require complicated and expensive drying equipment to produce granules, which are easy to transport, but are difficult to be dispersed in rubber. An integrated plant option may be feasible, wherein manufacturing fillers such as carbon black or silicon dioxide or any filler described herein and combinations thereof, and / or wherein the wet filler is a filler comprising process water or other liquids from a process for the manufacture of fillers, such as, from carbon black pellets that have never been dried or silicon dioxide that has never been dried.
[0547] In one integrated manufacturing option, when carbon black filler and / or silicon-treated carbon black filler is manufactured by a furnace process (e.g., a carbon black manufacturing facility), water is used to densify the fluffy carbon black by wet pelletizing the fluff, resulting in the produced carbon black including water. Typically, the wet carbon black produced is conveyed to a dryer where it is dried and then packaged and shipped to reduce dust and minimize costs and disposal issues associated with the transportation and storage of wet, low-density fluffy carbon black particulate materials. Using an integrated manufacturing process, the produced carbon black that has never been dried can be conveyed directly to a mixer as a wet filler for mixing with a solid elastomer in the mixing process described herein. In a multi-stage or step compounding process, a composite made from such never-dried carbon black may undergo one or more additional integrated unit operations, including, but not limited to, compounding with or without the addition of materials, such as a variety of the same or different elastomers and fillers, and / or oils, resins, polymers and other typical rubber chemicals and additives; further mixing or processing, curing to form a vulcanizate, and fabrication into rubber articles.
[0548] In another integrated manufacturing option, when the silica filler is manufactured by a precipitation process (e.g., a precipitated silica manufacturing facility), precipitated silica is typically produced by acidifying a silicate solution, which results in polymerization, nucleation, and growth of silica particles in an aqueous medium. The growing particles may collide, resulting in aggregation, which may be consolidated by further deposition of silica on the particle surface. The final size, surface area, and structure of the particles are controlled by controlling the silicate concentration, temperature, pH, and metal ion content. At the end of the particle formation process, an aqueous slurry of particles is obtained. The slurry is subjected to solid-liquid separation, which typically includes filtration, for example, by a filter press, a belt filter, or a vacuum filter. The filtered particles are then washed to remove salts and other soluble materials, and further filtered to obtain a filter cake. The filter cake typically contains 60-90% water and 10-40% silica by weight, based on the total weight of the filter cake. A typical production process is described in U.S. Pat. No. 7,250,463, which is fully incorporated herein by reference.
[0549] Conventionally, the wet cake is dried relatively slowly in an oven or rotary dryer. The silica produced in this way is generally considered difficult to disperse in rubber. An alternative drying process involves rapid heating to high temperatures for a short period of time (e.g., in a spray dryer). The precipitated silica produced with this alternative drying process generally imparts much better dispersibility in rubber. It is believed that during conventional drying, the combination of high capillary forces exerted by a thin layer of water and chemical reactions between silanol groups on adjacent particles results in tight agglomerates with strong bonds (bonds) between particles. The most significant chemical reaction is condensation, which results in siloxane bonds. The reaction is accelerated by heat and by the removal of water. The strong bonds formed between particles cannot be easily broken during rubber mixing and therefore, dispersion is often poor. During the rapid drying process, the residence time of the particles at high temperatures is much shorter, thereby providing less time for the particles to rearrange or compact and providing less condensation reactions. This results in a lower number of bonds or strong contacts between the silica particles, and therefore better rubber dispersion. However, it is not believed that silica particle-particle bonding is completely eliminated during the flash drying process, but only reduced relative to conventional processes.
[0550] It can be beneficial to use never-dried silica (e.g., slurry or cake) in an integrated manufacturing option and thus avoid or reduce the conventional silica drying process and incorporation of silica wet filler into solid elastomers. Advantages of such a multi-unit manufacturing operation include those listed herein, as well as obtaining higher quality silica-elastomer composites, streamlining of composite production from never-dried silica, simplified manufacturing processes, and significant cost savings.
[0551] For such multi-unit, integrated manufacturing operation, filler that has never been dried can be manufactured and it can be used in elastomer mixing operation immediately or within a few hours or days after manufacturing. Filler that has never been dried can be transported to elastomer mixing operation by conveyor line, storage box, track, truck or other means. Filler that has never been dried can be in cake or paste, fluidized state or be in granulated form. For such process, filler can be manufactured in filler factory, then transported or transmitted to adjacent elastomer factory, synthetic elastomer material in elastomer factory, purified, blended or otherwise processed into solid elastomer desired for one or more processes of this integrated manufacturing option as described herein and as an option, elastomer factory can further take the formed compound and carry out further steps, including, but not limited to, preparing vulcanized product and forming tire or one or more tire parts or other products including this vulcanized product or compound.
[0552] Since the integrated manufacturing process utilizes wet fillers, the ability to use never dried fillers such as never dried carbon black or never dried silica or other never dried fibers, particulates or elastomeric reinforcement materials, and combinations thereof, can potentially result in more efficient operations and can allow for turnkey operations. In such an integrated process as described herein, it is possible to use any never dried filler.
[0553] An example of a method utilizing an integrated manufacturing operation may involve manufacturing a filler in a filler manufacturing facility by a process wherein the final product as a wet filler includes a filler and a liquid present in an amount of at least 15 weight percent based on the total weight of the wet filler; conveying the wet filler to at least one mixer; charging at least a solid elastomer and the wet filler to the at least one mixer, wherein the at least one mixer has at least one temperature control means; mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of the mixing steps, conducting the mixing at a mixer temperature controlled by at least one temperature control means and removing at least a portion of the liquid from the mixture by evaporation; and discharging a composite from the at least one mixer, the composite comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the filler yield loss is no greater than 10%, wherein the composite has a liquid content of no greater than 20 weight percent based on the total weight of the composite.
[0554] With respect to the integrated manufacturing operation, the method may further include any one or more of the following embodiments: the wet filler is a filler that has never been dried; the filler manufacturing facility is a carbon black manufacturing facility, and the wet filler is a carbon black that has never been dried; the filler manufacturing facility is a precipitated silica manufacturing facility, and the wet filler is a precipitated silica that has never been dried; the filler manufacturing facility is a silicon-treated carbon black manufacturing facility; further comprising preparing a vulcanizate including an elastomeric compound, and optionally forming an article including the vulcanizate or the elastomeric compound;
[0555] With respect to the integrated manufacturing operation, the method may further include any one or more of the following parameters during the method: during the mixing, the at least one temperature control means is set to a temperature Tz of 65°C or higher; and / or during the mixing, the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time; and / or the mixer is charged with at least a solid elastomer and a wet filler, the solid elastomer comprising at least 50% by weight of natural rubber, wherein the filling factor of the at least solid elastomer and the wet filler on a dry weight basis is not greater than 68%; and / or the mixing is carried out at a mixer temperature controlled by at least one temperature control means and an average specific power of at least 2.5 kW / kg is applied during the mixing time; and / or the mixing is a continuous mixing step and the loading comprises loading a continuous flow of at least a solid elastomer and a wet filler into a continuous mixer; and / or a second a mixing mill to obtain a composite, wherein the second mixer is operated under at least one of the following conditions: (i) a ram pressure of 5 psi or less; (ii) the ram is raised to at least 75% of its highest level; (iii) the ram is operated in a floating mode; (iv) the ram is positioned so that it does not substantially contact the mixture; (v) the mixer is ram-free; and (vi) the filling factor of the mixture ranges from 25% to 70%; and / or the one or more rotors are operated at a tip speed of at least 0.5 m / s for at least 50% of the mixing time, resulting in a total specific energy of at least 1500 kJ / kg of composite, and wherein the wet filler is a wet granular filler; and / or optionally at least one additive selected from an antidegradant and a coupling agent is added during said filling (a) or said mixing (b), and optionally one or more rubber chemicals are added after the mixer reaches a temperature of 120° C. or higher.
[0556] The previous descriptions of the amount, type, and other parameters of filler apply equally here (eg, various examples and ranges for loading amounts were provided previously and will apply here as well).
[0557] Filling Type
[0558] The wet filler used in any of the methods disclosed herein can be a solid material in the form of a powder, paste, granules or cake, such as a solid bulk material. In the method, the wet filler can be dispersed in the elastomer at a loading ranging from 1 phr to 100 phr on a dry weight basis, or a loading ranging from 20 phr to 250 phr, 20 phr to 200 phr, for example, 20 phr to 180 phr, 20 phr to 150 phr, 20 phr to 120 phr, or 20 phr to 100 phr, as well as other ranges disclosed herein.
[0559] In any of the methods disclosed herein, a wet filler such as wet carbon black, wet silica, or wet silicon-treated carbon black (described in further detail herein) can be described for a liquid content determined as a function of its oil absorption number (OAN). Wet fillers such as wet carbon black that can be used herein can satisfy the equation: k*OAN / (100+OAN)*100, where k ranges from 0_3-1.1, or 0.5-1.05, or 0.6-1.1, or 0.95-1, or 0.95-1.1, or 1.0-1.1.
[0560] As a more specific example, such a wet filler having this type of 'wet' form as a solid may contain, for example, up to 80% by weight liquid (e.g., water and / or other aqueous liquids) based on the total weight of the wet filler. The wet filler may have a liquid content (e.g., water content) of 80% by weight or less, such as 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, such as about 15% to about 80% by weight, about 20% to about 80%, about 25% to about 80%, about 30% to about 80%, about 35% to about 80%, about 40% to about 80%, about 15% to about 70%, about 20% to about 70%, about 25% to about 80%, about 30% to about 80%, about 40% to about 80%, about 15% to about 70%, about 20% to about 70%, about 25% to about 70%, about 30% to about 80%, about 40% to about 80%, about 15% to about 70%, about 20% to about 70%, about 25% to about 70%, about The wet filler may have a liquid content in an amount of at least 30% by weight (based on the weight of the filler), or at least 40% by weight, or in an amount of 20% to 80% by weight.
[0561] As a more specific example, the wet carbon black may have a liquid content in the range of about 20% to about 70% by weight, for example, about 25% to about 70%, about 30% to about 70%, about 35% to about 70%, about 40% to about 70%, about 45% to about 70%, about 50% to about 70%, about 20% to about 65% by weight, relative to the total weight of the wet carbon black.
[0562] The wetted filler can be any conventional filler used with an elastomer, such as a reinforcing filler, including, but not limited to, carbon black, silica, a filler comprising carbon black, a filler comprising silica, and / or any combination thereof. The filler can be granular or fibrous or flaky, for example, a wet granular filler. For example, a granular filler is made of a discrete body. Such a filler may often have an aspect ratio (e.g., length to diameter ratio) of 3:1 or less, or 2:1 or less, or 1.5:1 or less. Fibrous fillers may have, for example, an aspect ratio of 2:1 or greater, 3:1 or greater, 4:1 or greater, or higher. Typically, fillers used to reinforce elastomers have a size in the micrometer range (e.g., hundreds of micrometers or less) or nanometer range (e.g., less than 1 micrometer). In the case of carbon black, a discrete body of granular carbon black refers to an aggregate or agglomerate formed by primary particles, and does not refer to the primary particles themselves. In other embodiments, the filler may have a flaky structure such as graphene and reduced graphene oxide.
[0563] The filler may be chemically treated (e.g., chemically treated carbon black, chemically treated silica, silicon-treated carbon black) and / or chemically modified. The filler may be or include carbon black to which organic groups (one or more) are attached. The filler may have one or more coatings (e.g., silicon-coated materials, silicon-coated materials, carbon-coated materials) on the filler. The filler may be oxidized and / or have other surface treatments. The filler may include at least one material selected from the following: carbonaceous material, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxide, metal carbonate, pyrolytic carbon, regenerated carbon, recycled carbon black (e.g., as defined in ASTM D8178-19, rCB), graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide spirals as disclosed in PCT Publication No. WO 2019 / 070514A1, or densified reduced graphene oxide granules as disclosed in U.S. Provisional Application No. 62 / 857,296 filed on June 5, 2019, the disclosure of which is incorporated herein by reference), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, or their corresponding coated materials or chemically treated materials (e.g., chemically treated carbon black). There is no limitation on the types of silica, carbon black, or other fillers that can be used. More details about fillers are provided in other sections herein.
[0564] The filler may be or include a blend of carbon black and silica in any weight ratio, such as a weight ratio range of 1:99-99:1, or 25:75-75:25, or 45:55-55:45. As an option, the blend of carbon black and at least one other filler (e.g., silica and / or silicon-treated carbon black) may contain at least 1 wt% carbon black (i.e., not greater than 99 wt% silica), at least 5 wt% carbon black, at least 10 wt% carbon black, at least 20 wt% carbon black, at least 30 wt% carbon black, at least 50 wt% carbon black, at least 66 wt% carbon black, at least 75 wt% carbon black, at least 90 wt% carbon black, at least 95 wt% carbon black, or at least 99 wt% carbon black (i.e., not greater than 1 wt% silica), wherein the weight % values are based on the total weight of the blend on a dry basis. The filler may be a blend of at least two fillers, for example, a filler selected from carbon black, silica, and silicon-treated carbon black.
[0565] As an option, a blend of silica and at least one other filler (e.g., carbon black and / or silicon-treated carbon black) may contain at least 1 wt % silica (i.e., no greater than 99 wt % carbon black), at least 5 wt % silica, at least 10 wt % silica, at least 20 wt % silica, at least 30 wt % silica, at least 50 wt % silica, at least 66 wt % silica, at least 75 wt % silica, at least 90 wt % silica, at least 95 wt % silica, or at least 98 wt % silica, or at least 99 wt % silica (i.e., no greater than 1 wt % carbon black or any other filler), or at least 99.8 wt % silica, wherein the wt % values are based on the total weight of the blend on a dry basis.
[0566] As an option, the mixture may further include one or more non-wetting fillers (eg, any filler as described herein that is not wetted, such as a dry filler, such as a filler having no more than 10% liquid by weight). When a non-wetting filler is present, the total amount of filler may be such that at least 10 wt%, at least 20 wt%, at least 30 wt%, at least 40 wt%, at least 50 wt%, or at least 60 wt%, or at least 70 wt%, or at least 80 wt%, or at least 90 wt%, or at least 95 wt% of the filler is a wet filler, for example, about 10 wt%-99.5 wt%, about 20 wt%-99.5 wt%, about 30 wt%-99.5 wt%, about 40 wt%-99.5 wt%, about 50 wt%-99.5 wt%, or about 50 wt%-99 wt%, 60 wt%-99 wt%, or 70 wt%-99 wt%, or 80 wt%-99 wt% of the total amount of filler may be a wet filler, and the remaining filler is in a non-wetting state or is not considered a wet filler.
[0567] The amount of filler (e.g., wet filler alone or with other fillers) loaded into the mixture can be targeted (by dry weight) to be in the range of 1 phr-200 phr, 1 phr-150 phr, 1 phr-100 phr, or 30 phr-150 phr, such as about 5 phr-100 phr, 10 phr-100 phr, 20 phr-100 phr, 30 phr-100 phr, 40 phr-100 phr, 50 phr-100 phr, or 5 phr-70 phr, 10 phr-70 phr, 20 phr-70 phr. , 30phr-70phr, 35phr-70phr, 40phr-70phr, 5phr-65phr, 10phr-65phr, 20phr-65phr, 30phr-65phr, 35phr-65phr, 40phr-65phr, 5phr-60phr, 10phr-60phr, 20phr-60phr, 30phr-60phr, 35phr-60phr, 40phr-60phr, 5phr-50phr, or other amounts within or outside of one or more of these ranges. Other ranges include about 15 phr to about 180 phr, about 20 phr to about 200 phr, about 20 phr to about 180 phr, about 20 phr to about 150 phr, about 20 phr to about 100 phr, about 25 phr to about 80 phr, about 30 phr to about 150 phr, about 35 phr to about 115 phr, about 35 phr to about 100 phr, about 40 phr to about 100 phr, about 40 phr to about 90 phr, about 40 phr to about 80 phr, about 29 phr to about 175 phr, about 40 phr to about 110 phr, about 50 phr to about 175 phr, about 60 phr to about 175 phr, etc. The filler can be any filler disclosed herein, such as carbon black, silica, or silicon-treated carbon black, either alone or with one or more other fillers. The above phr amounts may also apply to fillers dispersed in the elastomer (filler loading).
[0568] For graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, these fillers can be dispersed in the elastomer at a loading ranging from 1 phr to 100 phr, for example, 1 phr to 50 phr, 1 phr to 25 phr, 1 phr to 20 phr, or 1 phr to 10 phr. When combined with other fillers such as carbon black, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes can be dispersed in the elastomer at a loading ranging from 0.5 phr to 99 phr, for example, 0.5 phr to 50 phr, 0.5 phr to 25 phr, 0.5 phr to 20 phr, or 0.5 phr to 10 phr. In such a combination, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, and multi-walled carbon nanotubes can be present in an amount of at least 1%, at least 2%, at least 5%, at least 10%, at least 15%, at least 20%, at least 30%, at least 40%, or at least 50% by weight of the total amount of fillers dispersed in the elastomer. In some cases, for example, graphene, graphene oxide, reduced graphene oxide (e.g., reduced graphene oxide spirals and densified reduced graphene oxide granules), carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, the loading of these fillers in the total filler is much smaller, and their loading in the composite can range from 0.01phr to 10phr, 0.1-5phr, 0.1-2phr.
[0569] For example, for oil extended elastomers or formulations to which oil is added, filler loadings are typically higher and may range from 20 phr to 250 phr, 50 phr to 250 phr, 70 phr to 250 phr, 60 phr to 150 phr.
[0570] The carbon black may be untreated carbon black or treated carbon black or a mixture thereof. The filler may be or include wet carbon black in the form of pellets, fluffy powders, granules, and / or agglomerates. The wet carbon black may be formed into pellets, granules, or agglomerates in, for example, a granulator, a fluidized bed, or other equipment for making wet fillers.
[0571] Wet carbon black can be one or more of the following:
[0572] - carbon black which has never been dried; and / or
[0573] - carbon black pellets that have never been dried; and / or
[0574] - dried carbon black pellets which have been remoistened, for example with water in a pelletizer; and / or
[0575] - dried carbon black pellets which have been ground and then re-moistened with water in a pelletizer; and / or
[0576] - dried carbon black pellets in combination with water; and / or
[0577] - Fluffy powders, granules, or agglomerates in combination with water.
[0578] In typical carbon black manufacturing, carbon black is initially prepared as a dry, fine granular (fluffy) material. Fluffy carbon black can be densified by conventional pelletizing processes, for example, by combining the carbon black with a liquid, such as adding water, and adding the mixture to a pin pelletizer. Pin pelletizers are well known in the art and include the pin pelletizer described in U.S. Patent No. 3,528,785. The resulting wet pellets are then heated under controlled temperature and time parameters to remove liquid from the pellets before further handling and transportation. In an alternative process, carbon black pellets can be manufactured by a process that omits the drying step. In such a process, the pelletized carbon black contains at least 20% by weight, such as at least 30% by weight, or at least 40% by weight of process water based on the total weight of the wet carbon black. These "never dried carbon black" pellets and can be used directly in the claimed process after pelletizing. As used herein, "never dried" refers to pellets that are prepared from fluffy carbon black, have not undergone a drying step, and retain a water content greater than 15% by weight, such as greater than 20% by weight, greater than 30% by weight, greater than 40% by weight, or in the range of 20-65% by weight, 20-60% by weight, 30-65% by weight, 30-60% by weight, 40-65% by weight, or 40-60% by weight of the total weight of the filler (pellet). For example, never dried pellets may refer to pellets formed from fluffy carbon black that are densified by a conventional pelletizing process and used as is, i.e., have not yet been subjected to a drying step. During storage and / or transportation, the never dried pellets may lose some water. However, it is understood that the "never dried" pellets retain or have a water content as disclosed herein.
[0579] Alternatively, the carbon black pellets that have been dried (e.g., commercially available carbon black pellets) can be re-wetted in a pelletizer. The pellets can be pelletized, milled, classified, and / or ground (e.g., in a jet mill). The resulting carbon black is in a fluffy form and can be re-pelletized in a pelletizer in the presence of water or compressed or agglomerated in other ways to wet the carbon black. Alternatively, the fluffy carbon black can be compressed into other forms, such as brick form, using equipment known in the art. As another option, carbon black, such as carbon black pellets or fluffy carbon black, can be wetted, for example, by using a fluidized bed, an ejector, a mixer, or a drum. When the liquid is water, a water content in the range of 20%-80%, 30%-70% by weight, or other ranges such as 55%-60% by weight can be achieved from carbon black that has never been dried or has been re-wetted relative to the total weight of the wet carbon black.
[0580] The carbon black used in any method disclosed herein can be any grade of reinforcing carbon black and semi-reinforcing carbon black. Examples of ASTM grade reinforcing grades are N110, N12 1, N134, N220, N231, N234, N299, N326, N330, N339, N347, N351, N358, and N375 carbon black. Examples of ASTM grade semi-reinforcing grades are N539, N550, N650, N660, N683, N762, N765, N774, N787, N990 carbon black and / or N990 grade thermal black.
[0581] The carbon black may have any statistical thickness surface area (STSA), which may range, for example, from 20 m 2 / g-250m 2 / g or higher, for example at least 60m 2 / g, for example 60m 2 / g-150m 2 / g, 70m 2 / g-250m 2 / g, 80m 2 / g-200m 2 / g, 90m 2 / g-200m 2 / g、100m 2 / g-180m 2 / g, 110m 2 / g-150m 2 / g, 120m 2 / g-150m 2 / g, or 30m 2 / g-200m 2 / g, etc. STSA (Statistical Thickness Surface Area) is determined based on ASTM test procedure D-5816 (measured by nitrogen adsorption).
[0582] The carbon black may have a compression oil absorption number (COAN) ranging from about 30 mL / 100 g to about 150 mL / 100 g, such as about 30 mL / 100 g to about 125 mL / 100 g, about 30 mL / 100 g to about 115 mL / 100 g, about 50 mL / 100 g to about 150 mL / 100 g, about 50 mL / 100 g to about 125 mL / 100 g, about 50 mL / 100 g to about 115 mL / 100 g, about 60 mL / 100 g to about 150 mL / 100 g, about 50 mL / 100 g to about 125 mL / 100 g, about 50 mL / 100 g to about 115 mL / 100 g, about 60 mL / 100 g to about 150 mL / 100 g The carbon black may have a carbon black oil absorption value in the range of about 60 mL / 100 g, about 70 mL / 100 g to about 150 mL / 100 g, about 70 mL / 100 g to about 125 mL / 100 g, about 70 mL / 100 g to about 115 mL / 100 g, about 80 mL / 100 g to about 150 mL / 100 g, about 80 mL / 100 g to about 125 mL / 100 g, about 80 mL / 100 g to about 115 mL / 100 g, or about 80 mL / 100 g to about 100 mL / 100 g. The compression oil absorption number (COAN) is determined according to ASTM D3493. As an option, the carbon black may have a carbon black oil absorption value in the range of 60 mL / 100 g. 2 / g-150m 2 / g of STSA and 70mL / 100g-115mL / 100g of COAN.
[0583] As mentioned, the carbon black may be a rubber carbon black, and in particular a reinforcing grade carbon black or a semi-reinforcing grade carbon black. and Carbon black sold under the trademark AB, available from Birla Carbon (formerly available from Columbian Chemicals) as and Carbon blacks sold under the trademarks and the CD and HV series, and carbon blacks available from Orion Engineered Carbons (formerly Evonik and Degussa Industries) under and Carbon blacks sold under the trademarks and the CK series, and other fillers suitable for use in rubber or tire applications are used with various implementations. Suitable chemically functionalized carbon blacks include those disclosed in WO96 / 18688 and US2013 / 0165560, the disclosures of which are hereby incorporated by reference. Mixtures of any of these carbon blacks may be used. Carbon blacks having surface areas and structures exceeding the ASTM grades and typical values selected for mixing with rubber, such as those described in U.S. Patent Application Publication No. 2018 / 0282523 (the disclosures of which are incorporated herein by reference), may be used in wet fillers and in compounds made by any of the methods disclosed herein.
[0584] The carbon black may be an oxidized carbon black, such as a carbon black that has been surface treated with an oxidizing agent. Oxidizing agents include, but are not limited to, air; oxygen; ozone; NO2 (including mixtures of NO2 and air); peroxides such as hydrogen peroxide; persulfates, including sodium, potassium, or ammonium persulfates; hypohalites such as sodium hypochlorite, halites, halides, or perhalides (e.g., sodium chlorite, sodium chlorate, or sodium perchlorate); oxidizing acids such as nitric acid; and transition metal-containing oxidants such as permanganates, osmium tetroxide, chromium oxide (chromium oxide), or cerium ammonium nitrate. Mixtures of oxidizing agents may be used, particularly mixtures of gaseous oxidizing agents such as oxygen and ozone. In addition, carbon black prepared by other surface modification methods such as chlorination and sulfonation, which introduce ionic groups or ionizable groups onto the pigment surface, may also be used. Processes that can be used to produce oxidized carbon black are known in the art and several types of oxidized carbon black are commercially available.
[0585] The carbon black may be furnace black, gas black, thermal black, acetylene black, or lamp black, plasma black, recycled carbon black (e.g., as defined in ASTM D8178-19), or a carbon product containing silicon-containing species and / or metal-containing species, etc. The carbon black may be a multiphase aggregate including at least one carbon phase and at least one metal-containing species phase or silicon-containing species phase, i.e., silicon-treated carbon black. In silicon-treated carbon black, silicon-containing species such as silicon oxides or carbides are distributed in at least a portion of the carbon black aggregate as an inherent part of the carbon black. Silicon-treated carbon black is not a carbon black aggregate that has been coated or otherwise modified, but actually represents a dual-phase aggregate particle. One phase is carbon, which still exists as graphitic crystallites and / or amorphous carbon, and the second phase is silicon dioxide, and possibly other silicon-containing species). Therefore, the silicon-containing species phase of the silicon-treated carbon black is an inherent part of the aggregate and is distributed in at least a portion of the aggregate. EcoblackT MSilicon-treated carbon blacks are available from Cabot Corporation. The manufacture and properties of these silicon-treated carbon blacks are described in U.S. Pat. No. 6,028,137, the disclosure of which is incorporated herein by reference.
[0586] The silicon-treated carbon black may include silicon-containing regions that are primarily at the surface of the carbon black aggregate, but are still part of the carbon black and / or the silicon-treated carbon black may include silicon-containing regions distributed in the carbon black aggregate. The silicon-treated carbon black may be oxidized. The silicon-treated carbon black may contain about 0.1% to about 50% by weight, for example, about 0.1% to about 46.6%, about 0.1% to about 46%, about 0.1% to about 45%, about 0.1% to about 40%, about 0.1% to about 35%, about 0.1% to about 30%, about 0.1% to about 25%, about 0.1% to about 20%, about 0.1% to about 15%, about 0.1% to about 10%, about 0.1% to about 5%, or about 0.1% to about 2% by weight of silicon, based on the weight of the silicon-treated carbon black. These amounts may range from about 0.5 wt % to about 25 wt %, from about 1 wt % to about 15 wt % silicon, from about 2 wt % to about 10 wt %, from about 3 wt % to about 8 wt %, from about 4 wt % to about 5 wt %, or to about 6 wt %, all based on the weight of the silicon-treated carbon black.
[0587] Those skilled in the art will recognize that in addition to the silicon content of the silicon-treated carbon black, the surface of the particle may also have varying amounts of silica and carbon black. For example, the surface area of the silicon-treated carbon black may include about 5% to about 95% silica, for example, about 10% to about 90%, about 15% to about 80%, about 20% to about 70%, about 25% to about 60%, about 30% to about 50%, or about 35% to about 40%, for example up to about 20% or up to about 30% silica. The amount of silica at the surface can be determined by the difference between the surface areas of the particles as measured by iodine number (ASTM D-1510) and nitrogen adsorption (i.e., BET, ASTM D6556).
[0588] As another option, the filler, such as carbon black, may be chemically treated. For example, the carbon black may have at least one organic group attached. Attachment may occur via a diazonium reaction, wherein the at least one organic group has a diazonium salt substituent, as detailed, for example, in U.S. Pat. Nos. 5,554,739; 5,630,868; 5,672,198; 5,707,432; 5,851,280; 5,885,335; 5,895,522; 5,900,029; 5,922,118, the disclosures of which are incorporated herein by reference.
[0589] As an option, with respect to the filler being at least silica, one or more types of silica, or any combination of silica (one or more) may be used in any embodiment disclosed herein. The silica may include or be precipitated silica, pyrogenic silica, silica gel, and / or colloidal silica. The silica may be or include untreated silica and / or chemically treated silica. The silica may be suitable for reinforcing elastomer composites and may be characterized by a Brunauer-Emmett-Teller surface area (BET, as measured by multi-point BET nitrogen adsorption, ASTM D1993): about 20 m 2 / g-about 450m 2 / g; about 30m 2 / g-about 450m 2 / g; about 30m 2 / g-about 400m 2 / g; or about 60m 2 / g-about 250m 2 / g, about 60m 2 / g-about 250m 2 / g, about 80m 2 / g-about 200m 2 / g. The silica may have a range of about 80 m 2 / g-250m 2 / g For example, about 80m 2 / g-200m 2 / g or 90m 2 / g-200m 2 / g, 80m 2 / g-175m 2 / g, or 80m 2 / g-150m 2 / g STSA. Highly dispersible precipitated silica can be used as a filler in the present method. Highly dispersible precipitated silica ("HDS") is understood to mean any silica that has a significant ability to deagglomerate and disperse in an elastomer matrix. Such dispersion can be determined in a known manner by electron or optical microscopy of thin sections of the elastomer composite. Examples of commercial grades of HDS include, GT 3000GRAN Silica from Evonik Industries 7000 Silica from Solvay SA 1165 MP, 1115 MP, Premium, and 1200 MP silica from PPG Industries, Inc. EZ 160G silica, and from Evonik Industries 8741 or 8745 silica. Conventional non-HDS precipitated silicas may also be used. Examples of commercial grades of conventional precipitated silica include, KS408 Silica from Solvay SA 175GR Silica from Evonik Industries VN3 silica, and from PPG Industries, Inc 243 silica. Precipitated silica having a silane coupling agent attached to the surface may also be used. Examples of commercial grades of chemically treated precipitated silica include Silane from PPG Industries, Inc. 400, 454, or 458 silica and Coupsil silica from Evonik Industries such as 6109Silicon dioxide.
[0590] Although the amount of liquid in the filler as described above may also apply to silica, as a more specific example, when silica is used partially as a wet filler or entirely as a wet filler, the silica may have the liquid present in an amount of about 25% to about 75% by weight, for example, about 30% to about 75%, about 40% to about 75%, about 45% to about 75%, about 50% to about 75%, about 30% to about 75%, about 5 ... About 70%, about 40% to about 70%, about 45% to about 70%, about 50% to about 70%, about 30% to about 65%, about 40% to about 65%, about 45% to about 65%, about 50% to about 65%, about 30% to about 60% by weight, about 40% to about 60%, about 45% to about 60%, or about 50% to about 60% by weight, based on the weight of all wet filler or based on the weight of only the wet silica present.
[0591] Typically the silica (e.g., silica particles) has a silica content of at least 20 wt%, at least 25 wt%, at least 30 wt%, at least 35 wt%, at least 40 wt%, at least 50 wt%, at least 60 wt%, at least 70 wt%, at least 80 wt%, at least 90 wt%, or almost 100 wt%, or 100 wt%, or about 20 wt% to about 100 wt%, all based on the total weight of the particles. Any of the silica (one or more) can be chemically functionalized, for example, with a chemical group attached or adsorbed, for example, with an organic group attached or adsorbed. Any combination of silica (one or more) can be used. The silica can be partially or completely a silica with a hydrophobic surface, which can be a hydrophobic silica or a hydrophobic silica made hydrophobic by treating (e.g., chemically treating) the surface of the silica. The hydrophobic surface can be obtained by chemically modifying the silica particles with a hydrophobizing silane without ionic groups, such as bis-triethoxysilylpropyl tetrasulfide. Suitable hydrophobic surface treated silica particles for use herein can be obtained from commercial sources, such as from PPG Industries. 454Silica and 400 silica. Silica with a low surface silanol density can be used herein, for example silica obtained by dehydroxylation at temperatures exceeding 150° C. via, for example, a calcination process. Silica in an intermediate form (from never dried silica) obtained from a precipitation process in the form of a cake or paste without drying can be added directly to a mixer as a wet filler, thereby eliminating the complex drying and other downstream processing steps used in the conventional manufacture of precipitated silica.
[0592] In any embodiment and in any step, a coupling agent may be introduced in any of the steps (or in multiple steps or locations) as long as the coupling agent has an opportunity to become dispersed in the composite. The coupling agent may be or include one or more silane coupling agents, one or more zirconate coupling agents, one or more titanate coupling agents, one or more nitro coupling agents, or any combination thereof. The coupling agent may be or include bis(3-triethoxysilylpropyl)tetrasulfane (e.g., Si 69 from Evonik Industries, Struktol SCA98 from Struktol Company), bis(3-triethoxysilylpropyl)disulfane (e.g., Si 75 and Si 266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyl-triethoxysilane (e.g., Si 264 from Evonik Industries), γ-mercaptopropyl-trimethoxysilane (e.g., VP Si 163 from Evonik Industries, Struktol SCA989 from Struktol Company), γ-mercaptopropyl-triethoxysilane (e.g., VP ... VP Si 266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyl-triethoxysilane (e.g., VP Si 266 from Evonik Industries, Struktol SCA985 from Struktol Company), 3-thiocyanatopropyl-triethoxysilane (e.g., VP Si 266 from Evonik Industries, Struk 263), dineoalkanolbis(3-mercapto)propanoate-O,N,N′-bis(2-methyl-2-nitropropyl)-1,6-diaminohexane, S-(3-(triethoxysilyl)propyl) zirconium octanethiol (e.g., NXT coupling agent from Momentive, Friendly, WV), and / or a coupling agent that is chemically similar or has one or more of the same chemical groups. Additional specific examples of coupling agents, by trade name, include, but are not limited to, VP Si 363 from Evonik Industries, and NXT Z and NXT Z-50 silanes from Momentive. The coupling agents described herein can be used to provide hydrophobic surface modification of silica prior to its use in any of the processes disclosed herein (precoupled or pretreated silica). It should be appreciated that any combination of elastomer, additives, and additional compounds can be added to the elastomer compound, such as in a mixer.
[0593] Other fillers are disclosed in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent No. 2423253B1, the disclosures of which are incorporated herein by reference.
[0594] Solid Elastomer Type
[0595] Solid elastomers can be or include natural and / or synthetic elastomers and / or rubbers. Elastomer types include natural rubber (NR), styrene butadiene rubber (SBR), polybutadiene (BR) and polyisoprene rubber (IR), ethylene-propylene rubber (e.g., EPDM), isobutylene-based elastomers (e.g., butyl rubber), polychloroprene rubber (CR), nitrile rubber (nitrile-butadiene rubber) (NBR), hydrogenated nitrile rubber (hydrogenated nitrile-butadiene rubber) (HNBR), polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and silicone elastomers.
[0596] Exemplary elastomers include natural rubber, SBR, BR, IR, functionalized SBR, functionalized BR, functionalized NR, EPDM, butyl rubber, halogenated butyl rubber, CR, NBR, HNBR, fluoroelastomers, perfluoroelastomers, and silicone rubbers, for example, natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, nitrile rubber, hydrogenated nitrile rubber, and blends thereof, or for example, natural rubber, styrene-butadiene rubber, polybutadiene rubber, and blends thereof, for example, a blend of a first and a second solid elastomer. If two or more elastomers are used, the two or more elastomers may be charged simultaneously into the mixer as a blend (as a single charge or as two or more charges) or the elastomers may be added separately in any order and amount. For example, the solid elastomer may include natural rubber blended with one or more of the elastomers disclosed herein, such as butadiene rubber and / or styrene-butadiene rubber. For example, the additional solid elastomer may be added separately (separately) to the mixer and the natural rubber may be added separately to the mixer.
[0597] The solid elastomer may be or include natural rubber. Natural rubber may also be chemically modified in some manner. For example, it may be treated to chemically or enzymatically modify or reduce various non-rubber components, or the rubber molecule itself may be modified with various monomers or other chemical groups such as chlorine. Other examples include epoxidized natural rubber as described in PCT Publication No. WO 2017 / 207912 and natural rubber having a nitrogen content of up to 0.3 wt%.
[0598] Other exemplary elastomers include, but are not limited to, rubber, polymers (e.g., homopolymers, copolymers, and / or terpolymers) of 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (wherein the alkyl group may be methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, and the like. The elastomer may have a glass transition temperature (Tg) ranging from about -120°C to about 0°C as measured by differential scanning calorimetry (DSC). Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber and its derivatives such as chlorinated rubber, polybutadiene, polyisoprene, poly(styrene-co-butadiene), and oil-extended derivatives of any of them. Blends of any of the foregoing may also be used. Particularly suitable synthetic rubbers include copolymers of styrene and butadiene including about 10% to about 70% by weight styrene and about 90 to about 30% by weight butadiene, such as copolymers of 19 parts styrene and 81 parts butadiene, copolymers of 30 parts styrene and 70 parts butadiene, copolymers of 43 parts styrene and 57 parts butadiene, and copolymers of 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes such as polybutadiene, polyisoprene, polychloroprene, and the like, and copolymers of such conjugated dienes with monomers copolymerizable therewith containing olefinic groups such as styrene, methylstyrene, chlorostyrene, acrylonitrile, 2-vinyl-pyridine, 5-methyl-2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, allyl-substituted acrylic esters, vinyl ketone, methylisopropenyl ketone, methyl vinyl ether, α-methylene carboxylic acids and their esters and amides such as acrylic acid and dialkylacrylic acid amides. Also suitable for use herein are copolymers of ethylene and other higher alpha olefins such as propylene, 1-butene, and 1-pentene. Other polymers are disclosed in U.S. Patent Application Publication No. 2018 / 0282523 and European Patent No. 2423253B1, the disclosures of which are incorporated herein by reference. Other polymers include silicone-based elastomers or hybrid systems having silicone and hydrocarbon domains.
[0599] Rubber Chemicals
[0600] The composite prepared by any of the methods disclosed herein may consist of an elastomer and a filler, i.e., no rubber chemicals are present. Alternatively, in addition to the filler and the elastomer, the composite may also include at least one additive selected from an antidegradant and a coupling agent. Alternatively, the composite may include one or more rubber chemicals. In another alternative, the composite may be a composition with a curing agent.
[0601] In a typical dry mixing process (solid elastomer and dry filler), certain additives must often be added; typical additives include antidegradants, coupling agents, and one or more rubber chemicals that enable fillers to be dispersed in the elastomer. Rubber chemicals as defined herein include one or more of the following: processing aids (for providing ease in rubber mixing and processing, such as various oils and plasticizers, waxes); activators (for activating vulcanization processes, such as zinc oxide and fatty acids); accelerators (for accelerating vulcanization processes, such as sulfonamides and thiazoles); vulcanizers (or curing agents, which are used to crosslink rubber, such as sulfur, peroxides); and other rubber additives, such as, but not limited to, retarders, coagents, peptizers, adhesion promoters, tackifiers, resins, flame retardants, colorants, and foaming agents. As an option, rubber chemicals may include processing aids and activators. As another option, the one or more other rubber chemicals are selected from zinc oxide, fatty acids, zinc salts of fatty acids, waxes, accelerators, resins, and processing oils.
[0602] In a typical dry blending process, one or more rubber chemicals (e.g., processing aids) are loaded in the early stages of the mixing cycle to assist in the incorporation of fillers. Thus, rubber chemicals may be necessary, but they may hinder the bonding or interaction between the filler and the elastomer surface and have a negative impact on the properties of the vulcanized product. It has been found that the use of wet fillers enables the filler to be mixed with the solid elastomer in the absence or substantial absence of such rubber chemicals. Without wishing to be bound by any theory, it is believed that the presence of wet fillers eliminates the need for rubber chemicals in the early stages of the mixing cycle, or at any time during the mixing cycle, because the liquid enables the filler to be incorporated into the solid rubber and improves the incorporation of the filler into the solid rubber.
[0603] Thus, as an option, the method comprises charging a mixer with a solid elastomer and a wet filler, and in one or more mixing steps, mixing the solid elastomer and the wet filler in the substantial absence of rubber chemicals at a mixer temperature controlled by at least one temperature control means to form a mixture. Optionally the process further comprises adding at least one additive selected from an antidegradant and a coupling agent during the charging or mixing, i.e., during the one or more mixing steps. Examples of such antidegradants (e.g., antioxidants) and coupling agents are described herein.
[0604] In this process option, in at least one of the mixing steps and preferably in one of the mixing steps, the mixer reaches an indicated temperature of 120°C or higher, for example, at least 125°C or higher, at least 130°C or higher, at least 135°C or higher, at least 140°C or higher, at least 145°C or higher, or at least 150°C or higher. The indicated temperature can be measured by a temperature measuring device in the mixing chamber. The indicated temperature of the mixer can be the same as or differ from the maximum temperature of the mixture or compound achieved during the mixing stage (which can be determined by removing the compound from the mixer and inserting a thermocouple or other temperature measuring device into the compound) by 30 degrees or less, or 20 degrees or less, or 10 degrees or less (or 5 degrees or less or 3 degrees or less or 2 degrees or less). In this mixing method, as an option, one or more rubber chemicals can be added to the mixer when the mixer reaches a temperature of 120°C or higher. In other embodiments, the indicated temperature may range from 120°C-190°C, 125°C-190°C, 130°C-190°C, 135°C-190°C, 140°C-190°C, 145°C-190°C, 150°C-190°C, 120°C-180°C, 125°C-180°C, 130°C-180°C, 135°C-180°C, 140°C-180°C, 145°C-180°C, 150°C-180°C, 120°C-170°C, 125°C-170°C, 130°C-170°C, 135°C-170°C, 140°C-170°C, 145°C-170°C, 150°C-170°C, and the like. The one or more rubber chemicals may be added at an indicated temperature of 120°C or higher; at this point the filler has been distributed and incorporated into the elastomer, and the addition of the rubber chemical is not expected to interfere with the interaction between the filler and the elastomer.
[0605] In this process option, the filling step and the one or more mixing steps before the mixer reaches the indicated temperature are performed in the absence or substantial absence of the one or more rubber chemicals. As defined herein, "substantially absent" refers to a process in which the filling step and the one or more mixing steps can be performed in an amount of less than 10% by weight of the total amount of rubber chemicals in the vulcanized product, such as the cured composite, provided by the composite, or the filling step and the one or more mixing steps can be performed in an amount of less than 5% or less than 1% by weight of the total amount of rubber chemicals in the composite. Since it is optional to include rubber chemicals in the composite, a suitable means for determining the "substantially absent" of the one or more rubber chemicals is to determine the target amount in the vulcanized product prepared by the composite (e.g., after the composite is cured). Therefore, a nominal amount of the one or more rubber chemicals can be added during the filling or mixing, but the amount is not enough to interfere with the filler-elastomer interaction. As a further example of "substantially absent", the filling and mixing can be carried out in the presence of the one or more rubber chemicals in the following amounts or loadings: 5 phr or less, 4 phr or less, 3 phr or less, 2 phr or less, 1 phr or less, or 0.5 phr or less, 0.2 phr or less, 0.1 phr or less, based on the resulting vulcanized product. As an option, the compound discharged in step (d) does not contain the one or more rubber chemicals (0 phr).
[0606] When discharged from the mixer, the compound includes a filler dispersed in the elastomer with a loading of at least 1 phr, for example, at least 20 phr, wherein the filler yield loss is not more than 10%. For this process, the compound at the time of discharge may not exist or substantially do not exist one or more rubber chemicals, for example, except for any antidegradant that already exists when mixing is started. Alternatively, the compound at the time of discharge may contain at least one additive selected from antidegradant and coupling agent, which can be added at any time during filling or mixing. Alternatively, the compound at the time of discharge may contain or substantially do not exist any rubber chemicals, for example, if one or more antidegradants are not added when mixing is started. In other words, as an option, the mixture is basically composed of or is basically composed of: solid elastomer and wet filler. As another option, the mixture is composed of or is basically composed of: solid elastomer, wet filler and at least one antidegradant. As another option, the mixture is composed of or is basically composed of: solid elastomer, wet filler, at least one antidegradant and coupling agent.
[0607] In any embodiment disclosed herein, as an option, after the mixing of at least the solid elastomer and the wet filler has begun and before the discharge step, the method may further include further adding at least one antidegradant to the mixer so that the at least one antidegradant is mixed with the solid elastomer and the wet filler. The optional addition of the antidegradant (one or more) may occur at any time before the discharge step. For example, the addition of the antidegradant (one or more) may occur before the composite is formed and has a liquid content of 10% by weight or less, or 5% by weight or less. Examples of antidegradants that can be introduced are N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD), and others described in other sections of this article. The antidegradant can be introduced in an amount ranging from 0%-5%, 0.5%-5%, 1%-5%, 0%-3%, 0.5%-3%, 1%-3%, 0%-2%, 0.5%-2%, or 1%-2% based on the weight of the composite formed. Antidegradants added during the packing step or the mixing step can help prevent elastomer degradation during mixing; however, due to the presence of liquid in the mixture, the degradation rate of the elastomer is lower compared to dry blending processes and the addition of antidegradants can be delayed.
[0608] At least one additive may be included during the mixing method described herein or after forming the composite. The at least one additive may include a curing agent bag or at least one curing agent. In order to produce a vulcanizable composite, the added curing agent bag may include a crosslinking agent, and any activator and accelerator. In the case of using sulfur as a crosslinking agent, typical activators include zinc oxide and or stearic acid, and typical accelerators include sulfonamides such as N-tert-butyl-2-benzothiazole sulfonamide (TBBS) and N-cyclohexyl-2-benzothiazole sulfonamide (CBS). Other curing agents used in rubber processing are peroxides, carbamate crosslinkers, metal oxides, acetoxysilane compounds, phenolic resins, etc. Other suitable components for other crosslinking systems based on sulfur are well known to those skilled in the art.
[0609] Other rubber chemicals include antioxidants, processing aids, extender oils, waxes, various resins, coupling agents, and additional antidegradants. Antioxidants include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and those listed in WO2012 / 037244 (the disclosure of which is incorporated herein by reference).
[0610] As an option, the rubber chemicals can be combined with the compound in a mechanical mixer. In particular, additives such as fillers (which can be the same or different from the fillers used in the mixer; exemplary fillers include silica, carbon black, and / or zinc oxide), other elastomers, other or additional masterbatches, antidegradants (e.g., antioxidants), coupling agents, plasticizers, processing aids (e.g., stearic acid (which can also be used as a curing agent), liquid polymers, oils, waxes, etc.), resins, flame retardants, extender oils, and / or lubricants, and mixtures of any of them can be added to the mechanical mixer. Additional elastomers can be combined with the compound to produce an elastomer blend. Suitable elastomers include any of the elastomers used in the above-mentioned mixing process. Exemplary elastomers include, but are not limited to, rubber, polymers (e.g., homopolymers, copolymers and / or terpolymers) of 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (wherein the alkyl group may be methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, etc. Antidegradants (examples of degradation inhibitors) may be amine-type antidegradants, phenol-type antidegradants, imidazole-type antidegradants, metal carbamates, p-phenylenediamine (one or more) and / or dihydrotrimethylquinoline (one or more), polymerized quinine antidegradants, and / or waxes and / or other antidegradants used in elastomer formulations. Specific examples include, but are not limited to, N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine (6-PPD, for example, ANTIGENE 6C available from Sumitomo Chemical Co., Ltd., and NOCLAC 6C available from Ouchi Shinko Chemical Industrial Co., Ltd.), “Ozonon” 6C from Seiko Chemical Co., Ltd., polymerized 1,2-dihydro-2,2,4-trimethylquinoline (TMQ, for example, Agerite Resin D, available from RT Vanderbilt), 2,6-di-tert-butyl-4-methylphenol (available from Vanderbilt Chemicals LLC as Vanox PC), butylated hydroxytoluene (BHT), and butylated hydroxyanisole (BHA), and the like. Other representative antidegradants may be, for example, diphenyl-p-phenylenediamine and others, for example, those disclosed in Vanderbilt Rubber Handbook (1978), pages 344-346.
[0611] Compounding machine
[0612] The sealed mixer of specific type is a Banbury mixer or a Brabender mixer, any of which can be used for the composite forming method described herein. The sealed mixer can be a tangential sealed mixer. The sealed mixer can be a kneading type sealed mixer. Other mixers include kneading type sealed mixers. The sealed mixers commercially available from Farrel-Pomini, Harburg Freudenberger Maschinenbau GmbH (HF), Kobelco or Pelmar Eng'r Ltd can be used. In addition to the option of using steam or water or other fluids in the rotor, in addition or alternatively, the sealed mixer can have a cooling or heating jacket at one area or part of the mixing chamber or more than one area or part to control the temperature of the components mixed therein. This can produce one or more heating / cooling zones in the wall of the mixer or a part of the wall. The mixer can be a single-stage mixer or a multi-stage mixer (e.g., two stages or more). Examples of useful mixers and designs are described in European Patent No. 2423253 Bl and US Patent No. 7,556,419, the disclosures of which are incorporated herein by reference.
[0613] As another option, the mixer can be a continuous mixer. For example, the solid elastomer and wet filler can be mechanically processed by using one or more of the following: a continuous closed mixer, a twin-screw extruder, a single-screw extruder, or a roller mill, such as those described in U.S. Patent No. 9,855,686 B2 (the disclosure of which is incorporated herein by reference). Suitable kneading and plasticating devices are well known and commercially available, including, for example, Unimix continuous mixers and MVX (mixing, venting, extrusion) machines (from Farrel Pomini Corporation of Ansonia, Conn.), FCM TM Farrel continuous mixer, long continuous mixer (from Pomini, Inc.), Pomini continuous mixer, twin rotor co-rotating kneading extruder, twin rotor counter-rotating non-kneading extruder, continuous compounding extruder, twin shaft grinding extruder (produced by Kobe Steel, Ltd.), and Kobe continuous mixer. Alternative plasticating equipment suitable for use with one or more embodiments disclosed herein are familiar to those skilled in the art.
[0614] The mixing can be carried out with a mixer(s) having at least one rotor and the mixer can be one or more of the following: a kneader, a roll mill, a screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous compounder, and / or a twin-screw extruder.
[0615] The mixing can be performed with a mixer (one or more) having at least one rotor and the mixer can have a two-ribbed rotor, a four-ribbed rotor, a six-ribbed rotor, an eight-ribbed rotor, and / or one or more screw rotors.
[0616] Post-processing steps
[0617] The discharged composite may undergo one or more post-processing steps. Post-processing may be performed after any mixing step. For multi-stage mixing, post-processing may be performed after the first stage and / or after the second stage, and so on. The composite may be post-processed to provide a composite that is dried, homogenized, extruded, calendered, ground, etc. One or more post-processing steps may be shaped or formed or may allow for improved handling, but preferably the filler is not substantially dispersed. For example, the one or more post-processing steps may impart at most a small amount (e.g., less than 300 kJ / kg composite, less than 200 kJ / kg composite, less than 100 kJ / kg composite, or less than 50 kJ / kg composite) of energy. For example, the one or more post-processing steps do not result in a significant temperature increase of the composite (as a result of low energy input).
[0618] As an option, the liquid content of the discharged composite can be 10% by weight or less (e.g., 5% by weight or less) when discharged and the liquid content can be further reduced by one or more additional liquid (e.g., water) removal steps, such as using further mixing step(s), compounding step(s), dryers, or applying heat, or other means to remove water or liquid from the mixture, to achieve a desired composite liquid content that is lower than the liquid content when discharged from the mixer. Typically, post-processing steps can include compressing the composite to remove 1% to about 50% by weight, such as 1% to about 10% by weight of any residual liquid phase based on the total weight of the composite.
[0619] In any of the methods of producing a composite disclosed herein, the method may further comprise one or more of the following steps after formation of the composite:
[0620] - one or more saving steps;
[0621] - the composite may be further dried using one or more drying steps to obtain a dried composite;
[0622] - one or more extrusion steps;
[0623] - one or more calendering steps;
[0624] - one or more grinding steps to obtain a ground composite;
[0625] - one or more granulation steps;
[0626] - one or more cutting steps;
[0627] - one or more packaging steps to obtain a packaged product or mixture;
[0628] - the packaged mixture or product may be disintegrated to form a granulated mixture; and / or
[0629] - one or more mixing or compounding steps; and / or
[0630] - One or more tableting steps.
[0631] The one or more processing steps can be implemented using one or more of the following: an internal mixer, a kneader, a roll mill, a screw extruder, a twin-screw extruder, a multi-screw extruder, a continuous mixer, and / or a twin-screw discharge extruder that is equipped with a roller die (e.g., a twin-screw tablet press) or equipped with a fixed knife.
[0632] As a further example, following formation of the composite, the following sequence of steps may occur and each step may be repeated a number of times (using the same or different settings):
[0633] - one or more preservation steps to develop further flexibility;
[0634] - one or more cooling steps;
[0635] - further drying the composite to obtain a further dried composite;
[0636] - kneading or compounding the composite to obtain a compounded mixture;
[0637] - grinding the compounded mixture to obtain a ground mixture (e.g., rolling);
[0638] - Granulate the milled mixture:
[0639] - optionally packaging the mixture after granulation to obtain a packaged mixture;
[0640] - Optionally disintegrating and mixing the packaged mixture.
[0641] As an option, the compound can be further processed on an open mill. The compound can be discharged as a certain length of extrudate from a continuous mixer or an extruder and can be cut into smaller lengths before entering the open mill. Optionally, the compound can be fed to the open mill via a conveyor. The conveyor can be a conveyor belt, a conduit, a pipeline or other suitable means for conveying the compound from the continuous mixer to the open mill. The open mill can include a pair of rollers, which can be optionally heated or cooled to provide enhanced open mill operation. Other operating parameters of the open mill can include the gap distance between the rollers, the storehouse height, that is, the reservoir of the material in the gap between the rollers and the top, and the speed of each roller. The speed of each roller and the temperature of the fluid for cooling each roller can be independently controlled for each roller. The gap distance can be about 3mm-about 10mm or about 6mm-about 8mm. The roller speed can be about 15rpm-about 70rpm, and the rollers can rotate toward each other relative to the inlet side of the open mill. The friction ratio, i.e., the ratio of the speed of the collection roll (e.g., the roll on which the plasticated product is collected) to the speed of the back roll, can be from about 0.9 to about 1.1. The fluid used to cool the roll can be from about 35°C to about 90°C, for example, from about 45°C to about 60°C, from about 55°C to about 75°C, or from about 70°C to about 80°C. In addition to controlling the operation of the mill to provide the desired level of plastication and desiccation for the plasticated product, it is also desired that the output of the mill should be collected on the collection roll as a smooth sheet. The residence time of the composite in the mill can be determined in part by the roll speed, the gap distance, and the desired amount of plastication and drying and can be from about 10 minutes to about 20 minutes for materials that have been plasticated, such as in a twin-rotor continuous mixer.
[0642] Those skilled in the art will recognize that different combinations of devices may be employed. Depending on which device is used, it may be desirable to operate them under conditions different from those described above to impart varying amounts of processing and / or further drying to the material. Additionally, it may be desirable to use more than one specific type of device, such as an open mill or an internal mixer, in series or to pass the plasticated product through a given device more than once. For example, the composite may be passed through an open mill twice or more or through two or three or more open mills in series. In the latter case, it may be desirable to operate each open mill under different operating conditions, such as speed, temperature, different (e.g., higher) energy inputs, etc. The composite may be passed through one, two, or three open mills after mixing in an internal mixer.
[0643] Compounding
[0644] Additionally or alternatively, the composite may be compounded with one or more of an antidegradant, a rubber chemical, and / or a curing agent, and vulcanized to form a vulcanizate. Such a vulcanized compound may have one or more improved properties, such as one or more improved rubber properties, such as, but not limited to, improved hysteresis, wear resistance and / or rolling resistance (e.g., in a tire), or improved mechanical and / or tensile strength, or improved tan δ and / or improved tensile stress ratio, etc.
[0645] As an example, in the compounding step (which may also be the initial mixing (mixing) step), the components of the curing agent package except sulfur or other crosslinking agents and accelerators are combined with the neat compound in a mixing device (non-curing agents such as rubber chemicals and / or antidegradants are often premixed and collectively referred to as "fines"). The most common mixing equipment is a closed mixer, for example, a Banbury or Brabender mixer, but other mixers such as continuous mixers (e.g., extruders) may also be used. Afterwards, in the compounding step, crosslinking agents such as sulfur and accelerators (if necessary) (collectively referred to as curing agents) are added. The compounding step is often carried out in equipment of the same type as the mixing step, but can be carried out on different types of mixers or extruders or on a rolling mill. Those skilled in the art will recognize that once the curing agent has been added, once the activation conditions appropriate for the crosslinking agent are achieved, vulcanization will begin. Therefore, in the case of using sulfur, the temperature during mixing is preferably kept significantly lower than the curing temperature.
[0646] As an option, any method of preparing a composite disclosed herein may involve adding any rubber chemicals at a later stage in the process of forming the composite or avoiding adding rubber chemicals at any point in the process of forming the composite. With respect to the latter option, the rubber chemicals may be added to the composite during the compounding stage. For example, the rubber chemicals may be added after the temperature of the composite reaches 120°C or higher, such as 130°C or higher, or 140°C or higher. Alternatively, the rubber chemicals may be added in one or more compounding steps or after the composite is dumped from the initial mixing step (one or more) of forming the composite. With respect to this option, adding the rubber chemicals too early in the initial mixing step (one or more) may potentially hinder a smaller degree of contact between the rubber and the filler and may in turn result in overall poor filler dispersion and / or lower rubber-filler interaction in the composite. For example, in some scenarios, adding the rubber chemical too early in the mixing process may result in the vulcanizate exhibiting lower tensile properties, such as lower tensile stress ratio (M300 / M100), and poor filler dispersion, compared to when the rubber chemical is added after the temperature of the compound reaches 120°C or higher (e.g., 130°C or higher or 140°C or higher) or when the rubber chemical is added during the one or more compounding steps. In some cases, when the elastomer is, for example, natural rubber or the elastomer includes natural rubber, such undesirable effects of the rubber chemical may be seen if added too early.
[0647] Compounds and vulcanizates
[0648] Traditionally, reinforcement (e.g., stiffness) in elastomeric composites can be increased by increasing the loading, surface area, and structure of filler materials. The final mechanical properties of the composite can also be determined by how the particles are dispersed and arranged in the composite. In testing of composites and the resulting vulcanizates prepared by the present process, it has been found that certain dispersion states achieve the desired mechanical properties of the resulting vulcanizates.
[0649] The extent of filler distribution and dispersion in the elastomeric network for both the composite and the vulcanizate ("dispersion state" or "dispersed state" or macro-dispersion) can be examined via optical microscopy in transmission mode of a composite slice (e.g., 2 μm or less, e.g., 0.5 μm-2 μm, 0.5 μm-1.5 μm, about 1 μm thickness). The optical image of the slice (in transmission mode) typically shows a light background dense with dark objects, each object being the result of a pile of carbon black agglomerates. Since the image is observed in two dimensions, each dark object covers an area that can be associated with the type of "particle" (with respect to macro-dispersion, the term "particle" is intended to represent the area coverage of carbon black agglomerates and is distinguished from the "primary particles" that form a single carbon black aggregate. The aggregate has a size of about 0.1 μm, which is below the resolution of optical microscopy). The particle "diameter" is defined herein as the "area equivalent diameter" of the filler and is typically in the micrometer size range. Therefore, the dispersion state can be indicated by the form of particle size distribution, whether it is indicated by the area coverage of particles having a certain size or the number of particles per unit area.
[0650] For compounds, the state of filler distribution and dispersion in the elastomer can also be evaluated at the micron and submicron level ("microdispersion") and can be demonstrated by rheological properties such as those measured by a Rubber Process Analyzer (RPA).
[0651] RPA is a tool for analyzing the rheological properties of elastomeric materials such as the composites described herein by subjecting the material to a strain sweep. The strain sweep test applies a series of strain amplitudes to the material, and a behavior known as the "Payne effect" can be observed, which is considered to be a measure of microscopic dispersion. One way to evaluate such an effect is to measure the dynamic storage modulus G' at low strain and at high strain, the ratio of which is defined as the "Payne ratio". The Payne effect can also be affected by the addition of rubber chemicals and the molecular weight of the rubber.
[0652] The composites prepared by the present process can be compared to composites prepared by a dry blending method (dry filler and dry elastomer). By doing so, differentiated rheological behaviors can be confirmed. At similar levels of reinforcement (determined by G' or G'(50%) measured at 50% strain amplitude), any of the methods disclosed herein can achieve composites with lower Payne's Effect compared to dry blending methods or comparative wet blending processes (e.g., comparative processes in which wet fillers are combined with solid elastomers). It is known that a lower Payne's Effect indicates desirable properties in the final product, such as rolling resistance of a tire. At the same time, at similar levels of Payne's Effect, any of the methods disclosed herein can provide composites with higher reinforcement G'(50%) compared to those achieved by dry blending methods or comparative wet blending processes in which wet fillers and solid elastomers are combined.
[0653] It has been found that for the composites prepared by the present process, the following relationship or equation can be achieved:
[0654] Payne ratio ≤ 0.1*G'@50%-y
[0655] Wherein the Payne ratio is G'(0.1%) / G'(200%), G'(0.1%) is the dynamic storage modulus measured at a strain amplitude of 0.1%, G'(200%) is the dynamic storage modulus measured at a strain amplitude of 200%, G'(50%) is the dynamic storage modulus measured at a strain amplitude of 50%, the dynamic storage modulus is measured at a frequency of 1 Hz at 100°C, and y is a number ranging from 7 to 10.
[0656] This relationship was not achieved for composites made by dry mixing methods or by comparative wet mixing processes.
[0657] Further, the macroscopic dispersion of the composite can be evaluated using optical microscopy of the slices as discussed above. Macroscopic dispersion indicators such as the particle size distribution (weighted by area) and area % of filler particles larger than 2 μm can be obtained. Using any of the methods disclosed herein, the composite can be made so that there is a low number of large particles relative to the total area, which characterizes the distribution of fillers such as carbon black in the elastomer. As an option, the dispersion state can be measured by the "d 90 " Particle size indication. As an option, the dispersion state can be measured by "% area contribution from particles > 2 μm". The area contribution from the particles can be reported for the imaged area. The total imaged area of the image (μm 2 ) can be determined by the number of pixels and the image resolution. An image can have the following dimensions: width and height, each reported in pixels, and the corresponding area can be reported as (pixels) 2 For area, the resolution is available as (μm / pixel) 2 The imaging area is the product of:
[0658] (Area)*(resolution).
[0659] In certain embodiments, the filler has a dispersion state in the elastomer that satisfies the following equation:
[0660] A≤1.25*B+x
[0661] in:
[0662] A is the area equivalent diameter of the filler particles in the composite. 90 (μm), and
[0663] B is [Total area of particles with area equivalent diameter ≥ 2 μm] x100%
[0664] [Total imaging area]
[0665] Where B ≥ 1%,
[0666] A and B are measured by optical microscopy in transmission mode of sections, and x is a number in the range of 15-20.
[0667] In other words, 90% (d 90 ) may have an area equivalent diameter less than 1.25B+x. By this relationship, the present composite may have a dispersion state characterized by a low number of large particles relative to composites prepared by dry mixing and comparative wet mixing methods.
[0668] Certain embodiments provide compounds that have (a) better microdispersion properties than compounds made by prior methods of combining dry fillers with solid elastomers, and (b) distinct macrodispersion properties from liquid masterbatches and comparative wet mixing processes (combining wet fillers with solid elastomers). In other words, the combination of microdispersion and macrodispersion properties or features of at least some of the compounds disclosed herein are unique and not seen with previous compounds.
[0669] Various composites can be made by one or more methods disclosed herein. For example, certain composites disclosed herein include an elastomer that may include or contain at least 50% (by weight) natural rubber. Further, the composite includes a filler dispersed in the natural rubber (or dispersed in the elastomer). The filler may include or contain carbon black.
[0670] Thus, disclosed herein are composites having the following properties:
[0671] (a) Fillers are dispersed in natural rubber according to equation (1):
[0672] A≤1.25·B+x (1)
[0673] in:
[0674] A is the area equivalent diameter of the filler particles in the composite. 90 (μm), and
[0675] B is [Total area of particles with area equivalent diameter ≥ 2 μm] x100%
[0676] [Total imaging area]
[0677] Where B ≥ 1%,
[0678] A and B were determined by light microscopy of sections, and
[0679] x = 15-20; and
[0680] (b) The complex has properties that conform to equation (2):
[0681] G'(0.1%) / G'(200%)≤0.1·G'(50%)-y (2)
[0682] Wherein G'(0.1%) is the dynamic storage modulus measured at 0.1% strain amplitude, G'(200%) is the dynamic storage modulus measured at 200% strain amplitude, G'(50%) is the dynamic storage modulus measured at 50% strain amplitude, the dynamic storage modulus is measured at 100°C at a frequency of 1 Hz, and y=7-10.
[0683] The carbon black may be the carbon black as described above.
[0684] The variables x and y in the above equations may be integers or decimals (e.g., x may be 15, 16, 17, 18, 19, or 20, or 15.1, 15.2, 15.3, etc. for x, and / or y may be 7, 8, 9, or 10, or 7.1, 7.2, 7.3, etc. for y).
[0685] As an option, the carbon black present in the composite may have a carbon content of at least 60 m 2 / g STSA, for example, the range is 60m 2 / g-210m2 / g or 70m 2 / g-210m 2 / g, or 80m 2 / g-210m 2 / g, or 90m 2 / g-210m 2 / g, or 100m 2 / g-210m 2 / g etc.
[0686] As an option, the carbon black present in the composite may have a COAN of at least 75 mL / 100 g, e.g., 75 mL / 100 g to 150 mL / 100 g, 85 mL / 100 g to 150 mL / 100 g, 95 mL / 100 g to 150 mL / 100 g, or 105 mL / 100 g to 150 mL / 100 g.
[0687] As an option, the composite may have a carbon black loading of 60 phr or less, such as 50 phr or less, or 40 phr or less, or 30 phr or less, or 20 phr or less, or 1 phr-60 phr, or 5 phr-60 phr, or 10 phr-60 phr.
[0688] As an option, the carbon black present in the composite may have a BET / STSA ratio in the range of 1-1.2, such as a BET / STSA ratio of 1-1.15, 1-1.1, or 1-1.05.
[0689] As an option, with respect to the total filler amount in the composite, the carbon black may comprise at least 50% by weight relative to the total weight of the filler, such as at least 60%, at least 70%, at least 80%, at least 90%, at least 99%, or 100% by weight relative to the total weight of the filler, such as 50%-100% or 60%-95% by weight. The carbon black may be the only filler or may be the predominant filler by weight.
[0690] As an option, while the majority of the filler is carbon black, silica may be present in the composite if the filler comprises a blend of carbon black and silica, for example, a blend of 90 wt% or more carbon black and 10% or less silica.
[0691] As an option, the elastomer comprises at least 50% by weight of natural rubber relative to the total weight of the elastomer. This amount may be at least 75% by weight, at least 90% by weight, at least 95% by weight or 100% by weight of natural rubber. This option may be combined with an amount of carbon black in an amount of at least 50% by weight relative to the total weight of the filler.
[0692] Also disclosed herein are vulcanized products prepared from the composite disclosed herein. The vulcanized products may include or contain fillers (as described herein) dispersed in the following elastomers: it is or includes natural rubber, for example, a blend of natural rubber and polybutadiene rubber and / or styrene-butadiene rubber. The filler may include or include or be carbon black. The carbon black may be the carbon black as described above.
[0693] In the vulcanized rubber compound including carbon black, the state of microdispersion can be characterized using resistivity measurement results. Resistivity depends especially on the loading of carbon black and its specific surface area and structure. In order to apply resistivity as the characteristic of carbon black microdispersion, it is standardized by the parameter δ considering carbon black loading, particle size and structure. This parameter represents the theoretical average spacing between the aggregates in the filled rubber system, assuming that monodisperse particle size and particles are perfectly random dispersion (MJ.Wang, S.Wolff and EHTan in Rubber Chemistry and Technology, 1993, Vol.66, p 178).
[0694] For the vulcanizates, the macrodispersion is determined by the parameter v (ie the number of particles / mm having an area equivalent diameter of at least 4 μm as determined by optical microscopy of the sections). 2) is defined. As discussed previously, each "particle" is defined by the area coverage of the dark object as observed in the optical image. In the cured material, the area measurement can be distorted by a small amount of very large non-carbon black entities such as other compounding ingredients such as ZnO, etc. Therefore, the approach here is to use the number of particles (and remove the contribution from a single large particle) rather than the area to define the total undispersed area, as it is considered to be more representative of the property attributes of the cured material.
[0695] Certain embodiments provide a vulcanizate that may have at least carbon black present as a filler, and the carbon black may have at least 60 m 2 / g STSA and a BET / STSA ratio in the range of 1-1.2; and the vulcanizate has resistivity and dispersion properties satisfying equation (3):
[0696] [ln(R)-3.8] / [0.28·δ]≥0.0004·v+0.9 (3)
[0697] in:
[0698] R is the resistivity, measured in ohm·cm;
[0699] δ=(6000·[0.806·φ-1 / 3β-1 / 3-1] / ρS)x β1.43
[0700] in:
[0701] φ = volume fraction of carbon black in the composite,
[0702] S = BET surface area of carbon black, in m 2 / g,
[0703] ρ = carbon black density, assumed to be 1.8 g / cm 3 ,
[0704] β=φeff / φ,
[0705] φeff is the effective volume fraction of carbon black taking into account the entrapped rubber, which is calculated as follows: φeff = φ[1 + (0.0181*COAN)] / 1.59, where COAN is the compression oil absorption number of carbon black as determined by ASTM D3493; and
[0706] v ≥ 65, where v is the number of particles / mm having an area equivalent diameter of at least 4 μm as determined by optical microscopy of the section 2 .
[0707] Regarding the vulcanized product, the carbon black may have a range of 60 m 2 / g-210m 2 / g, or 60m 2 / g-190m 2 / g of STSA.
[0708] With respect to the vulcanizate, the carbon black may have a COAN of at least 75 mL / 100 g.
[0709] With respect to the vulcanizate, the vulcanizate may have a carbon black loading of 60 phr or less.
[0710] With respect to the vulcanizate, the filler may include or contain carbon black in an amount of at least 50% by weight relative to the total weight of the filler, or at least 90% by weight relative to the total weight of the filler, or at least 99% by weight relative to the total weight of the filler. ...
Claims
1. A method for preparing a composite, wherein include: (a) charging a first mixer having one or more rotors with at least a solid elastomer and a wet filler, the wet filler comprising a filler and a liquid present in an amount of at least 15% by weight based on the total weight of the wet filler; (b) mixing the at least solid elastomer and the wet filler in one or more mixing steps to form a mixture, and in at least one of said mixing steps, said mixing is carried out at a mixer temperature controlled by at least one temperature control means, wherein the one or more rotors are operated at a tip speed of at least 0.6 m / s for at least 50% of the mixing time, and at least a portion of the liquid is removed from the mixture by evaporation; (c) discharging a mixture from the first mixer, the mixture comprising a filler dispersed in an elastomer at a loading of at least 20 phr, wherein the mixture has a liquid content reduced to an amount less than the liquid content at the beginning of step (b), and wherein the mixture has a material temperature in the range of 100° C. to 180° C.; (d) mixing the mixture from (c) in a second mixer to obtain a composite, wherein the second mixer is operated under at least one of the following conditions: (i) A jacking pressure of 5 psi or less; (ii) the jack is raised to at least 75% of its maximum level; (iii) the jack is operated in floating mode; (iv) the top pin is positioned so that it does not substantially contact the mixture; (v) the mixer is jackless; and (vi) the fill factor of the mixture is in the range of 25% to 70%; and (e) discharging a composite from the second mixer, the composite having a liquid content of less than 3% by weight based on the total weight of the composite.
2. The method of claim 1, wherein the filler comprises at least one material selected from the group consisting of carbonaceous materials, carbon black, silica, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, pyrolytic carbon, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, single-walled carbon nanotubes, multi-walled carbon nanotubes, or combinations thereof, and coated and treated materials thereof.
3. The method of claim 1, wherein the filler comprises at least one material selected from the group consisting of carbon black and silicon-treated carbon black.
4. The method of claim 1, wherein the filler comprises carbon black.
5. The method of any one of claims 1 to 4, wherein the wet filler has the liquid present in an amount of at least 20% by weight.
6. The method of any one of claims 1 to 4, wherein the wet filler has the liquid present in an amount ranging from 40% to 65% by weight.
7. The process of any one of claims 1 to 6, wherein the mixture has a liquid content that is reduced to an amount less than 50% by weight of the liquid content of the mixture at the start of step (b).
8. The process of any one of claims 1 to 6, wherein the mixture in (c) has a liquid content in the range of 1% to 20% by weight.
9. The process of any one of claims 1 to 6, wherein the mixture in (c) has a liquid content in the range of 2% to 15% by weight.
10. The method of any one of claims 1 to 9, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 60°C to 110°C z .
11. The process of any one of claims 1 to 10, wherein the time between the start of mixing and the discharging in (c) ranges from 3 minutes to 15 minutes.
12. The method of any one of claims 1 to 10, wherein the plunger down time for mixing in the first mixer ranges from 3 minutes to 15 minutes.
13. The method of any one of claims 1 to 12, wherein the filling factor of the mixture in the first mixer is in the range of 50% to 70%.
14. The method of any one of claims 1 to 13, wherein the filling factor of the mixture in the second mixer is in the range of 25% to 60%.
15. The method of any one of claims 1 to 14, wherein the solid elastomer is selected from the group consisting of natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene rubber, isobutylene-based elastomers, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, silicone elastomers, and blends thereof.
16. The method of any one of claims 1-15, wherein the solid elastomer comprises natural rubber.
17. The method of any one of claims 1 to 16, wherein the mixture has a material temperature in the range of 120°C to 150°C.
18. The method of any one of claims 1 to 16, wherein the mixture has a material temperature in the range of 130°C to 140°C.
19. The method of any one of claims 1 to 18, wherein the elastomer is selected from the group consisting of natural rubber, styrene-butadiene rubber, butadiene rubber, and blends thereof.
20. The method of any one of claim 19, wherein the mixture has a material temperature in the range of 120°C to 170°C.
21. The method of any one of claims 1 to 20, wherein the resulting total specific energy of the mixing in (b) is in the range of 1000 to 2500 kJ / kg.
22. The method of any one of claims 1 and 5-21, wherein the filler comprises silica.
23. The method of claim 22, wherein in step (b) and optionally in step (a), the at least one temperature control means is set to a temperature T in the range of 40°C to 110°C z .
24. The method of claim 22 or 23, wherein the wet filler has the liquid present in an amount ranging from 20% to 65% by weight.
25. The method of any one of claims 22-24, wherein the filler comprises silica and the elastomer comprises natural rubber.
26. The method of claim 25, wherein the mixture has a material temperature in the range of 100°C to 150°C.
Citation Information
Patent Citations
Rubber composition and pneumatic tire
EP2423253B1
Modified Fillers And Elastomeric Composites Comprising Same
US20130165560A1
Tire with tread with oxidized carbon black
US20180282523A1
Carbon black pelletization including heated boundary wall
US3528785A
Elastomeric compounds incorporating silicon-treated carbon blacks
US6028137A
